3D-Kenngrößen zur Beschreibung von Feinblechoberflächen. - Pfestorf, Markus; Engel, Ulf; Geiger, Manfred (Blech, Rohre, Profile, 1996)
LFT Import::2019-07-15 (667)

3D-Kennwerte zur Beschreibung technischer Oberflächen. - Geiger, Manfred; Pfestorf, Markus; Engel, Ulf (Tagungsbund IX. Int. Oberflächenkolloquium Chemnitz, 1996)
LFT Import::2019-08-05 (653)

3D-Lichtschnittsensor zur Biegewinkelerfassung - Geiger, Manfred; Heckel, Werner (Blech, Rohre, Profile, 1993)
LFT Import::2019-07-15 (403)

3D Oberflächenanalyse bei Feinblechen - Geiger, Manfred; Pfestorf, Markus; Engel, Ulf (Stahl und Eisen, 1995)
LFT Import::2019-07-16 (1975)

3D Sensor based Closed Loop Control System for Flexible Forming Processes - Hutterer, Angelika; Otto, Andreas; Geiger, Manfred (Proceedings of 7th International Fall Workshop, Vision, Modelling and Visualisation, 2002)
LFT Import::2019-08-05 (1701)

3D-Surface Parameters and their Application on Deterministically Textured Sheet Metals - Pfestorf, Markus; Engel, Ulf; Geiger, Manfred (International Journal of Machine Tools and Manufacture, 1998)
LFT Import::2019-07-16 (1615)

3-Rollen-Schubbiegen zur flexiblen Herstellung freiformgebogener Rohrleitungen - Merklein, Marion; Geiger, Manfred; Hagenah, Hinnerk; Cojutti, Massimo (Zukunftstechnologien in Bayern, 2008)
LFT Import::2019-07-29 (257)

5. Internationale Tagung Kaltumformung, Brighton, Großbritannien - Geiger, Manfred (Draht, 1976)
LFT Import::2019-07-15 (334)

5th International Cold Forging Congress, Brighton, Great-Britain - Geiger, Manfred (Wire, 1976)
LFT Import::2019-07-15 (333)

Adapted mechanical properties for improved formability of aluminium blanks by local induction heating - Kerausch, Michael; Merklein, Marion; Geiger, Manfred (Adapted mechanical properties for improved formability of aluminium blanks by local induction heating. Proceedings of the International Body Engineering Conference 2003 in Chiba, Japan, 2003)
In this paper a novel process sequence consisting of local induction heating followed by deep drawing of a precipitation hardenable aluminum alloy is presented and compared with conventional processing. Using an induction heating system, it is possible to change the mechanical properties of the 6xxx-series in a restricted area by influencing the precipitation structure. Hardness measurements and tensile tests characterize the conversion from the stable naturally aged condition T4 to reversible solution heat-treated conditions of AA6016 as function of temperature and time. This effect leads to a reduction of flow stress, which is used to design an initial material property distribution adapted for the subsequent deep drawing process. A process characterization study provides detailed information concerning induction heating parameters, to improve the deep drawing of cylindrical cups, which results in a decisive increase of the limiting drawing ratio. Accompanying the experimental investigations, a finite element analysis approach is realized as a process design and optimization tool. Copyright © 2003 SAE International.
LFT Import::2019-08-05 (997)

Adaptive Beam Delivery for CO2 Laser Material Processing - Geiger, Manfred; Neubauer, Norbert; Hoffmann, Peter; Hutfless, Joachim (Laser Processing: Surface Treatment and Film Deposition, Proceedings of the NATO ASI, 1994)
LFT Import::2019-08-05 (601)

Adaptive Design of Aluminium Sheets for Deep Drawing Processes - Geiger, Manfred; Merklein, Marion (Production Engineering, 2002)
LFT Import::2019-07-16 (1721)

Adaptive Optik für die prozeßoptminierte Fokussierung in Laserbearbeitungsmaschinen - Schottelius, H.U.; Geiger, Manfred; Hoffmann, P. (Laser/Optoelektronik in der Technik, 2001)
LFT Import::2019-07-15 (907)

Adaptives Streckbiegen von Aluminiumprofilen - Geiger, Manfred; Sprenger, Axel (Blech, Rohre, Profile, 1998)
LFT Import::2019-07-16 (1597)

Advanced Concept for the FE-Simulation of Metal Forming Processes for the Production of Microparts. - Engel, Ulf; Meßner, Arthur; Geiger, Manfred (Advanced Technology of Plasticity 1996, Proc. Of the 5th ICTP, 1996)
LFT Import::2019-08-05 (587)

Advanced Numerical Modelling of Patchwork Blank Forming Processes - Lamprecht, Klaus; Geiger, Manfred (Proceedings of the 8th International Conference on Technology of Plasticity (ICTP), 09.-13.10., Verona, Italy, 2005)
LFT Import::2019-08-05 (1136)

Advanced process strategies for the hydroforming of complex structures - Geiger, Manfred; Celeghini, Martino; Novotny, Stefan (XIV Workshop on Supervising and Diagnostics of Machining Systems, 10-12 March 2003, 2003)
LFT Import::2019-08-05 (935)

Advanced rapid prototyping by Laser beam sintering of metal prototypes: design and development of an optimized laser Beam delivery system. - Geiger, Manfred; Coremans, Arjan; Neubauer, Norbert; Niebling, Frank (Proc. Of the Europto Series - Rapid Prototyping (1996), Frankreich : Besancon, 1996)
LFT Import::2019-08-05 (639)

A dynamic simulation scheme using Fuzzy Set Theory for the prediction of the efficiency of innovative manufacturing techniques - Menzel, Thomas; Geiger, Manfred (Proceedings of the CIRP International Seminar on Intelligent Computation in Manufacturing Engineering, 1998)
LFT Import::2019-08-05 (1610)

A Feature Based Approach for Simultaneous Engineering of Sheet Metal Components - Greska, Wolfgang; Hoffmann, Peter; Geiger, Manfred (Transactions of the North American Manufacturing Research Institution, 1993)
LFT Import::2019-08-05 (417)

Algorithms for Irradiation Planning in Medical Laser Applications - Klämpfl, F.; Schmidt, Michael; Hagenah, Hinnerk; Geiger, Manfred (Proceedings of the 5th CIRP International Seminar on Intelligent Computation in Manufacturing Engineering, 2006)
LFT Import::2019-08-05 (265)

Algorithms for Planning and Control of Laser Forming - Hagenah, Hinnerk; Plettke, Raoul; Geiger, Manfred (Proceedings of the IWOTE 08, 2008)
LFT Import::2019-08-05 (144)

Aluminium Tailored Heat Treated Blanks - Geiger, Manfred; Merklein, Marion; Vogt, Uwe (Annals of the German Academic Society for Production Engineering WGP, 2009)
LFT Import::2019-08-05 (1567)

Aluminum tailored heat treated blanks - Geiger, Manfred; Merklein, Marion; Vogt, Uwe (Production Engineering, 2009)
Tailored Heat Treated Blanks (THTB) are blanks, which exhibit locally different material properties optimized for the succeeding sheet metal forming process. The distribution of the material properties is obtained by a local, short-term heat treatment. As a result of the optimized property gradients in the sheet metal's plain, THTB allow enhancing the forming limits significantly. The research work covered in this paper focuses on THTB made out of aluminum alloys. The article presents the microstructural mechanisms due to a short-term heat treatment as well as design principles for the heat treatment layout for THTB made out of AlMgSi alloys and ultra-fine grained (UFG) aluminum alloys produced by the Accumulative Roll Bonding process.
EAM Import::2019-03-13

Analyse und Klassifizierung von Blechteilen - Geiger, Manfred; Greska, Wolfgang (Technica, 1993)
LFT Import::2019-07-15 (395)

Analysing the DMLS-Process by a Macroscopic FE-Model - Niebling, Frank; Otto, Andreas; Geiger, Manfred (Solid Freedom Fabrication Symposium, 2002)
LFT Import::2019-08-05 (1703)

Analysis and Classification of Sheet Metal Components - Geiger, Manfred; Greska, Wolfgang (Production Engineering, 1993)
LFT Import::2019-07-15 (396)

Analysis of the dynamics of transition from deep to shallow penetration CO2 laser welding - Govekar, E.; Gradisek, J.; Grabec, I.; Geisel, M.; Otto, Andreas; Geiger, Manfred (Proceedings of the 6th Experimental Chaos Conference, Potsdam, 2001)
LFT Import::2019-08-05 (868)

Analytical studies on laser cut surfaces - Biermann, Stefan; Nuss, Rudolf; Geiger, Manfred (Proceedings of the 7th International GCL-Symposium, Vienna, Austria, 1988)
LFT Import::2019-08-05 (266)

Analytisches Modell für das Laserstrahlbiegen von Profilen - Geiger, Manfred; Kraus, Jürgen; Pohl, Thomas; Hoffmann, Peter; Vollertsen, Frank (Laser-Magazin, 1994)
LFT Import::2019-07-15 (595)

An Architecture for Multivariate laser Process Control - Geiger, Manfred; Hohenstein, Ralph (Production Engineering. Annals of the German Academic Society for Production Engineering, 2005)
LFT Import::2019-08-05 (1234)

A new method for investigating the relation between real contact and friction in bulk metal forming - Stancu-Niederkorn, S.; Engel, Ulf; Geiger, Manfred (Wire, 1993)
LFT Import::2019-07-15 (447)

An Experimental Analysis of the Onset of Buckling in Sheet Metal Forming - Sobis, Tomasz; Engel, Ulf; Geiger, Manfred (International Journal of Materials & Product Technology, 1992)
In this study a test method is presented in which buckling phenomena can be investigated at a fundamental level. A rectangular sheet sample is fixed in a specially designed mounting device which transfers tensile forces in the longitudinal direction as well as compressive forces in the perpendicular direction. The mechanical principle used ensures a steady ratio of the corresponding strains. Onset and growth of the wrinkle can be monitored by special measuring equipment. The aim of the experimental and theoretical investigations described in this paper was to check the operational characteristics and capabilities of the equipment and to deduce a reproducible criterion for the formation of wrinkles.
LFT Import::2019-07-15 (487)

An Experimental Study of the Onset of Buckling in Sheet Metal Forming - Geiger, Manfred; Engel, Ulf; Otto, Andreas (Int. J. Mater Product Technol. Nr. 7/3, 1991)
LFT Import::2019-08-05 (354)

An inverse approach to the numerical design of the process sequence of tailored heat treated blanks - Geiger, Manfred; Merklein, Marion; Staud, Detlev; Kaupper, Markus (Production Engineering, 2008)
While in industries lightweight construction gain an increasingly significant role and as weight reduction is often done with aluminum sheets, advanced production technologies have to be developed to be competitive for this evolution. Since steel sheet metal parts cannot be substituted directly with aluminum due to its minor formability, the usage of so called tailored heat treated blanks (THTB) is presented in this work. THTB are locally heat treated aluminum blanks from the 6,000-series alloy which exhibit a specific strength pattern optimized to the forming operation leading to a significantly improved formability for the manufacturing of complex aluminum car body parts. The enhancement of the formability is reached by a local heat treatment before the forming process. Due to the strong interdependency of heat treatment and forming operation, a numerical investigation of the process sequence is a prerequisite for a cost-effective usage of the THTB. An inverse approach on basis of a finite element simulation enables the determination of process parameters for an optimized THTB, thus having an effective and efficient engineering method for this technology. © German Academic Society for Production Engineering (WGP) 2007.
LFT Import::2019-07-29 (204)
Keywords: Aluminum; Production process; Simulation

Anlagen- und Prozeßdiagnostik an Bearbeitungssystemen mit Nd:YAG-Lasern - Geiger, Manfred; Gropp, Armin (Trennen mit Festkörperlasern, 1993)
LFT Import::2019-07-15 (397)

A Novel Approach for In-Situ Observation of Local Deformation Behaviour at Micro Scale - Geißdörfer, Stefan; Engel, Ulf; Geiger, Manfred (Proceedings of the 9th International Conference on Technology of Plasticity, 2008)
Microforming processes are characterized by a significant influence of the microstructure on the deformation behaviour. While effects which are influencing the integral deformation behaviour like the influence of the free surface on the material properties are meanwhile identified and welldescribed, the local deformation behaviour of grains which has a significant impact on the final shape evolution is still not understood. In dependency of the grain size as well as the grain orientation, local deformation behaviour is yielding to differences in die filling and in shape evolution. Within this paper, a methodology is discussed to determine and analyze the local deformation behaviour by in-situ optical measurements of stress-strain state within the deformation area. Based on first investigations, a cold forging tool system has been developed in order to measure the local deformation within the specimen using can-backward extrusion process. The process layout is reduced to the deformation of a half cylinder where the die is closed by a sapphire window. Through this translucent tool the deformation process can be observed in-situ by a CCD-camera with a resolution of about two microns. The local deformation information of the captured images can be used for the calculation of the strain distribution. Based on this improved understanding of local deformation behaviour, previously described simulation models can be enhanced and finally verified.
LFT Import::2019-08-05 (1533)

Applicability of a magnetorheological fluid to the flow influenced hydroforming process - Dal Bò, Paolo; Geiger, Manfred (Proceedings of the 9th ESAFORM Conference on Material Forming, 2006)
LFT Import::2019-08-05 (1348)

Application of genetic algorithms for the optimisation of actuator systems for laser micro adjustment. - Plettke, Raoul; Hagenah, Hinnerk; Geiger, Manfred (International Journal of Microstructure and Materials Properties, 2009)
LFT Import::2019-07-29 (135)

Application of genetic algorithms for the optimization of actuator systems for laser micro adjustment - Plettke, Raoul; Hagenah, Hinnerk; Geiger, Manfred (Proceedings of the 6th International Conference on Industrial Tools and Material Processing Technologies 2007 (ICIT&MPT 2007), 2007)
LFT Import::2019-08-05 (143)

Applications of Diffractive Optical Elements for High Power Lasers - Hutfless, Joachim; Geiger, Manfred; Lang, A.; Frank, M.; et al. (Proceedings of SPIE, 1994)
Diffractive optical elements for high-power lasers offer interesting applications in addition to conventional refractive and reflective optics like lenses and mirrors. Their function is based on diffraction at small surface structures in the scale of the wavelength. This paper tries to assess realistically the application potential of diffractive optical elements for industrial high-power lasers. These are excimer lasers (λ = 193 ... 308 nm), Nd:YAG solid-state lasers (λ = 1.06 μm) and CO2 lasers (λ = 10.6 μm). After a short description of both the physical fundamentals of diffractive optical elements and their production processes this paper mainly deals with new methods of beam forming and guiding by diffractive optical elements as well as the integration of these optics into laser systems. Hereby the problems arising from high-power densities as well as the possibility of increasing the efficiency of the beam guiding system are stressed.
LFT Import::2019-07-15 (618)

A Product Model for Sheet Metal Parts and its Applications - Geißler, U; Hoffmann, M; Geiger, Manfred (Journal of Manufacturing Systems, 1991)
LFT Import::2019-07-15 (251)

A Theoretical Study on Wear Simulation in Metal Forming Processes - Sobis, Tomasz; Engel, Ulf; Geiger, Manfred (Journal of Materials Processing Technology, 1992)
One of the main reasons of tool failure in industrial application of metal forming technologies is wear. Typical for this kind of failure is that it affects not only the costs of the process but also the tolerances of the formed parts. The only way to control these features is to develop methods which allow prediction of wear and which are suited to be used in the design stage in order to optimize the process. Starting with a survey of prediction methods, a new concept for the simulation of wear is presented in this paper. © 1992.
LFT Import::2019-07-15 (486)

Aufweittiefziehen kurzer rohrförmiger Werkstücke - Geiger, Manfred; Raghuathi, P.S. (Industrieanzeiger, 1977)
LFT Import::2019-07-15 (338)

Auslegung von Fließpreßwerkzeugen - Geiger, Manfred; Wissmeier, H.J (1985)
LFT Import::2019-08-05 (182)

Ausstrahlung des Bayerischen Forschungsverbundes Lasertechnik auf den Wirtschaftsstandort Bayern. - Geiger, Manfred; Hoffmann, Peter; Schultz, Markus (Präzisionslaserstrahlfertigungstechnik für den Maschinenbau. Abschlußbericht zum Bayerischen Forschungsverbund Lasertechnik FORLAS, 1996)
LFT Import::2019-08-05 (646)

Automated Brazing of Sheet Metal Parts with Nd:YAG-Laser and 6-Axis-Robot - Hanebuth, Henning; Geiger, Manfred (Proc. of the 5th European Conference on Laser Treatment of Materials ECLAT 94, 1994)
LFT Import::2019-08-05 (610)

Automated Construction Methods for Press Brake Tools - Franke, Volker; Backes, Frank; Geiger, Manfred (Sheet Metal 1996: Proc. of the 4th Int. Conf. on Sheet Metal, 1996)
LFT Import::2019-08-05 (588)

Automated Laser Beam Brazing for the Automobile Body Construction. - Hanebuth, Henning; Hoffmann, Peter; Geiger, Manfred (CIRP-Proceedings - Manufacturing Systems, 1995)
LFT Import::2019-08-05 (561)

Automated Metal Foil LOM - A Novel Technology for Rapid Tooling - Prechtl, Martin; Otto, Andreas; Geiger, Manfred (LIM 2005, Proceedings of the 3rd International WLT-Conference on Lasers in Manufacturing, Munich, 2005)
LFT Import::2019-08-05 (1137)

Automated online planning of localized laser process parameters using simulated annealing - Geiger, Manfred; Klämpfl, Florian; Hagenah, Hinnerk (Production Engineering, 2008)
Today, the planning of the irradiation for most laser applications is carried out by determining global irradiation process parameters like spot size, traverse speed, hatch pattern and laser power. Locally changing properties of the irradiation area are not taken into account. The determination of the process parameters is done offline by simulation and experiments. However, there are situations where this is not feasible, the laser process must be planned in more detail. In this paper, the core algorithms used for a localized planning of the irradiation process will be presented. This planning is carried out using a heuristic optimization algorithm, so-called simulated annealing. Besides the description of the used algorithms and an overview of the surrounding algorithms and system technology of a sample application, results which demonstrate that the algorithms work well will be shown. © German Academic Society for Production Engineering (WGP) 2007.
LFT Import::2019-07-29 (261)
Keywords: Computer aided engineering; Laser process planning; Optimization

Automatische Arbeitsplanung für Blechbiegeteile - Geiger, Manfred; Backes, Frank; Franke, Volker; Greska, Wolfgang (Technica, 1994)
LFT Import::2019-07-15 (462)

Basic investigations on boundary lubrication in metla forming processes by in situ observation of the real contact area - Weidel, Stephan; Engel, Ulf; Merklein, Marion; Geiger, Manfred (Production Engineering, 2009)
LFT Import::2019-07-29 (1576)

Basic investigations on hot sheet metal forming of quenchable high strength steels - Geiger, Manfred; Merklein, Marion; Lechler, Jürgen; Bach, F.W.; Springer, R.; Kleiner, M.; Tekkaya, A.E.; Homberg, W.; Brosius, A.; Karbasian, H.; et al. (2nd International Conference on New Forming Technology, 2007)
LFT Import::2019-08-05 (1460)

Basic investigations on the hot stamping steel 22MnB5 - Geiger, Manfred; Merklein, Marion; Hoff, Cornelia (Sheet Metal 2005, Proceedings of the 11th International Conference on Sheet Metal, 2005)
Basic research concerning the material properties of the hot stamping steel 22MnB5 has been carried out. A survey is given about the as-delivered conditions with hardness tests, micrographs and flow curves. The process window of the austenitization time, before hot stamping can take place, is defined by austenitization tests. Also a new experimental set-up to detect the cooling rate in dependency on the contact pressure is presented. In addition to that the cooling experiments were simulated with ABAQUS and the heat transfer coefficient for each contact pressure is determined by inverse modeling.
LFT Import::2019-08-05 (1130)
Keywords: Heat treatment; Hot stamping; Sheet metal

Basic research on cold forging of microparts - Tiesler, Nicolas; Engel, Ulf; Geiger, Manfred (Advanced Technology of Plasticity, Proceedings of the 7th ICTP, 2002)
LFT Import::2019-08-05 (1686)

Beanspruchungsgerechte Oberflächenstrukturierung hartstoffbeschichteter Werkzeuge der Kaltmassivumformung - Geiger, Manfred; Engel, Ulf; Popp, Uwe (Bayerischer Forschungsverbund für Oberflächentechnik, 2000)
LFT Import::2019-07-15 (763)

Beanspruchungsgerechte Oberflächenstrukturierung hartstoffbeschichteter Werkzeuge der Kaltmassivumformung - Geiger, Manfred; Engel, Ulf; Popp, Uwe (Bayerischer Forschungsverbund für Oberflächentechnik, 2001)
LFT Import::2019-07-15 (862)

Bearbeitung von Blechteilen mit CO2-Hochleistungslasern - Geiger, Manfred; Hoffmann, Peter; Biermann, Stefan; Nuss, Rudolf (Laser/Optoelektronik in der Technik, 1989)
LFT Import::2019-07-15 (433)

Behaviour of a High Viscous Fluid and its Effect on the Flow Influenced Hydroformnig Process - Dal Bò, Paolo; Geiger, Manfred (Tagungsband der Femlab Konferenz: Neue Wege der Multiphysik-Simulation, 2006)
LFT Import::2019-08-05 (1346)

Beispiele zur Anwendung der elementaren Plastizitätstheorie - Geiger, Manfred; Geiger, R (Industrieanzeiger, 1973)
LFT Import::2019-07-12 (157)

Bend Better with Lasers - Vollertsen, Frank; Geiger, Manfred (Forming & Fabrication, 1995)
LFT Import::2019-07-15 (577)

Berechnung des elastischen Verhaltens einer Kurbelpresse mit der Methode der finiten Elemente - Geiger, Manfred (Industrieanzeiger, 1975)
LFT Import::2019-07-12 (165)

Berechnung des Spannungs- und Formänderungszustandes beim Voll-Vorwärts-Fließpressen eines starrplastischen Werkstoffes - Geiger, Manfred (Industrieanzeiger, 1971)
LFT Import::2019-07-12 (153)

Berechnung von Bauteilen von Umformmaschinengestellen nach der Matrizenverschiebungsmethode - Geiger, Manfred; Rüdt, W (Industrieanzeiger, 1972)
LFT Import::2019-07-12 (156)

Beschreibung des mechanischen Werkstoffverhaltens beim Warumumformen höchstfester Vergütungsstähle - Geiger, Manfred; Merklein, Marion; Lechler, Jürgen (1. Erlanger Workshop Warmblechumformung, Tagungsband zum Berichts- und Industriekolloquium der FOR552, Erlangen, 7. November 2006, 2006)
LFT Import::2019-08-05 (1340)

Bessere Werkstücke durch moderne Umformtechnik - Lange, K.; Geiger, Manfred; Müller, H. (Umschau in Wissenschaft und Technik, 1970)
LFT Import::2019-07-11 (152)

Betriebsbeanspruchung vorgespannter Fließpreßwerkzeuge - Geiger, Manfred; Krämer, G. (Industrieanzeiger, 1976)
LFT Import::2019-07-15 (335)

Beurteilung des Glanzgrades an Blechen durch 3D-Oberflächenanalyse - Geiger, Manfred; Engel, Ulf; Leopold, J.; Krauß, Hans-Joachim; Günther, H.; et al. (Blech, Rohre, Profile, 1999)
LFT Import::2019-07-16 (2008)

Biegen mit Excimerlasern. - Becker, Wolfgang; Geiger, Manfred (Europäischer Laser-Markt, 1996)
LFT Import::2019-07-15 (586)

Biegewerkzeuge aus laserstrahlgeschnittenen Lamellen - Geiger, Manfred; Franke, Volker (Blech, Rohre, Profile, 1995)
LFT Import::2019-07-15 (469)

Blank Optimization for the Sheet Hydroforming of a Frame-Shaped Structure - Tolazzi, M.; Geiger, Manfred (NUMIFORM 2004, Materials Processing and Design. Proceedings of the NUMIFORM, 2004)
LFT Import::2019-08-05 (1050)

Blechbearbeitung an der Schwelle zum 21. Jahrhundert - einige Visionen aus jüngster Forschung. - Geiger, Manfred; Hoffmann, Peter; Vollertsen, Frank; Müller, Burkhard (20 Jahre Umformtechnik in Darmstadt (1996), 1996)
LFT Import::2019-08-05 (648)

Blechbearbeitung durch Laserstrahlschneiden - Beeinflussung der Werkstoffeigenschaften durch den Schneidvorgang - Geiger, Manfred; Bergmann, H.W.; Nuss, Rudolf (Blech, Rohre, Profile, 1988)
LFT Import::2019-07-15 (274)

Bruchkriterien für die Auslegung von Hartmetall-Fließpressen - Geiger, Manfred; Engel, Ulf; Wissmeier, Hans-Jürgen (Neuere Entwicklungen in der Massivumformung, 1989)
LFT Import::2019-08-05 (443)

Bruchkriterien für die Auslegung von Hartmetall-Fließpreßmatrizen - Wissmeier, Hans-Jürgen; Engel, Ulf; Geiger, Manfred (Draht, 1990)
LFT Import::2019-07-15 (741)

Bruchmechanische Untersuchungen an Fließpressmatrizen - Geiger, Manfred; Hänsel, M (Umformtechnik, 1991)
LFT Import::2019-07-15 (240)

Ceramic Adapted Tool Design in Cold Forging - Consideration of Thermal Effects on Prestressing System - Arbak, Murat; Engel, Ulf; Geiger, Manfred (4th International Conference and Exhibition on Design and Production of Machines and Dies/Molds, 2007)
LFT Import::2019-08-05 (1462)

Characterisation of ceramic coatings generated by laser pyroloysis of SiCN-polymers - Krauß, H.J.; Geiger, Manfred; Otto, Andreas; Motz, G. (Proceedings of THE coatings, 2005)
LFT Import::2019-08-05 (1193)

Characterisation of the flow properties of the quenchable ultra high strength steel 22MnB5 - Merklein, Marion; Lechler, Jürgen; Geiger, Manfred (Annals of the CIRP, 2006)
LFT Import::2019-08-05 (1268)

Characterisation of the Forming Behaviour of Patwork Blanks - Lamprecht, Klaus; Geiger, Manfred (Steel Research International, 2005)
LFT Import::2019-07-16 (1134)

Characterisation of Yielding BEhvior of Sheet Metal under Biaxial Stress Condition at Elevated Temperatures - Merklein, Marion; Hußnätter, Wolfgang; Geiger, Manfred (Annals of the CIRP, 2008)
LFT Import::2019-08-05 (1512)

Characterization of Yielding Magnesium Alloy AZ31 with BBC2005 - Hußnätter, Wolfgang; Banabic, D.; Merklein, Marion; Geiger, Manfred (Proceedings of ICTP2008, 2008)
The finite element analysis (FEA) is getting more and more important in fields of sheet metal forming for process design and parts' dimensioning. But the reliability and the quality of the numerical results strongly depend on the model that has to be built for the calculations. Especially the modelling of the elastic-plastic material behaviour is of main importance, since it shows a wide impact on the numerically calculated stresses and strains in sheet metal parts. Therefore, the material data have to be determined using experiments and have to be modelled basing on the experimental results. Most of semi-finished products are characterized by anisotropic material properties which can be approximated by yield criteria like those of Hill'48 for common steels or Barlat'89 and various BBC-models for some aluminium alloys. The diversity of new materials, in particular light weight materials like magnesium sheet metals may cause the necessity of new yield criteria, but in some cases the material behaviour can also be modelled by existing ones. In this paper the material behaviour of the magnesium alloy AZ31 under plane tensile stress conditions is investigated. The experimental investigations have been done at the Chair of Manufacturing Technology (LFT) of the University of Erlangen using a novel experimental setup. The yielding behaviour is determined basing exclusively on real material data out of experiments so that no FE-calculations are necessary to detect strains and stresses. Using these data different yield criteria are applied to model the real material characteristics, whereas the criterion of BBC2005 gives to the best approximation for uniaxial yield stresses, the anisotropy coefficients and also the yield locus diagram.
LFT Import::2019-08-05 (1514)

Characterization of yielding of sheet metal at elevated temperatures - Hußnätter, Wolfgang; Merklein, Marion; Geiger, Manfred (Journal of Materials Processing Technology, 2007)
In times of highest significance of process modeling and numerical simulation characterization of material properties is of special importance for components' and tools' dimensioning. Especially in fields of sheet metal forming the mechanical behavior of components highly differ according to real stress condition. In particular yield loci combine the information of beginning of yielding with biaxial stress conditions. Although these data are essential, they are unknown for many different sheet metals, mainly new materials used for light-weight constructions, e.g. aluminum and magnesium alloys. In this paper investigations done on a novel concept of experimental setup, which has been developed at the Chair of Manufacturing Technology (LFT) and which enables the determination of yield loci at elevated temperatures, are presented. The strategy for local heating is based on FE-calculations and verified afterwards. A 210 W-diode laser is used for the local heating of the specimens up to temperatures in the range of 300 °C. During forming process a constant temperature is guaranteed by a closed-loop temperature-control (CLTC), the homogeneous distribution of temperature in the forming zone is realized using a special optical system. © 2007 Elsevier B.V. All rights reserved.
LFT Import::2019-07-16 (1381)
Keywords: Diode laser; FE-simulation; Materials' characterization; Yield locus

Charakterisierung der Fließeigenschaften von Aluminium- und Magnesiumblechwerkstoffen - Geiger, Manfred; Merklein, Marion; Hußnätter, Wolfgang (Tagungsband 12. Sächsische Fachtagung Umformtechnik (SFU) - Leichtbau durch Umformtechnik, 2005)
LFT Import::2019-08-05 (1192)

Charakterisierung einer magnetorheologischen Flüssigkeit für die Innenhochdruck-Umformung von Rohren - Dal Bò, Paolo; Blankl, Andreas; Geiger, Manfred (Tagungsband der Femlab Konferenz: Neue Wege der Multiphysik-Simulation, 2005)
LFT Import::2019-08-05 (1248)

Charakterisierung und Modellierung des Fließverhaltens höchstfester Vergütungsstähle bei erhöhten Temperaturen - Merklein, Marion; Lechler, Jürgen; Geiger, Manfred (Umformtechnik im Spannungsfeld zwischen Plastomechanik und Werkstofftechnik, 2008)
LFT Import::2019-07-29 (1560)

Classification Problems in Manufacturing of Sheet Metal Parts - Geiger, Manfred; Greska, Wolfgang; Franke, Volker (Reprints of the 2nd International Workshop on Learning in Intelligent Manufacturing Systems, 1995)
LFT Import::2019-08-05 (542)

Closed Loop Control Approach in Finite Element Simulation for Efficient Process Design of Sheet Metal Hydroforming - Geiger, Manfred; Kohlbauer, R. (Production Engineering. Annals of the German Academic Society for Production Engineering, 2004)
LFT Import::2019-08-05 (1032)

Closed-Loop-Control of the Focus-Parameters of rf-Excited CO2 High Power Lasers. - Kauf, Michael; Schuberth, Stefan; Hutfless, Joachim; Geiger, Manfred (Tagungsband zu Mechanik und Optik - Hochleistungslaser im Maschinenbau, 1995)
LFT Import::2019-08-05 (571)

CO2-Laser Cutting Fiber Reinforced Plastics - Müller, Roland; Nuss, Rudolf; Geiger, Manfred (Tagungsband Congress on Optical Science and Engineering (ECO2): High Power Lasers and Laser Machining Technology, 1989)
LFT Import::2019-08-05 (437)

Combination of laser beam cutting and welding for car body manufacturing: welding with wire as filler - Geiger, Manfred; Hoffmann, Peter; Deinzer, Günter (Proceedings of the 3rd European Conference on Laser Treatment of Materials (ECLAT), Erlangen, 1990)
LFT Import::2019-08-05 (731)

Combined tube and double sheet hydroforming for the manufacturing of complex parts - Merklein, Marion; Geiger, Manfred; Celeghini, Martino (Annals of the CIRP 2005, 2005)
LFT Import::2019-08-05 (1222)
Keywords: Hydroforming; Sheet metal; Tube

Comparative study of two different laser forming mechanisms regarding the mechanical properties of aluminium alloys - Merklein, Marion; Geiger, Manfred (Laser Assisted Net shape Engineering (LANE), 2001)
LFT Import::2019-07-15 (872)

Computer-aided Design of Press Frames - Geiger, Manfred (Proceedings of the International Conference on Production Engineering, 1974)
LFT Import::2019-08-05 (162)

Computer-Aided Generation of Bending Sequences for Die-Bending Machines - Hoffmann, Martin; Geißler, Uwe; Geiger, Manfred (Journal of Materials Processing Technology, Nr. 30, 1992)
The planning of bending sequences and the assigning of tools is a task that has to be done manually at the present time. As part of a computerized process-planning tool for sheet-metal parts, a bending-sequence generator has been developed. The bent part can be developed into the plane part automatically, technological data and know-how about the bending process and the press brake being included in this tool. The bending sequence generated by the computer can be simulated and altered ad libitum on a graphics screen. © 1992.
LFT Import::2019-08-05 (482)

Computer assisted design of actuators for high precision adjustment in micro technology - Hagenah, Hinnerk; Wurm, Thomas; Geiger, Manfred (Advances in Integrated Design and Manufacturing in Mechanical Engineering, 2005)
LFT Import::2019-08-05 (276)

Computer assisted design of actuator systems for laser micro adjustment - Plettke, Raoul; Hagenah, Hinnerk; Geiger, Manfred (Key Engineering Materials, 2007)
The adjustment of micro system components with laser forming using especially designed sheet metal actuator systems is a new and promising technology. However, due to the complexity of the design challenge and the contradicting targets that have to be considered computer assistance for the design of the actuator systems is needed. In order to build such a system several steps have to be taken. First, the actuators have to be modeled with all necessary data. Second, quality criteria have to be defined and fully automated assessment modules for every single objective have to be implemented. And third, an optimization system which utilizes the assessment modules must be developed to improve an initial design. This paper presents a solution for each of these steps. It closes with first results of a reduced version of the system as well as an outlook on the next development steps.
LFT Import::2019-07-11 (141)
Keywords: Actuator design; Evolutionary algorithm; Laser micro adjustment; Multi-criteria optimization

Computer assisted design of complex actuator systems for laser micro adjustment - Geiger, Manfred; Otto, Andreas; Schmidt, Michael (Proceedings of the LANE 2007, 2007)
LFT Import::2019-08-05 (142)

Computer assisted, knowledge based process design for sheet metal hydroforming using finite element simulation - Geiger, Manfred; Hagenah, Hinnerk; Kohlbauer, Rainer (Enterprises, production networks, 2004)
LFT Import::2019-08-05 (1034)

Concept for a closed loop control system for laser bending of extrusions - Menzel, Thomas; Geiger, Manfred; Brandt, Volker; Otto, Andreas (CIRP Journal of Manufacturing Systems, 2000)
LFT Import::2019-07-15 (789)

Concurrent Manufacturing of Parts and Tools for Sheet Metal Industry - Backes, Frank; Franke, Volker; Geiger, Manfred (The Second World Congress on Intelligent Manufacturing Processes & Systems IMP & S, Budapest, Ungarn, 10.06-13.06.1997, 1997)
LFT Import::2019-08-05 (691)

Contact Mask Technique for Laser Structuring of 3-D MID - Roth, Stephan; Dietel, C.; Eßer, Gerd; Geiger, Manfred (Proceedings of the IEMT Europe Symposium, Electronics Manufacturing and Development for Automotives, 1998)
Molded Interconnect Devices (MID) are promising polymer parts for many industrial applications to make possible complex functional components containing circuits, and to avoid costs in material and production. Already existing examples in the automotive field are a car dash board and a rear stop light. For suitable large scale production technologies for complex three-dimensional MID, development of new manufacturing processes is essential. Different technologies are used to generate circuit patterns on the substrate by photoimaging. The geometrical information can be transformed by using different mask technologies. Besides the common mask projection technique, a contact mask which contains the circuit geometry is also suitable. Therefore the circuits are generated in original scale by IR laser radiation on a polyvinyl chloride (PVC) sheet. The blackened polymer is non-transparent for UV radiation of common UV lamps and especially excimer lasers, used for imaging of photosensitive resists. For three-dimensional masks the sheet is formed by a deep drawing process.
LFT Import::2019-08-05 (1618)

Contour generation and surface Quality of parts manufactured by automated Metal Foil LOM - Technology - Seidel, S.; Otto, Andreas; Geiger, Manfred (Proceedings of the LANE 2007, 2007)
LFT Import::2019-08-05 (1454)

Controlled Section Bending by Using a Neural Network - Arnet, Horst; Geiger, Manfred (Proceedings of the 29th CIRP International Seminar on Manufacturing Systems, Osaka, Japan, 11.05.-13.05.1997, 1997)
LFT Import::2019-08-05 (685)

Cost estimation for large scale production of sheet metal parts using artificial neural networks - Geiger, Manfred; Knoblach, Jürgen; Backes, Frank (Production Engineering, 1998)
LFT Import::2019-07-16 (1150)

Coupling of analytical and numerical models for laser adjustment - Geiger, Manfred; Müller, Burkhard (Lasers in Engineering, 1998)
Miniaturisation in mass production requires more and more accuracy. Economic production of the demanded tolerances cannot be achieved with the available joining technology. The only possibility is laser beam adjustment of the already joined structural component. Modelling the behaviour of complex three-dimensional structures during laser adjustment becomes more and more necessary for building up a closed loop system which is designed to reach the accuracy of less than 0.1 μm. The model which is presented in this paper can be characterised by the fact that the plastic strain field after the laser irradiation is analytically calculated and included into a FEM program. The analytical solution includes the solution of the one-dimensional transient temperature field by pulsed irradiation assuming pulse durations in the range of nanoseconds. Based on this transient temperature field, a local maximum temperature is calculated. This non-time-dependent function is the basis of the calculation of the plastic deformation. Both elastic deformation and restraining is taken into account. The so-calculated plastic deformation is a residual stress source. For simple geometries like stripes, this plastic strain is used for calculating the bending angle by integrating over all three directions. On the other hand it is linearised and builds the input for the FE calculation. This method makes a fast calculation of the three-dimensional forming of complex geometries in short calculation times possible.
LFT Import::2019-07-16 (1592)
Keywords: Analytical model; Excimerlaser beam adjustment; FEM; Laser beam adjustment; Laser forming; Modelling

Crash behviour of various modern steels exposed to high deformation - Laumann, T.; Pfestorf, Markus; Beil, A.; Geiger, Manfred; Merklein, Marion (Key Engineering Materials, 2007)
LFT Import::2019-07-16 (1466)

Critéres de rupture applicables á la conception des matrices de frappe en métal dur - Wißmeier, H.-J; Engel, U; Geiger, Manfred (Le tréfilé, 1991)
LFT Import::2019-07-15 (355)

Criteri di rottura per la progettazione di matrici in metallo duro per 10 stampaggio a freddo - Wißmeier, H.-J; Engel, U; Geiger, Manfred (Il filo metallico, 1991)
LFT Import::2019-07-15 (356)

Criterios de rotura para el dimensionado de matrices de extrusión de metal duro - Wißmeier, H.-J; Engel, U; Geiger, Manfred (Alambre, 1991)
LFT Import::2019-07-15 (357)

Cross Transport in a Multi-Station Former for Microparts - Geiger, Manfred; Egerer, Emil; Engel, Ulf (Production Engineering, 2002)
LFT Import::2019-07-16 (1664)

Das Institut für Umformtechnik der Universität Stuttgart - Lange, K.; Geiger, Manfred (Werkstattstechnik, 1970)
LFT Import::2019-07-12 (151)

Das Verbundprojekt -3D-Bearbeiten mit CO2-Hochleistungslasern- im Überblick - Geiger, Manfred; Hoffmann, Peter (3D-Bearbeiten mit CO2-Hochleistungslasern, 1992)
LFT Import::2019-07-15 (472)

Data Flow for the Development of Laser Manufactured Products - Geiger, Manfred; Kach, Andreas (35th CIRP-International Seminar on Manufacturing Systems ISMS, 2002)
LFT Import::2019-08-05 (1675)

Datenorganisation in einem wissenbasierten System zur Biegestadienplanung - Geiger, Manfred; Hoffmann, Martin (CIM-Management, 1990)
LFT Import::2019-07-15 (729)

Deep Drawing of Friction Stir Welded Aluminium Tailored Blanks - Geiger, Manfred; Merklein, Marion; Giera, Artur (Proceedings of IDDRG, 24.-26.05., 2001)
LFT Import::2019-08-05 (1064)

Deep drawing of friction stir welded thin sheet aluminium-steel tailored hybrids - Merklein, Marion; Giera, Artur; Geiger, Manfred (Steel Research International, 2005)
LFT Import::2019-07-16 (1223)
Keywords: Aluminium steel tailored hybrids; Deep drawing; Forming behaviour; Friction stir welding

Der Einsatz des Festkörperlasers zum Laserstrahl-Mikroschweißen in der Elektronikfertigung - Geiger, Manfred; Glasmacher, Matthias; Pucher, Hans-Jörg; Hutfless, Joachim (Laser, 1994)
LFT Import::2019-07-15 (589)

Der Einsatz von digitalen Rechenanlagen bei der Auslegung von Pressengestellen - Geiger, Manfred (Werkzeugmaschine international, 1974)
LFT Import::2019-07-12 (163)

Der SFB 396 im Überblick- Beiträge zum Berichts- und Industriekolloquium - Geiger, Manfred; Hagenah, Hinnerk (Robuste, verkürzte Prozessketten für flächige Leichtbauteile: Tagungsband zum Industriekolloquium, 2006)
LFT Import::2019-08-05 (264)

Der Sonderforschungsbereich - Geiger, Manfred; Otto, Andreas; Schöberl, T. (Sonderforschungsbereich 396 - Robuste, verkürzte Prozessketten für flächige Leichtbauteile - 1. Berichtskolloquium 24./25. Mai, 2000)
LFT Import::2019-08-05 (775)

Design of Micro Forming Proces¬ses Fundamentals, Mate¬rial Data and Friction Behaviour. - Geiger, Manfred; Meßner, Arthur; Engel, Ulf; Kals, Roland; Vollertsen, Frank (Chipless 2000 Advancing Chipless Component Manufacture, Proceedings of the 9th International Cold Forging Congress, 1995)
None
LFT Import::2019-08-05 (1971)

Design of Micro-Forming Processes - Fundamentals, Material Data and Friction Behaviour - Geiger, Manfred; Meßner, Arthur; Engel, Ulf; Kals, Roland; Vollertsen, Frank (Proceedings of the 9th International Cold Forging Congress, 1995)
LFT Import::2019-08-05 (550)

Determination of contact stresses in the boundary area considering elastomere-pad bending as example - Geiger, Manfred; Merklein, Marion; Trägler, Horst; Nock, Marco (Production Engineering - Annals of the WGP, 2005)
LFT Import::2019-08-05 (1218)

Determination of Data for the Hot Stamping Process - Geiger, Manfred; Merklein, Marion; Hoff, Cornelia (Production Engineering. Annals of the German Academic Society for Production Engineering, 2006)
LFT Import::2019-08-05 (1344)

Determination of forming limit diagrams? a new analysis method for characterization of materials' formability - Geiger, Manfred; Merklein, Marion (CIRP Annals - Manufacturing Technology, 2003)
LFT Import::2019-07-16 (1007)

Determination of friction coefficients for the finite element analysis of double sheet hydroforming with a modified dup test - Tolazzi, Massimo; Vahl, Meik; Geiger, Manfred (ESAFORM, 2003)
LFT Import::2019-07-15 (950)

Determination of Mechanical Properties for the Hydroforming of Magnesium Sheets at Elevated Temperature - Hecht, Joachim; Pinto, S.; Geiger, Manfred (Sheet Metal 2005, Proceedings of the 11th International Conference on Sheet Metal, 2005)
LFT Import::2019-08-05 (1143)
Keywords: Hydroforming; Magnesium; Sheet metal

Determination of the heat transfer during hot stamping - Geiger, Manfred; Merklein, Marion; Hoff, Cornelia (Steel-Future for the Automotive Industry, 2005)
LFT Import::2019-08-05 (1179)

Determination of thermal and mechanical material properties if ultra high strength steels for hot stamping - Lechler, Jürgen; Merklein, Marion; Geiger, Manfred (Steel Research International, 2008)
Direct and indirect hot stamping presently constitutes one of the most innovative forming technologies in the automotive industry through the combination of forming and hardening in one process step or line. Thus, structural components with strength up to 1600 MPa can be accomplished with the quench hardenable ultra-high strength steel 22MnB5. With respect to the numerical investigation of the feasibility of different parts the knowledge of various thermal and mechanical material characteristics determined under process relevant conditions are required. Within the scope of this paper different experimental methods will be introduced for the determination of material properties according to the typical time-temperature characteristics of the hot stamping process, as well as the modelling of it as input data for the FE analysis.
LFT Import::2019-07-29 (1561)
Keywords: 22MnB5; Flow behaviour; Heat transfer; Hot stamping; Modelling

Determination of tribological conditions within hot stamping - Geiger, Manfred; Merklein, Marion; Lechler, Jürgen (Production Engineering, 2008)
Innovative hot sheet metal forming technologies are gaining an increasing significance in the scope of application of more and more innovative high and ultra high strength steels in the automotive industry. With respect to a numerical process design beside the mechanical and the thermal material characteristics the friction coefficient represents an important input parameter for finite element (FE) simulation. Within the scope of this paper an evaluation method for the determination of the friction coefficient μ for the direct hot stamping process of boron-manganese steels will be presented. Therefore cup deep drawing tests at elevated temperatures following the time-temperature-characteristic of the hot stamping process are carried out. For the calculation of the friction coefficient the approach according to Siebel for the modeling of the maximum drawing force is used. © German Academic Society for Production Engineering (WGP) 2008.
LFT Import::2019-07-29 (1553)
Keywords: Friction coefficient; Hot stamping; Production process

Determination of Yield Loci of Sheet Metal at Elevated Temperatures by the Integration of a Diode Laser Source - Hußnätter, Wolfgang; Merklein, Marion; Geiger, Manfred (Proceedings of AMPT 2006, 2006)
LFT Import::2019-08-05 (1264)

Developing a computer aided design system for actuator design for laser micro adjustment - Plettke, Raoul; Hagenah, Hinnerk; Geiger, Manfred (Proceedings of the 18th CIRP International Design Seminar (March 2008), 2008)
LFT Import::2019-08-05 (145)

Development of a Control Strategy for Laser Beam Melt Ablation Based on Process Modelling - Cser, Adrienn Orsolya; Otto, Andreas; Geiger, Manfred (Proceedings of the 4th CIRP International Seminar on Intelligent Computation in Manufacturing Engineering. ICME' 2004. Sorrento, Italy, 2004)
LFT Import::2019-08-05 (1052)

Development of an irradiation strategy withing a closed loop control system for the laser adjustment of deformation - Hutterer, Angelika; Hagenah, Hinnerk; Geiger, Manfred (Proceedings of the 2003 International Conference on Control, Automation and Systems (ICCAS 2003), 2003)
LFT Import::2019-08-05 (947)

Development of a Process Model for Laser Beam Melt Ablation - Geiger, Manfred; Cser, Adrienn Orsolya; Otto, Andreas (Production Engineering. Annals of the German Academic Society for Production Engineering, 2005)
LFT Import::2019-08-05 (1235)

Development of Software Modules for Flexible Manufacturing System for Sheet Metal Parts - Geiger, Manfred; Geißler, Uwe (16th North American Manufacturing Research Conference Proceedings, University of Illinois, 1988)
LFT Import::2019-08-05 (280)

Diagnostik der Werkstücktemperatur beim thermischen Abtragen mit CO2-Hochleistungslasern - Kauf, Michael; Hartmann, W.; Biermann, Stefan; Geiger, Manfred; Christiansen, J. (DPG, 1990)
LFT Import::2019-08-05 (736)

Die Bedeutung der Gasführung beim Laserstrahlschneiden von kurzglasverstärkten Verbundwerkstoffen - Müller, Roland; Geiger, Manfred (Laser und Optoelektronik, 1990)
LFT Import::2019-08-05 (739)

Die Hochschule als Gesellschafter - Anmerkungen aus der Sicht eines Wissenschaftlers - Geiger, Manfred (Die Hochschule als Gesellschafter, 2001)
LFT Import::2019-08-05 (861)

Diesseits und jenseits der Umformtechnik - Geiger, Manfred; Merklein, Marion; Nock, Marco (Lange währt die Umformtechnik, 2004)
LFT Import::2019-07-16 (1097)

Diplom-, Bachelor- und Masterstudium im Erlanger Maschinenbau - Kreis, Oliver; Geiger, Manfred (Technik in Bayern, 2004)
LFT Import::2019-07-16 (1031)

Double Sheet Hydroforming of Complex Hollow Parts - Celeghini, Martino; Geiger, Manfred (Journal of the Japan Society for Technology of Plasticity, 2003)
LFT Import::2019-07-15 (944)

Dreidimensionale Oberflächenanalyse bei Feinblechen. - Geiger, Manfred; Pfestorf, Markus; Engel, Ulf (Stahl und Eisen, 1995)
LFT Import::2019-07-15 (552)

Dry Film Lubricants in Aluminium Sheet Metal Forming - Geiger, Manfred; Meiler, M.; Pfestorf, Markus; Merklein, Marion (Proceedings of the 3rd International Conference THE Coatings in Manufacturing Engineering, 2002)
LFT Import::2019-08-05 (1720)

Dual beam Nd:YAG laser welding: Influence of lubricants to lap joint welding of steel sheets - Geiger, Manfred; Merklein, Marion; Otto, Andreas; Blankl, Andreas (Proceedings of the XVI. International Symposium on Gas Flow and Chemical Lasers & High Power Laser Conference, Gmunden, Austria, 2006)
LFT Import::2019-08-05 (1313)

Eddy Current Measurement of Mechanical Properties of Sheet Metal - Geiger, Manfred; Schwind, Michael; Engel, Ulf (Production Engineering, 1995)
LFT Import::2019-07-15 (555)

Effects of PVD and CVD Coatings on Fatigue Strength of Tool Steel for Cold Forging - Geiger, Manfred; Engel, Ulf; Hinsel, Christian (Production Engineering, 1998)
LFT Import::2019-07-16 (1586)

Effects of specimen size and geo-metry in metal forming. - Kals, Roland; Pucher, Hans-Jörg; Vollertsen, Frank; Geiger, Manfred (Proc. of the 2nd int. conf. on advances in materials and processing technologies, 1995)
LFT Import::2019-08-05 (569)

Effects of viscous dissipation in flow-inflluenced tube hydroforming - Dal Bò, Paolo; Geiger, Manfred (International Journal of Microstructure and Materials Properties, 2008)
LFT Import::2019-07-29 (1508)

Effects of viscous dissipation in the flow influenced tube hydroforming - Dal Bò, Paolo; Geiger, Manfred (International Journal of Microstructure and Materials Properties, 2006)
LFT Import::2019-07-16 (1345)

Eigenschaften reibrührgeschweißter Aluminium-Stahl-Verbindungen - Geiger, Manfred; Merklein, Marion; Giera, Artur; Staud, Detlev (Berichtskolloquium der DFG-Forschergruppe 505, 2005)
LFT Import::2019-08-05 (1242)

Ein CNC-Blechbearbeitungszentrum für die Serienfertigung - Leibinger, B.; Geiger, Manfred (NC-Praxis, 1978)
LFT Import::2019-07-15 (346)

Einfluß von Strahleigenschaften auf die Bearbeitungsqualität beim Schneiden mit dem Laser - Biermann, Stefan; Nuss, Rudolf; Geiger, Manfred (Maschinenmarkt, 1988)
LFT Import::2019-07-15 (270)

Einführung neuer Produktions- und Schlüsseltechnologien am Beispiel der Laserstrahlbearbeitung. Schnell lernende Unternehmen - Quantensprünge in der Wettbewerbsfähigkeit - Geiger, Manfred; Hutfless, Joachim (Tagungsband Münchner Management Kolloquium, 1995)
LFT Import::2019-08-05 (546)

Einsatz der numerischen Prozeßsimulation in der Werkzeugentwicklung - Falk, Bernd; Engel, Ulf; Geiger, Manfred (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 1999)
LFT Import::2019-07-16 (2004)

Einsatz von Laserstrahlung zur Herstellung tribologich optimierter Oberflächentopographien - Geiger, Manfred; König, Werner; Tönshoff, H.K. (Werkstoffe für die Fertigungstechnik, 1998)
LFT Import::2019-08-05 (1590)

Elastomere-Pad Bending of Tubes for Reaching High Residual Formability - Geiger, Manfred; Nock, Marco (ESAFORM 2004, Proceedings of the 7th ESAFORM Conference, Trondheim, Norway, 2004)
LFT Import::2019-08-05 (1047)

Elementare Plastizitätstheorie - Ansätze nach Siebel u. a. für die Kraftberechnung bei Umformvorgängen - Geiger, Manfred; Geiger, R (Industrieanzeiger, 1973)
LFT Import::2019-07-12 (158)

Enhanced formability of aluminium blanks by local laser heat treatment - Merklein, Marion; Geiger, Manfred; Vogt, Uwe (Proceedings of the 5th LANE Conference, 2007)
LFT Import::2019-08-05 (1471)

Enhanced numerical results on friction stir welded aluminium butt joints - Staud, Detlev; Giera, Artur; Merklein, Marion; Geiger, Manfred (Proceedings of the 12th International Conference on Sheet Metal (SheMet), 2007)
Friction stir welding is a newer technology to join materials in the solid phase. Therefore plenty of problems which appear by melting phase welding technologies for aluminium alloys are avoided by this process. This is the main chance for friction stir welding to be accepted and integrated in forthcoming applications, especially for uses out of aluminium alloys. Starting from former results for friction stir welding of aluminium this article deals with the determination of the constitutive material properties of friction stir welded aluminium tailored blanks with regard to the finite-element (FE) simulation of sheet metal forming. The FE simulation of the formability of welded sheet metal demands the knowledge of the precise mechanical properties of the base material as well as the characteristic zones of the weld seam, which are affected by friction stir welding. While ordinary tensile tests can only determine the constitutive behaviour of a simple tensile specimen, an optical strain measurement can be used to determine flow stresses of the base and of the welded material with an adapted tensile specimen, respectively. By the usage of the so called rule of mixture the advantages of this new approach is demonstrated with a comparison of the tensile forces within FE simulations and experimental validations. For this purpose specimen with the weld seam oriented perpendicular and parallel to the uniaxial loading direction are utilized.
LFT Import::2019-08-05 (1395)
Keywords: Friction stir welding; Mechanical properties; Simulation; Tensile test

Enlargement of deep drawability of aluminium blanks - Merklein, Marion; Kerausch, Michael; Hußnätter, Wolfgang; Geiger, Manfred (Advanced Technology of Plasticity, Proceedings of the 7th ICTP, 2002)
LFT Import::2019-08-05 (1697)

Entwicklung einer Wissenserwerbskomponente für die Biegestadienplanung - Geiger, Manfred; Hoffmann, Peter; Backes, Frank (Werkstattstechnik, 1993)
LFT Import::2019-07-15 (404)

Entwicklung eines Datenmodells für die Fertigungsvorbereitung von Blechbiegeteilen - Geiger, Manfred; Hoffmann, Martin (Blech, Rohre, Profile, 1992)
LFT Import::2019-07-15 (375)

Entwicklungen zum Präzisionslaserschneiden - Geiger, Manfred; Nuss, Rudolf (Neuere Entwicklung in der Blechbearbeitung - Tagungsband zum Seminar, 1988)
LFT Import::2019-08-05 (282)

Entwicklung keramischer Schichten durch Pyrolyse, insbesondere Laserpyrolyse metallorganischer Polymere - Krauß, H.-J.; Geiger, Manfred; Motz, G.; Ziegler, G. (Bayerischer Forschungsverbund für Oberflächentechnik, 2000)
LFT Import::2019-07-15 (786)

Entwicklungstendenzen in der flexiblen Blechbearbeitung - Geiger, Manfred (Proceedings CAT'88 Computer Aided Technologies in Manufacturing, 4th Int. Exhibition and Users Conf., 1988)
LFT Import::2019-08-05 (272)

Entwurf eines erweiterten CAD/CAP-Datenmodells - Greska, Wolfgang; Hoffmann, Peter; Geiger, Manfred (Blech, Rohre, Profile, 1994)
LFT Import::2019-07-15 (609)

Ermittlung vin thermischen und mechanischen Werkstoffeigenschaften höchstfester Vergütungsstähle für das Presshärten - Merklein, Marion; Geiger, Manfred; Lechler, Jürgen (Tagungsband VDEh-Workshop: Moderne thermomechanische Prozessstrategien in der Stahlumformung, 2007)
LFT Import::2019-08-05 (1459)

Erweitertes Mesoskoisches Modell zur FE-Berechnung komplexer Mikroumformprozesse - Geißdörfer, Stefan; Engel, Ulf; Geiger, Manfred (Proceedings of the 2nd Colloquium of DFG Priority Program Process Scaling, 2005)
LFT Import::2019-08-05 (1201)

Estimation of Tool Life in Bulk Metal Forming Based on Different Failure Concepts - Falk, Bernd; Engel, Ulf; Geiger, Manfred (Journal of Materials Processing Technology, 1998)
LFT Import::2019-07-16 (1155)
Keywords: Cold forging; Fatigue; Finite elements; Tool life

Excimer Laser Micro Texturing of Cold Forging Tool Surfaces - Influence on Tool Life - Geiger, Manfred; Popp, Uwe; Engel, Ulf (CIRP Annals - Manufacturing Technology, 2002)
LFT Import::2019-07-16 (1680)
Keywords: Excimer Laser; Surface; Tribology

Excimer Laser Processing of Ceramics Assited by a Diagnostic System - Geiger, Manfred; Lutz, N; Biermann, S (Proceedings of SPIE, 1991)
LFT Import::2019-07-15 (247)

Excimer Laser Radiation - A Promising Tool for Microstructuring Ceramics - Geiger, Manfred; Lutz, Norbert; Goller, M. (Lasers in Engineering, 1993)
LFT Import::2019-07-15 (410)

Excimer Laser Texturing of Hard Coated Cold Forging Tools - Investigations on Tool Life - Popp, Uwe; Neudecker, Thomas; Engel, Ulf; Geiger, Manfred (Advanced Technology of Plasticity, Proceedings of the 7th ICTP, 2002)
LFT Import::2019-08-05 (1682)

Excimer Laser Texturing of Tool Surfaces and its Influence on Friction in Cold Forging - Popp, Uwe; Neudecker, Thomas; Engel, Ulf; Geiger, Manfred (Proceedings of the 2nd International Conference THE Coatings in Manufacturing Engineering, 2001)
LFT Import::2019-08-05 (836)

Experimental and analytical investigations on friction stir welding of steel aluminium tailored hybrids - Geiger, Manfred; Merklein, Marion; Giera, Artur; Staud, Detlev (Production Engineering, 2006)
LFT Import::2019-07-16 (1254)

Experimental and numerical evaluation of different powder metallurgical steels for cold forging tools - Falk, Bernd; Engel, Ulf; Geiger, Manfred (Advanced Technology of Plasticity 1999, Proc. of the 6th Int. Conf. on Technology of Plasticity, Vol. 1, 1999)
None
LFT Import::2019-08-05 (1997)

Experimental and Numerical Investigation of the Formability of Laser Welded Patchwork Blanks - Lamprecht, Klaus; Geiger, Manfred (Sheet Metal 2005, Proceedings of the 11th International Conference on Sheet Metal; Advanced Materials Research, 2005)
Within the past decades tailored welded blanks have become a key product for the construction of lightweight automotive bodies. Following the principle of applying material only where it is really needed results in an improved stiffness and crash worthiness of the body-in-white, while at the same time weight and production costs may be reduced. An alternative to the concept of tailored blanks is the so-called patchwork blank technique. The principle of patchwork blanks is to add a flat piece of sheet metal onto the main blank in the areas where reinforcements are required. The assembly can be done by adhesive bonding, resistance spot welding or laser welding prior to forming. The major benefits of this technique in comparison to tailored blanks are the abolition of cutting operations and a high flexibility regarding the shape and position of the reinforcement. Even if there is a big application potential for patchwork blanks in automobile production, practical realisation of this innovative technique is hindered due to a lack of knowledge regarding the formability of patchwork blanks. In this study the formability of laser welded patchwork blanks is investigated by means of experimental trials and finite element analysis. In order to simulate accurately the forming processes of patchwork blanks using finite element analysis, knowledge about the characteristics of the weld metal, including the weld bead and the heat affected zone, is essential. Microhardness measurements have been applied to analyse the heat affected zone and to determine its lateral dimensions. The constitutive behaviour of the weld metal has been investigated by uniaxial tensile tests with a special sample geometry. The results obtained from these experimental investigations have been used to define different modelling techniques for the finite element analysis of patchwork blank forming processes. It can be shown that the consideration of the modified material properties along the weld seam leads to an improvement of the accuracy of the numerical calculation.
LFT Import::2019-08-05 (1126)
Keywords: Finite element method; Forming; Patchwork blank

Experimental Determination of Yielding of the Aluminium Wrought Alloy AA6016 for Biaxial Loading - Hußnätter, Wolfgang; Merklein, Marion; Geiger, Manfred (Proceedings of COMA 2007, 2007)
LFT Import::2019-08-05 (1385)

Experimental Determination of Yield Loci for Magnesium Alloy AZ31 under Biaxial Tensile Stress Conditions at Elevated Temperatures - Geiger, Manfred; Merklein, Marion; Hußnätter, Wolfgang; Grüner, Martin (Production Engineering, 2008)
The finite element analysis (FEA) has become one of the most relevant and most important tools in fields of sheet metal forming for designing processes and dimensioning parts. However, reliability and quality of the numerical results strongly depend on the whole FE-model and especially on the modeling of the material behavior, which shows wide impact on calculated stresses and strains of sheet metal parts. Therefore, the experimental determination of characteristic material data concerning anisotropic and temperature-effects is essential. In this paper the influence of temperature on the yielding and the hardening behavior of the magnesium sheet metal alloy AZ31 are investigated for different uniaxial and biaxial stress conditions. For that purpose an experimental setup has been developed at the Chair of Manufacturing Technology (LFT) which enables biaxial tensile testing of sheet metal. Yield loci of AZ31 are determined as a function of temperature and they are based on solely measurement data of the forming process itself. © German Academic Society for Production Engineering (WGP) 2008.
LFT Import::2019-07-29 (294)
Keywords: Computer aided engineering; Material characterization; Yield locus diagram

Experimental investigation of the contact phenomena in cold forging - Geiger, Manfred; Engel, Ulf; Niederkorn, Sorin; Pfestorf, Markus (Production Engineering, 1996)
LFT Import::2019-07-15 (640)

Experimental Setup for Determination of Yield Loci - Demands of Accuracy - Hußnätter, Wolfgang; Geiger, Manfred (Proceedings of the 4th JSTP International Seminar on Precision Forging, 2006)
LFT Import::2019-08-05 (1260)

Experimentelle Untersuchung des Bruchverhaltens von Hartmetallen für Fließpreßmatrizen - Wissmeier, Hans-Jürgen; Engel, Ulf; Geiger, Manfred (Draht, 1990)
LFT Import::2019-07-15 (742)

Expertensystem zur Vorhersage des Werkzeugversagens - Cser, L; Engel, U; Geiger, Manfred (Werkstatt und Betrieb, 1992)
LFT Import::2019-07-15 (360)

Fatique of PVD and CVD Coated Tool Steel. - Geiger, Manfred; Hinsel, Christian (Proc. of the 29th Plenary Meeting of the International Cold Forging Group (1996), 1996)
LFT Import::2019-08-05 (644)

FE-Analysis Based Prediction of Tool Life in Cold Forging With the Consideration of Stochastic Process Characteristics - Geiger, Manfred; Engel, Ulf; Völkl, Ralf (Production Engineering - Annals of the WGP, 2005)
LFT Import::2019-08-05 (1216)

FE-Analysis for the Double Blank Hydroforming of Complex Structures - Vahl, Meik; Celeghini, Martino; Geiger, Manfred (Proceedings of the Numsheet 2002, 2002)
LFT Import::2019-08-05 (1671)

Feinblechprüfung mit magnetinduktiven Prüfverfahren - Schwind, Michael; Engel, Ulf; Geiger, Manfred (DVM-Berichtsband der Tagung Werkstoffprüfung 1994 in Bad Nauheim, 1994)
LFT Import::2019-08-05 (623)

FEM Simulation of Mixed-Mode Fatigue Crack Growth in Metal Forming Tools - Hänsel, Matthias; Engel, Ulf; Geiger, Manfred (Mixed Mode and Fatigue Fracture ESIS 14, 1993)
LFT Import::2019-08-05 (420)

FEM Simulation of the Laser Beam Welding Process. - Otto, Andreas; Geiger, Manfred (M4PL, Proceedings of the 11th Meeting on Mathematical Modelling of Material Processing with Lasers, 1995)
LFT Import::2019-08-05 (573)

FEM Simulation of Transient Processes during Laser Beam Welding. - Geiger, Manfred; Otto, Andreas (Production Engineering, 1996)
LFT Import::2019-07-15 (652)

Fertigungsaspekte zur umformtechnischen Herstellung von Bauteilen aus Magnesiumblech für den Fahrzeugbau - Geiger, Manfred; Merklein, Marion; Hecht, Joachim; Stich, A. (Tagungsband EFB-Kolloquium 2006 "Konstruktionskonzepte der Gegenwart und Zukunft - Herausforderungen an die Blechbearbeitung", 2006)
LFT Import::2019-08-05 (1271)

Fertigungstechnik- Neue Fachrichtung an der Universität Erlangen-Nürnberg - Geiger, Manfred; Feldmann, K; Kuhn, G (Das Neue Erlangen, 1983)
LFT Import::2019-07-12 (175)

FE-Simulation des selektiven Laserstrahlsinterns von Metallpulver - Niebling, Frank; Otto, Andreas; Geiger, Manfred (LaserOpto, 2000)
LFT Import::2019-07-15 (795)

FE-Simulation des Werkzeugversagens von Fließpreßmatrizen - Geiger, Manfred; Hänsel, Matthias (Kaltmassivumformung Cold Forging (8. Int. Kongress Kaltumformung Nürnberg), 1990)
LFT Import::2019-08-05 (726)

FE-Simulation of Microforming Process Applying a Mesoscopic Model - Geißdörfer, Stefan; Engel, Ulf; Geiger, Manfred (International Journal of Machine Tools and Manufacture, 2004)
LFT Import::2019-07-16 (1060)

FE- Simulation of Mixed- Mode Fatigue Crack- Growth in Metal Forming tools - Hänsel, M; Engel, U; Geiger, Manfred (Proc. Int. Conf. on Mixed- Mode Fracture and Fatigue, Wien, 1991)
LFT Import::2019-08-05 (252)

Festakt 25 Jahre Institut für Maschinenbau der Universität Erlangen-Nürnberg. Mit Laudatio und Festvortrag anlässlich der Ehrenpromotion von K.-D. Bouzakis durch die Technische Fakultät - Kreis, Oliver; Geiger, Manfred; Gaus, Ingrid (2007)

Finite Elemente Simulation of Deep Drawing of Tailored Heat Treated Blanks - Geiger, Manfred; Merklein, Marion; Kerausch, Michael (Annals of the CIRP, 2004)
LFT Import::2019-08-05 (1055)

Flexible Blechbearbeitung durch Computereinsatz - Geiger, Manfred (Technische Rundschau, 1985)
LFT Import::2019-07-12 (181)

Flexible Blechumformung mit Laserstrahlung - Laserstrahlbiegen - Geiger, Manfred; Vollertsen, F; Amon, S (Blech, Rohre, Profile, 1991)
LFT Import::2019-07-15 (250)

Flexible Kinematic 3D-bending of Tubes and Profiles - Nock, Marco; Geiger, Manfred (Proceedings of the 7th International Conference on Technology of Plasticity, 2002)
LFT Import::2019-08-05 (1678)

Flexibles Biegen stranggepreßter Aluminium Profile - Geiger, Manfred; Arnet, Horst; Engel, Ulf; Vollertsen, Frank (Blech, Rohre, Profile, 1995)
LFT Import::2019-07-16 (1972)

Flexibles Biegen stranggepreßter Aluminium-Profile - Geiger, Manfred; Arnet, Horst; Engel, Ulf; Vollertsen, Frank (Blech, Rohre, Profile, 1995)
LFT Import::2019-07-15 (518)

Flexibles Blechbearbeitungssystem im interdisziplinären Forschungsprojekt PAP - Geiger, Manfred; Geißler, Uwe (Blech, Rohre, Profile, 1988)
LFT Import::2019-07-15 (281)

Flexibles Laserstrahllöten durch indirekte Bestrahlungsstrategien - Rahn, A.; Fleckenstein, Marc; Fröhlich, T.; Geiger, Manfred (Laser in der Elektronikproduktion & Feinwerktechnik, 2001)
LFT Import::2019-07-15 (873)

Flexible spatial forming of a tube using an elastomere tool - Nock, Marco; Geiger, Manfred (ICAFT 2003, 10. Sächsische Fachtagung Umformtechnik SFU, Proceedings of the 1st International Conference on Accuracy in Forming Technology, 2003)
LFT Import::2019-08-05 (1001)

Flexibles Profilbiegen mit Polyurethanmatrize - Geiger, Manfred; Engel, Ulf; Vollertsen, Frank; Arnet, Horst (Flexible Umformtechnik, 1995)
LFT Import::2019-08-05 (1983)

Flexible straightening of car body shells by laser forming - Geiger, Manfred; Vollertsen, Frank; Deinzer, Günter (Proceedings of the North American Deep Drawing Research Group (NADDRG), 1993)
Distortion after welding is one of the problems arising during the manufacturing especially of visible parts for car body shells. The straightening work has to be minimized in order minimize production times. A system is presented which may be used for cutting, welding and straightening of car body shell parts by application of a laser beam. Some aspects of distortion after laser beam welding are highlighted. Distortion decreases with increasing welding speed. The process of laser beam bending, e. g. bending with thermal induced stresses, is presented. It is shown that the process can be sufficientl controlled. Influence parameters on the working result are discussed. It is concluded that straightening by laser beam bending should be possible in an automated system. In addition, the results show that there are the same parameters which control the distortion after welding and the bending angle after laser beam bending. So the results from laser beam bending may be used to minimize the distortion after welding. © Copyright 1993 Society of Automotive Engineers, Inc.
LFT Import::2019-07-15 (415)

Formability of accumulative roll bonded aluminum AA1050 and AA6016 investigated using bulge tests - Topic, Irena; Höppel, Heinz Werner; Staud, Detlev; Merklein, Marion; Geiger, Manfred; Göken, Mathias (Advanced Engineering Materials, 2008)
The paper reports one of the very first attempts to investigate the formability of ultrafine- grained aluminum sheets produced by a severe plastic deformation process known as accumulative roll bonding. During hydraulic bulge testing the samples showed a tendency to higher achievable burst pressures and/or von Mises equivalent strains with increasing number of accumulative roll bonding cycles, indicating promising deformation behaviour and good formability.
WW1::765

Formability of Tailored Blanks from Steel and Aluminium Alloys. - Vollertsen, Frank; Schultz, Markus; Geiger, Manfred (Advanced Sheet Metal Forming, Proc. 19th Biennial IDDRG Congress (1996), 1996)
LFT Import::2019-08-05 (670)

Forming of microparts - effects of miniaturization on friction - Tiesler, Nicolas; Engel, Ulf; Geiger, Manfred (): Advanced Technology of Plasticity, Proc. Of the 6th Int. Conf. on Technology of Plasticity ICTP 1999, Vol. II, 1999)
None
LFT Import::2019-08-05 (1995)

Formklassifizierung von Blechteilen mit Fuzzy-Logic - Geiger, Manfred; Backes, Frank; Greska, Wolfgang (CIM-Management, 1993)
LFT Import::2019-07-15 (386)

Fortschrittliche Programmierung von 3D-Laseranlagen. - Geiger, Manfred; Reinhart, G.; Backes, Frank; Bauer, L. (Blech, Rohre, Profile, 1996)
LFT Import::2019-07-15 (654)

Fracture Mechanics Analysis of Extrusion Dies - Geiger, Manfred (Annals of the CIRP Vol 40/1991/1, 1991)
Premature tool failure caused by fatigue crack growth or wear is a severe problem in industrial application of meal forming technology. Better knowledge about manufacturing process, tool loading and fracture behaviour is necessary in order to improve tool design. Process simulation applying Finite Element Method could offer a powerful assistance for process-adjusted tool layout. The paper will give some results of FE-simulation of tool loading and fatigue crack propagation in extrusion dies and some considerations about tool life prediction. A new approach to J-controlled fatigue crack growth under complex mixed mode tool loading will be presented. © 1991 CIRP.
LFT Import::2019-08-05 (235)
Keywords: forming; fracture; simulation; tool life

Friction stir knead welding of steel aluminium butt joints - Geiger, Manfred; Micari, F.; Merklein, Marion; Fratini, Livan; Contorno, D.; Giera, Artur; Staud, Detlev (International Journal of Machine Tools and Manufacture, 2008)
To develop steel aluminium-tailored hybrids in a butt joint for sheets in a thickness of about 1 mm conventional Friction Stir Welding is not feasible due to a high distortion of the welded specimen. Contrary to Friction Stir Welding the tool used for Friction Stir Knead Welding has no pin wherefore higher welding speeds can be realised. Due to the fact that this is a newer process, applied for patent in 2005, the cut contours of the edges and their variations have to be optimised by numerical analysis to transfer a maximum of load in order to improve the formability. The examined materials in this paper are steel DC04, as well as the aluminium alloys AA5182 and AA6016 in sheet thicknesses of 1 mm. Accompanying experimental investigations, as tensile tests, will evaluate the quality of the welding mechanism. As the mechanics of the new welding technology is not fundamentally investigated until now, metallographic investigations are performed, and additionally micro hardness measurements are carried out to verify the changes in the hardness distribution in the welding zone after stirring and welding. © 2007 Elsevier Ltd. All rights reserved.
LFT Import::2019-07-29 (1509)
Keywords: Aluminium; Friction Stir Knead Welding; Simulation; Steel

Friction stir welding of aluminium foam sandwich - Geiger, Manfred; Dörfler, Stephan Manuel; Otto, Andreas (Production Engineering Research and Development - Annals of the German Academic Society for Production Engineering, 2005)
LFT Import::2019-08-05 (1123)

From basic research to industrial application - new developments for laser beam welding - Otto, Andreas; Geiger, Manfred (Proceedings of the 4th International WLT-Conference on Lasers in Manufacturing, 2007)
LFT Import::2019-08-05 (1487)

Fügen von niedriglegiertem Baustahl im Dünnblechbereich durch flußmittelfreies Laserstrahlhartlöten. - Hanebuth, Henning; Geiger, Manfred (Proc. der Deutsch-Französischen Tagung Mechanik und Optik - Hochleistungslaser im Maschinenbau, 1995)
LFT Import::2019-08-05 (560)

Fully Automated Nd:YAG-Welding-System for Assembly of Electronic Components - Geiger, Manfred; Breitenbach, Frank; Govekar, E.; Brassel, Jan-Oliver (Proceedings of the ICARCV 1998, 1998)
LFT Import::2019-08-05 (1585)

Functional protective coatings for improved tool life in cold forging - Engel, Ulf; Hinsel, Christian; Geiger, Manfred (THE Coatings, Proc. of the 1st Int. Conf., 14-15 Oct 1999 Thessaloniki, Greece, 1999)
None
LFT Import::2019-08-05 (2001)

Fundamental aspects for the evaluation of the fatigue behavi¬our of cold forging tools - Falk, Bernd; Engel, Ulf; Geiger, Manfred (Journal of Materials Processing Technology, 1999)
LFT Import::2019-07-16 (2003)

Fundamentals on the manufacturing of sheet metal micro parts. - Geiger, Manfred; Vollertsen, Frank; Kals, Roland (CIRP Annals - Manufacturing Technology, 1996)
LFT Import::2019-07-15 (658)

Fuzzy-Logic knowledge representation for water jet cutting of lightweight composites - Geiger, Manfred; Kach, A.; Hohenstein, Ralph; Maros, Z. (Machining Science and Technology, 2003)
LFT Import::2019-07-15 (1002)

Genaubearbeitung beim Schneiden von Stahlblechen mit CO2- Lasern - Nuss, Rudolf; Biermann, S; Geiger, Manfred (Blech, Rohre, Profile, 1987)
LFT Import::2019-07-15 (190)

Genaubearbeitung von Feinblechen durch Laserstrahlschneiden - Geiger, Manfred; Nuss, Rudolf (Laser-Materialbearbeitung für den Automobilbau, 1987)
LFT Import::2019-07-15 (187)

Generalized Life-Time Model for Cold Extrusion Tools - Cser, L; Geiger, Manfred (CIRP Annals - Manufacturing Technology, 1991)
It is very difficult to predict the expected life time at cold extrusion because of die complexity of interchanges among the different kinds of failures and failure mechanisms. To the prediction of the most probably life time for a class of cold forming tools an expert system bas been developed which takes into account the geometrical, mechanical and inbological boundary conditions and utilizes factory data and experience. In order to be able to handle the different mechanisms of failure it was necessary to work out a generalized life-time model of cold forming dies. The governing idea is similar on the state-space method used in the qualitative reasoning. All the damage mechanisms are active at the same time, but the life-time is determined by the dominant mechanism leading fastest to the total fall out of the die. The role of the dominant mechanism can be taken over by other mechanisms during the exploitation of the die, depending on the changes in the state variables. The expert system is based on the feature processing. The tool is divided into the elements carrying not only geometric information, but information about the loads and the possible failure also. The elements of the same tool part are connected with each other by different types of contact and neighbours between the elements of different tool parts. © 1991 CIRP.
LFT Import::2019-07-15 (231)
Keywords: EXPERT SYSTEM; EXTRUSION; FORMING; TOOL-LIFE

Generation of ceramic coatings by laser pyrolysis of organo-metallic polymers - Geiger, Manfred; Ziegler, G.; Engel, Ulf; Motz, G.; Krauß, Hans-Joachim (THE Coatings, Proc. of the 1st Int. Conf., 14-15 Oct 1999 Thessaloniki, Greece, 1999)
None
LFT Import::2019-08-05 (2002)

Generation of Functional Coatings and Structures by Laser Pyrolysis of Preceramic Polymers - Geiger, Manfred; Krauß, Hans-Joachim (Production Engineering. Annals of the German Academic Society for Production Engineering, 2006)
LFT Import::2019-08-05 (1342)

Geometrieeinflüsse beim Laserstrahlschneiden - Biermann, Stefan; Geiger, Manfred; Hoffmann, Martin; Nuss, Rudolf (Proc. 2nd European Conf. Laser Treatment of Materials (ECLAT 88), Bad Nauheim, 1988)
LFT Import::2019-08-05 (256)

Herstellung flächiger Verbundbauteile mit Metallschaumkernen - Körner, Carolin; Heinrich, Frank; Singer, Robert; Otto, A.; Schöberl, T.; Geiger, Manfred (Sonderforschungsbereich 396 - robuste verkürzte Prozessketten für flächige Leichtbauteile - 1. Berichtskolloquium 24./25.Mai, 2000)
LFT Import::2019-08-05 (785)

High-power laser welding of contaminated steel sheets - Geiger, Manfred; Kägeler, Christian; Schmidt, Michael (Production Engineering, 2008)
A deep penetration laser welding process differs from a heat conduction laser welding process in the generation of a steam capillary through the material. The so called keyhole is formed if high energy densities of the laser beam vaporize the base material, leading to a vapor-filled channel which is surrounded by a liquid weld pool. The shape and the oscillations of the keyhole are affected by various physical parameters of the welding process. Under constant process conditions a balance of pressure keeps the capillary open. If the material is contaminated by a layer with physical properties differing from the bulk material (e.g. oil), the equilibrium is disturbed in a negative way. The coating evaporates during the melting of the base material, resulting in vapor locks at the capillary and the weld pool, leading to pores and failures along the weld seam. In order to understand and avoid this effect, it is the aim to analyze and describe the failure generating mechanisms. Additionally, a control method of the laser power is investigated which influences the keyhole's oscillations and could suppress an unwanted collapse. © German Academic Society for Production Engineering (WGP) 2008.
LFT Import::2019-07-29 (1541)
Keywords: Laser welding; Process oscillations; Production process

High Precision Laser Beam Welding and Brazing - New Technologies and Components for Quality Assurance - Geiger, Manfred; Deinzer, Günter; Hanebuth, Henning (Proc. of the 75th Annual Convention of the American Welding Society, 1994)
LFT Import::2019-08-05 (466)

High quality laser cuts with the aid of on-line diagnostics - Geiger, Manfred; Biermann, Stefan; Nuss, Rudolf (CLEO 88 - Conference on Lasers and Electro-Optics, 25-29. April, Anaheim, Ca., 1988)
LFT Import::2019-08-05 (279)

High-temperature processing of aluminium foam - Hahn, Markus; Otto, Andreas; Geiger, Manfred (MetFoam 2003, Cellular Metals and Metal Foaming Technology. Proceedings of the 3rd International Conference on Cellular Metals and Metal Foaming Technology, 2003)
LFT Import::2019-08-05 (963)

Hybridschweißen von Kunststoffen - Durch den kombinierten Einsatz von Laserstrahlung und Heizstrahlung beim Schweißprozess eröffnen sich völlig neue Anwendungsfelder - Geiger, Manfred; Brandmayer, O.; Frick, Thomas (Joining Plastics - Fügen von Kunststoffen, 2007)
LFT Import::2019-07-16 (1482)

Hydroforming in Patchwork Blanks - Numerical Modeling and Experimental Validation - Lamprecht, Klaus; Merklein, Marion; Geiger, Manfred (Proceedings of the 6th International Conference and Workshop on Numerical Simulation of 3D Sheet forming Processes (NumiSheet), 15.-19.08., Detroit, USA, 2005)
LFT Import::2019-08-05 (1139)

Hydroforming of Deep-Drawn Preforms? A Novel Approach Towards Innovative Sheet Metal Components - Geiger, Manfred; Lamprecht, Klaus (Production Engineering - Annals of the WGP, 2006)
LFT Import::2019-08-05 (1270)

Hydroforming of Inhomogeneous Sheet Pairs with Counterpressure - Geiger, Manfred; Merklein, Marion; Cojutti, Massimo (Production Engineering Research and Development, 2008)
LFT Import::2019-07-29 (1544)

Hydroforming of Laser Welded Tailored and Patchwork Blanks - Tolazzi, Massimo; Lamprecht, Klaus; Geiger, Manfred (LANE, 2007)
LFT Import::2019-08-05 (1441)

Hydroforming of Sheet Metal Pairs - Geiger, Manfred; Vollertsen, Frank; Hein, Philipp (Sheet Metal 1998: Proceedings of the 6th International Conference on Sheet Metal, 1998)
LFT Import::2019-08-05 (1599)

Idroformatura di lamiera per strutture complesse - Geiger, Manfred; Tolazzi, Massimo (Lamiera, 2005)
LFT Import::2019-07-16 (1209)

Improved Deep Drawability of Aluminium Blanks by Local Laser Heat Treatment - Kerausch, Michael; Merklein, Marion; Geiger, Manfred (Laser Assisted Net shape Engineering 4. Proceedings ot the 4th LANE, 2004)
LFT Import::2019-08-05 (1066)

Improved fatigue strength of cold forging tools by surface and coating technologies - Hinsel, Christian; Celeghini, Martino; Engel, Ulf; Geiger, Manfred (Advanced Technology of Plasti¬city 1990, Proc. of the 6th Int. Conf. on Technology of Plasticity, Vol. 1, 1999)
None
LFT Import::2019-08-05 (1996)

Improved material flow for deep drawing of aluminium blanks by local laser heat treatment - Kerausch, Michael; Merklein, Marion; Geiger, Manfred (Proceedings of the 10th International Conference on Sheet Metal, She Met, 2003)
LFT Import::2019-08-05 (952)

Improved Tribological Behavior of Cold Forging Tool Surfaces by Excimer Laser Micro Texturing - Geiger, Manfred; Popp, Uwe; Engel, Ulf (Production Engineering, 2002)
LFT Import::2019-07-16 (1679)

Improvement of axial sliding in the tube hydroforming process of long components due the reduction of friction by high viscous fluid flow - Geiger, Manfred; Dal Bò, Paolo (Proceedings of the 8th ESAFORM Conference on material forming, 27.-29. April 2005, Cluj-Napoca, Romania, 2005)
LFT Import::2019-08-05 (1194)

Improvement of Formability in Tube Hydroforming by Reduction of Friction with a High Viscous Fluid Flow - Geiger, Manfred; Vollertsen, Frank; Dal Bò, Paolo (Production Engineering, 2006)
LFT Import::2019-07-16 (1253)

Improvement of the Reliability of Laser Beam Micro Welding as Interconnection Technique. - Glasmacher, Matthias; Pucher, Hans-Jörg; Geiger, Manfred (Proceedings of the OE/LASER Optoelectronics and Lasers, 1996)
LFT Import::2019-08-05 (659)

Improvements in the Aluminium Welding Process through FE-Modelling - Komlodi, Attila; Otto, Andreas; Geiger, Manfred (Sheet Metal 2003, Proceedings of the 9th International Conference on Sheet Metal, 2003)
LFT Import::2019-08-05 (968)

Improving Laser Ablation by Controlled Laser Beam Parameters. - Kauf, Michael; Hutfless, Joachim; Geiger, Manfred (Proc. of the EuroLaser Academy, 1995)
LFT Import::2019-08-05 (570)

Improving the Fatigue Resistance of Cold Forging Tools by FE-Simulation and Computer Aided Die Shape Optimization - Geiger, Manfred; Hänsel, M; Rebhan, T (Proceedings of the Institution of Mechanical Engineers, Part B: Journal of Engineering Manufacture, 1992)
It is the intention of the present article to point out a new method for computer aided tool optimization as part of computer integrated tool manufacturing. Based on the results of finite element (FE) analysis and subsequent tool failure simulation, it is possible to optimize the FE model of a tool already at the stage of construction, in order to enhance the service life and process reliability. The permissible degree of freedom for any shape correction, of course, is mainly limited by constructive constraints of the tool and the properties of the material flow during the extrusion process. Thus the resulting optimized geometry has to he considered as a possible constructive alternative. However, analytical as well as practical solutions already show that a parabolical or elliptical curved surface contour, replacing a regular radius, not only improves the fatigue resistance but may have a positive influence on material flow behaviour, friction forces and resulting tool loads as well (1). The influence imposed on the material flow by the geometrical modification of the die shape will be clarified in future by the results of FE process simulation. A renewed simulation run, employing the optimized shape, may be conducted immediately after the optimization process. Along with current material research, the simulation of tool failure based on the finite element method (FEM) analysis of forging techniques (FE process simulation) therefore represents a promising direction for future developments (2-4). © 1992, Institution of Mechanical Engineers. All rights reserved.
LFT Import::2019-07-15 (374)

Increased Tool Life in Cold Forging with Micro Textured Tool Surface - Popp, Uwe; Engel, Ulf; Geiger, Manfred (ICEM 2003, Proceedings of the International Workshop on Environmentally Conscious Manufacturing, 2003)
LFT Import::2019-08-05 (993)

Increase of Efficiency for the XeCl excimer laser ablation of ceramics - Geiger, Manfred; Becker, Wolfgang; Rebhan, Thomas; Hutfless, Joachim; Lutz, Norbert (Applied Surface Science, 1996)
LFT Import::2019-07-15 (637)

Increasing Tool Life in Cold Forging by Laser Micro Texturing the Tool Surface - Popp, Uwe; Engel, Ulf; Geiger, Manfred (Proceedings of the 3rd International Conference THE Coatings in Manufacturing Engineering, 2002)
LFT Import::2019-08-05 (1683)

Industrial Ceramics in Cold Forging: Increasing Dimensional Accuracy and Surface Quality - Arbak, Murat; Putz, Alexander; Engel, Ulf; Geiger, Manfred (Proceedings of the 4th JSTP International Seminar on Precision Forging, Nara, Japan, 2006)
LFT Import::2019-08-05 (1258)

Inferenzmaschine für ein Biegestadienplanungssystem - Geiger, Manfred; Hoffmann, M; Kluge, B (ZWF (1992), Nr. 87/5, 1992)
LFT Import::2019-08-05 (377)

Influence of laser-produced microstructures on the tribological behaviour of ceramics - Geiger, Manfred; Roth, Stephan; Becker, Wolfgang (Surface & Coatings Technology, 1998)
LFT Import::2019-07-16 (1594)
Keywords: Ceramics; Excimer laser; Microstructuring; Tribology

Influence of Media on Process Stability in Sheet Metal Hydroforming - Geiger, Manfred; Merklein, Marion; Blankl, Andreas (International Journal of Materials & Product Technology, 2008)
The difference between sheet metal hydroforming and deep drawing is elementary: one half of the tool is substituted by hydraulic pressure. In order to guarantee an optimised forming result a tight cavity in the tool has to be created, since as soon as a leakage occurs, the forming pressure decreases rapidly and the forming operation is interrupted. The separation plane of the tool is the critical area for an occurring leakage because here a metallic sealing is often realised. Therefore, the objective of this paper is to present theoretical consideration on the leakage problematic in hydroforming. For illustration of the problem an existing process chain is presented in the beginning of this paper. Subsequently theoretical considerations are made. In the end a new strategy for defusing the leakage problem by changing the hydroforming media is presented in the outlook. Copyright © 2008 Inderscience Enterprises Ltd.
LFT Import::2019-07-29 (1505)
Keywords: Hydroforming; Process stability; Sheet metal

Influence of microstructure on the mechanical properties and the forming behaviour of very thin metal foils - Diehl, Alexander; Engel, Ulf; Geiger, Manfred (International Journal of Advanced Manufacturing Technology, 2010)
The demand for accurate process design of microforming processes is increasing steadily due to ongoing miniaturisation. Occurring size effects, however, prevent the transfer of existing know-how of standard sheet forming processes with conventional dimensions like blanking, bending and deep drawing on microforming processes. These size effects are either generally valid for all microforming processes, as the influence of the share of surface grains are process-specific, like the influence of large strain gradients as they appear, e.g. in bending processes. A decisive parameter for the occurrence of size effects is the ratio of material mean grain size to foil thickness. For a simulation-based description of microforming processes, the implementation of size-dependent material behaviour in finite element (FE) simulation is essential. Hence, a reliable determination of size-dependent mechanical properties as input data for FE simulation is needed to provide a broad fundamental database for a future theoretical description of microforming processes. In the present paper, the influence of the material microstructure on the mechanical properties of metal foils with thicknesses ranging from 25 to 500 μm is discussed based on tensile tests, bulge tests and fundamental bending experiments. Challenges resulting from the small thickness of the metal foils are pointed out, and future demands regarding determination of material characteristics of thin metal foils are presented. © 2008 Springer-Verlag London Limited.
LFT Import::2019-07-29 (1536)
Keywords: Bending; Hydraulic bulge test; Mechanical properties; Metal foils; Pneumatic bulge test

Influence of Process and Material Parameters on Ablation Phenomena and Mechanical Properties of Ceramics and Composites for Excimer Laser Treatment - Geiger, Manfred; Lutz, Norbert; Rebhan, Thomas; Goller, M. (Laser Treatment of Materials, Oberursel : DGM Informationsgesellschaft, 1992)
LFT Import::2019-08-05 (477)

Influence of Various Atmospheres on the Laser Micro Welding Process of Electronic Contacs - Geiger, Manfred; Fleckenstein, Marc (Production Engineering. Annals of the German Academic Society for Production Engineering, 2001)
LFT Import::2019-08-05 (865)

Innenhochdruckumformen mit erwärmtem Medium - eine Leichtbautechnologie für die Aluminium- und Magnesium- Halbzeugumformung - Stich, A.; Celeghini, Martino; Novotny, Stefan; Geiger, Manfred; Haldenwanger, H.G. (Tagungsband zum 7. Dresdner Leichtbausymposium "Interaktionsfeld Leichtbau - Effizienzsteigerung durch dichtere Vernetzung", 26.-28. Juni, Dresden, 2003)
LFT Import::2019-08-05 (956)

Innenhochdruck-Umformen von Doppelblechen - Geiger, Manfred; Neugebauer, Stephan; Merklein, Marion; Lamprecht, Klaus; Tolazzi, Massimo; Bahn, V. (Wirkmedienbasierte Fertigungstechniken zur Blechumformung, Abschlussbereicht zum DFG-Schwerpunktprogramm SPP 1098, 28.-29.09., Dortmund, 2006)
LFT Import::2019-08-05 (1298)

Innenhochdruck-Umformen von Magnesiumblechen - Merklein, Marion; Hecht, Joachim; Hußnätter, Wolfgang; Geiger, Manfred (Karosserie II, 2006)
LFT Import::2019-07-16 (1312)

Innovationen in der Blechbearbeitung durch Integration der Lasertechnik in die Blechumformung - Geiger, Manfred; Hein, Philipp (Aachener Kolloquium für Lasertechnik, 1995)
LFT Import::2019-08-05 (544)

Innovationsmanagement für Laserstrahltechnologien: Strategische Überlegungen und ausgewählte Technologiebeispiele. - Hutfless, Joachim; Geiger, Manfred (Innovation und Kundennähe: Wachstumsstrategien im Wettbewerb. Tagungsband Müncher Management Koloquium, 1996)
LFT Import::2019-08-05 (660)

Innovative Kombinationen - Wirkmedienbasierte Umformung von Tailored Welded Blanks und Patchwork Blanks - Geiger, Manfred; Tolazzi, Massimo; Lamprecht, Klaus (Uni-Kurier-Magazin, 2004)
LFT Import::2019-07-16 (1107)

Innovative Manufactring Chain for Complex Hydroforming Parts - Special Solutions for Process and Systems Technology - Geiger, Manfred; Merklein, Marion; Blankl, Andreas (Proceedings of the 22nd International Manufacturing Conference (IMC), 2005)
LFT Import::2019-08-05 (1198)

Innovatives Konstruktions- und Fertigungskonzept für Straßenbahn-Rohbau - Celeghini, Martino; Pohl, Thomas; Geiger, Manfred; Merklein, Marion; Hecht, Joachim; Meerkamm, H.; Stockinger, A. (8. Fachtagung Fügen und Konstruieren im Schnienfahrzeugbau, 2009)
LFT Import::2019-08-05 (1584)

Innovative Technologien für den Blech-Leichtbau - Geiger, Manfred; Meyer-Pittroff, Frank (Dresdner Leichtbausymposium, 1998)
LFT Import::2019-08-05 (1591)

In-Process Measurement of Bending Angles - Geiger, Manfred; Heckel, Werner (Production Engineering, 1996)
LFT Import::2019-07-15 (642)

In-situ-Ultraschallmessung der wahren Kontaktfläche bei Massivumformverfahren - Geiger, Manfred; Engel, Ulf; Vollertsen, Frank (Umformtechnik, 1993)
LFT Import::2019-07-15 (392)

In Situ Ultrasonic Measurement of the Real Contact Area in Bulk Metal Forming Processes. - Geiger, Manfred; Engel, Ulf; Vollertsen, Frank (CIRP Annals - Manufacturing Technology, 1992)
LFT Import::2019-07-16 (1965)
Keywords: contact area; forming; friction; interface; ultrasonics

Integrated manufacturing by hydroforming, laser welding and cutting of complex hollow parts - Kreis, Oliver; Celeghini, Martino; Geiger, Manfred; Merklein, Marion (LANE 2004, Proceedings of the 4th International Conference on Laser Assisted Net Shape Engineering, 21.-24.09.2004, Erlangen, Germany, 2004)
LFT Import::2019-08-05 (1084)

Integrated Tube and Double Sheet Hydroforming Technology - Optimised Process for the Production of a Complex Part - Geiger, Manfred; Merklein, Marion; Cojutti, Massimo (Key Engineering Materials, 2007)
LFT Import::2019-07-16 (1399)
Keywords: Double sheet hydroforming; Process optimisation; Tube hydroforming

Integration of Diagnostics in High Power Laser Systems for Optimization of Laser Material Processing - Biermann, S; Hutfless, J; Geiger, Manfred (SPIE- High Power Lasers. Int. Conf. OE/Laser 91, 1991)
Experimental investigations on high power CO2-laser systems has been carried out. To ensure the processing quality and to allow a fast reaction in case of an accident a diagnostic system was developed and realized with integrating special equipment for on-line and off-line diagnostics for laser beam, gasflow and workpiece temperature.
LFT Import::2019-08-05 (229)

Integration of Double Sheet and Tube Hydroforming Processes: Numerical Investigation of the Feasibility of a complex Part - Geiger, Manfred; Cojutti, Massimo (The 23rd International Manufacturing Conference 30th August - 1st September 2006, University of Ulster, 2006)
LFT Import::2019-08-05 (1314)

Integration of Laser Material Processing into the Computer-Aided Product and Process Development - Geiger, Manfred; Kach, Andreas (3rd International Conference on Integrated Design and Manufacturing in Mechanical Engineering, 2000)
LFT Import::2019-08-05 (768)

Integrierte Fertigung durch Umformen, Trennen und Fügen in einem Werkzeug - Geiger, Manfred; Kreis, Oliver (Autonome Produktion, 2003)
LFT Import::2019-07-15 (996)

Integrierte Konstruktion und Fertigungsvorbereitung - Hoffmann, Peter; Greska, Wolfgang; Geiger, Manfred (Blech, Rohre, Profile, 1994)
LFT Import::2019-07-15 (616)

Integriertes Bestück- und Laserstrahl-Lötsystem mit prozessbegleitender Qualitätssicherung - Geiger, Manfred; Albert, F. (Produktionssysteme in der Elektronik, 2005)
LFT Import::2019-07-16 (1224)

Integriertes Bestück- und Laserstrahl-Lötsystem mit prozessbegleitender Qualitätssicherung - Geiger, Manfred; Feldmann, K.; Bickert, Matthias; Fröhlich, Thomas; Zolleis, B. (Produktionssysteme in der Elektronik - Sonderforschungsbereich 356 - Bericht des Forschungsverbundes 1999 - 2001, 2001)
LFT Import::2019-08-05 (864)

Intelligente Werkzeuge für das Kokillen- und Druckgießen- Teil 1: Prozesskettezur Werkzeugfertigung und Metallfolien-LOM-Technologie - Prechtl, Martin; Niebling, Frank; Otto, Andreas; Geiger, Manfred; Sobczyk, M.; Behm, I. (Giesserei, 2004)
LFT Import::2019-07-16 (1026)

Intelligent Processing Head for CO2 Laser Material Processing - Geiger, Manfred; Neubauer, Norbert; Hoffmann, Peter (Production Engineering - Annals of the WGP, 1994)
LFT Import::2019-08-05 (600)

Internationale Forschung Umformtechnik - Geiger, R.; Geiger, Manfred (Industrieanzeiger, 1976)
LFT Import::2019-07-15 (336)

Investigation into the Process Basics of Warm Forming - Neugebauer, R.; Hartwig, H.; Geiger, Manfred; Bitter, Stefan (Advanced Technology of Plasticity, Proceedings of the 7th ICTP, 2002)
LFT Import::2019-08-05 (1685)

Investigation of the mechanical behaviour of advanced high strength steels under various loading conditions - Geiger, Manfred; Merklein, Marion; Kaupper, Markus (International Journal of Material Forming, 2008)
Nowadays advanced high strength steel sheets and related forming technologies play a vital role in light weight construction in the transportation sector. Within this paper the mechanical behaviour of the multi phase steels DP600, DP800 and CP800 is investigated, being focussed on the influence of various loading conditions in particular. Uniaxial tensile tests, layer compression tests and bulge tests are carried out, to characterize plastic material properties like anisotropy and work hardening. The forming behaviour is evaluated utilizing optical strain measurement, to obtain detailed information on the deformation behaviour. True stress strain curves are obtained, clearly quantifying the properties described above. The results are discussed and evaluated with regard to numerical simulation of sheet metal forming processes. © Springer/ESAFORM 2008.
LFT Import::2019-07-29 (207)
Keywords: Loading condition; Material characterization; Work hardening; Yielding

Investigation on heating strategies for hot stamping of boron alloyed steels - Kolleck, R.; Veit, R.; Merklein, Marion; Lechler, Jürgen; Geiger, Manfred (CIRP Annals - Manufacturing Technology, 2009)
LFT Import::2019-08-05 (1572)

Investigations on Double Sheet Hydroforming with Counterpressure - Cojutti, Massimo; Merklein, Marion; Geiger, Manfred (2nd International Conference on New Forming Technology, 2007)
LFT Import::2019-08-05 (1451)

Investigations on Formability and Tribology of Magnesium Sheets with Regard to Warm Forming processes - Geiger, Manfred; Merklein, Marion; Hecht, Joachim; Stich, A. (Proceedings of the 7th International Conference on Magnesium Alloys and their Applications, Nov 6-9, Dresden, Germany, 2006)
LFT Import::2019-08-05 (1337)

Investigations on Formability and Tribology with Regard to Warm Forming of Magnesium Sheets - Geiger, Manfred; Merklein, Marion; Hecht, Joachim (Production Engineering. Annals of the German Academic Society for Production Engineering, 2006)
LFT Import::2019-08-05 (1305)

Investigations on Forming Limits within Hot Stamping - Geiger, Manfred; Arbak, Murat; Engel, Ulf (Production Engineering, 2008)
LFT Import::2019-07-29 (1535)

Investigations on Seam Quality in Laser Beam Welding of Contaminated, Zinc Coated Sheets - Blankl, Andreas; Geiger, Manfred (Sheet Metal 2005, Proceedings of the 11th International Conference on Sheet Metal, 2005)
The customers' demand for high quality and low cost products with rising functionality forces the enterprises to cost savings. In production these cost savings can be accomplished by simplification or omission of handling operations in the process chain. In laser beam welding of stamped sheet metals a previous cleaning of the sheets is usually necessary to guarantee a sufficient seam quality at a lap joint. Due to the recent trend towards low use of lubricants in forming operations the question arises, whether this process could be avoided in order to lower the production costs. The disadvantage of this measure would be a degradation of the seam quality. This reduction shows up in a falling strength of the weld due to inclusions and pore formation. This paper deals with the impact of different types of contaminations on the quality of laser welding. Therefore several liquid (oils) and solid (metallic and non-metallic) contaminants are examined. Zinc coated sheets are investigated too, because a zinc contamination arises with these sheets in the welding operation. The zinc coating evaporates because of the high temperature and this leads to a high porosity in the welding seam. In both cases also the height of the gap between the two sheets is varied in order to investigate its influence on the weld. To reduce the effort of the investigations, but not the accuracy of the results, the laboratory trials were supported by the methods of design of experiments. After the welding operation, the quality of the welding seam is evaluated by means of its mechanical properties and tightness. The results of the investigations are discussed and the developed solution strategies are presented.
LFT Import::2019-08-05 (1138)
Keywords: Lubrication; Nd:YAG laser; Welding

Investigations on the Sheet Bending Process with Elastic Tools - Geiger, Manfred; Engel, U; Vom Ende, A (Journal of Materials Processing Technology, 1991)
The forming process investigated in this study is the bending of U-shaped parts with a rigid punch and an elastic die. The methods of the finite element approach used for the process simulation are described. One of the most important input data for such an analysis is the material characterization especially the description of the rubber-like behavior of the die. The experimental and theoretical procedures to determine the material constants are presented. The process simulation is performed for three sheet materials and different values of sheet thickness and die hardness. In comparison with some experimental results it is shown that the FEM-approach is suitable to simulate the characteristic features of the whole process such as e.g. the dependence of bend angle on material and thickness of the sheet. Furthermore the observed curvature of the bent part can be understood in terms of the calculated stress distributions on the interfaces between punch and sheet, and sheet and die respectively. The process force resulting from simulation can be taken as an upper bound. Thus, the methods discussed in this study are suited to improve the understanding of the process and to assist the engineer in designing a particular bending operation. © 1991.
LFT Import::2019-07-15 (238)

Investigations towards extended stability in laser brazing - Grimm, A.; Schmidt, Michael; Dietrich, Simon; Hoffmann, Peter; Geiger, Manfred (Laser Assisted Net Shape Engineering 5 - Proceedings of the LANE 2007, 2007)
LFT Import::2019-08-05 (1448)

Joining of DC04 and AA5182 in a butt joint configuration by laser assisted friction stir welding - Giera, Artur; Merklein, Marion; Geiger, Manfred (5th Laser Assisted Net Shape Engineering LANE, 2007)
LFT Import::2019-08-05 (1435)

Kaltmassivumformung - VDI-Tagung 1976 - Geiger, Manfred (VDI-Tagung 1976, 1977)
LFT Import::2019-08-05 (337)

Keramik als Werkzeugstoff in der Kaltmassivumformung - Arbak, Murat; Putz, Alexander; Engel, Ulf; Geiger, Manfred (Technik in Bayern, 2006)
LFT Import::2019-07-16 (1349)

Knowledge based automated process design using finite element intermediate states - Hagenah, Hinnerk; Kohlbauer, Rainer; Geiger, Manfred (Proceedings of the 4th CIRP International Seminar on Intelligent Computation in Manufacturing Engineering. ICME' 2004. Sorrento, Italy, 2004)
LFT Import::2019-08-05 (1038)

Knowledge Management and Environmental Aspects in Integrated Forming Process - Cser, Adrienn Orsolya; Geiger, Manfred; Celeghini, Martino (Advanced Technology of Plasticity, Proceedings of the 7th ICTP, 2002)
LFT Import::2019-08-05 (1709)

Kombination der Laser-Bearbeitung mit herkömmlichen Fertigungsverfahren - Geiger, Manfred; Nuss, Rudolf; Müller, Roland (Werkstatt und Betrieb, 1988)
LFT Import::2019-07-15 (283)

Kombiniertes 3D-Laserstrahlschneiden und -schweißen - ein neues Verfahren für die Karosseriefertigung - Geiger, Manfred; Hoffmann, Peter; Biermann, Stefan (Opto-Elektronik-Magazin, 1989)
LFT Import::2019-07-15 (432)

Kombiniertes Laserstrahlschneiden und -schweißen von Blechformteilen - Rief, Alfons; Nuss, Rudolf; Geiger, Manfred (Laser/Optoelektronik in der Technik, 1989)
LFT Import::2019-07-15 (440)

Kombiniertes Schneiden und Schweißen von Blechteilen im Automobilbau - Geiger, Manfred (2. Int. Anwenderforum Laser-Materialbearbeitung für den Automobilbau, 1990)
LFT Import::2019-08-05 (504)

Konzepte zur laserstrahlunterstützten, strukturierten Metallisierung von 3-D - Geiger, Manfred; Pucher, Hans-Jörg; Glasmacher, Matthias; Hutfless, Joachim; Kickelhain, J. (Berichtsband zum 1. Int. Kongreß MID 94 - Molded Interconnect Devices, 1994)
LFT Import::2019-08-05 (602)

Lamellierte Aktiv-Werkzeugelemente in flexiblen Blechumformwerkzeugen - Geiger, Manfred; Euringer, Maximilian (Blech, Rohre, Profile, 1998)
LFT Import::2019-07-16 (1587)

Laminated Object Manufacturing of Metal Foil - Process Chain and System Technology - Prechtl, Martin; Otto, Andreas; Geiger, Manfred (Advanced Manufacturing Systems and Technology: Proceedings of the 7th International Conference, 2005)
Laminated Object Manufacturing of metal foil as an automated two-step procedure is a novel technology for additive manufacturing of massive three-dimensional parts. It enables for example the production of technical tools like moulds. The great advantage hereby is the high accuracy in combination with a high stability of the resulting tools. A laser system for the automated stacking of metal foil contours has been developed. The stacking procedure is realised by a combination of layer fixing and contour generation with a laser beam. But the stability of the produced foil stack is insufficient for most kind of application. Therefore a second step to enhance the mechanical properties of the part is necessary. This can for example be realised by high temperature brazing or diffusion welding. In this paper the laser system for the automated stacking of metal foil contours is described as well as the required preparation of the layer data. Further on some results of investigations on the sub-processes layer fixing, counter generation and final joining are shown.
LFT Import::2019-08-05 (1127)
Keywords: Diffusion welding; Laser material processing; Rapid tooling

Laminated Tool System for Press Brakes. - Franke, Volker; Greska, Wolfgang; Geiger, Manfred (Manufacturing Systems, 1995)
LFT Import::2019-07-15 (516)

Laser Adjustment of Pre-assembled Systems using Actuators - Geiger, Manfred; Huber, Alexander (Production Engineering, Annals of the WGP, 2001)
LFT Import::2019-08-05 (921)

Laser Adjustment Using Actuators - Hagenah, Hinnerk; Geiger, Manfred (60 Excellent Inventions in Metal Forming, 2015)
After the identification and classification of laser forming mechanism the potentials of this technology in the field of adjustment was discovered. In order to use the possibilities in the field of micro systems technology the idea of specifically designed, task specific actuators was born and researched. The detected challenge of actuator design has been addressed with suitable algorithms models. The paper gives an overview of the possibilities and explains how the design challenge has been overcome.
LFT Import::2019-08-05 (2094)

Laser and forming technology - an idea and the way of implementation - Geiger, Manfred; Merklein, Marion; Pitz, Matthias (Journal of Materials Processing Technology, 2004)
This paper will give a survey of some of the actual research activities at the Chair of Manufacturing Technology in Erlangen concerning laser and forming technology. In detail the paper will deal with two main focuses of development: laser forming of aluminum alloys and laser-assisted forming of high strength steels. Laser forming is a technology often used for small series productions and for adjustment of small electronic components. In contrast to laser forming, which is a forming technology that is common for over 20 years, laser-assisted forming is an example of a new production technology that is able to enhance the forming limits of high strength steels. © 2004 Elsevier B.V. All rights reserved.
LFT Import::2019-07-16 (1028)
Keywords: Laser forming; Laser-assisted forming; Mechanical properties; Microstructure

Laser Application in Automotive Industry - Geiger, Manfred; Hoffmann, Peter; Deinzer, Günter (Proceedings of the 9th Int. Colloquium -Advanced Manufacturing and Repair Technologies in Vehicle Industries-, Balatonfüred (1992), 1992)
LFT Import::2019-08-05 (473)

Laser Applications in the Automotive Industry - Geiger, Manfred; Hoffmann, Peter; Deinzer, Günter (Laser Applications in the Automotive Industries, Proc. 25th Int. Symp. on Automotive Technology and Automation (ISATA) (1992), Croydon, England : Automotive Automation Ltd, 1992)
LFT Import::2019-08-05 (474)

Laser assisted bending and roll forming - Geiger, Manfred (Proceedings og the International Conference LANE 2004, 2004)
LFT Import::2019-08-05 (1065)

Laser assisted bending of complex-phase steel - Geiger, Manfred; Merklein, Marion; Otto, Andreas (Production Engineering - Annals of the WGP, 2004)
LFT Import::2019-08-07 (1027)

Laser assisted bending of martensite-phase steel - Pitz, Matthias; Geiger, Manfred; Merklein, Marion; Otto, Andreas (Sheet Metal 2003, Proceedings of the 9th International Conference on Sheet Metal, 2003)
LFT Import::2019-08-05 (965)

Laser assisted generation of electronic circuits on tailored thermoplastics - Eßer, Gerd; Geiger, Manfred (First International Symposium on High-Power Laser Macroprocessing Proceedings of the SPIE, 2003)
LFT Import::2019-08-05 (977)

Laser Assisted Rapid Prototyping - Processes, Applications and Developments in the Field of Additive Processes - Geiger, Manfred; Prechtl, Martin; Niebling, Frank; Otto, Andreas (Proceedings of the 4th International Conference on Industrial Tools (ICIT 2003), 2003)
LFT Import::2019-08-05 (933)

Laser assisted tooling in metal forming - Kreis, Oliver; Geiger, Manfred; Vahl, Meik (Proceedings of the 2nd International Conference on Industrial Tools (ICIT), 1999)
This article describes several applications of laser technology for tooling. Laminated tools and laser sintering as technologies for rapid tooling are presented. In the field of laser beam surface treatment, the technologies laser ablating, hardening and microstructuring are discussed. Finally, the integration of cutting and laser beam welding in the tool of a forming press is described.</
Keywords: Rapid Tooling; Laminated Tools; Laser Sintering; Laser Surface Treatment; Hydroforming; Process Integration

Laser-based microalignment for fabrication of highly precise 2D fiber collimator arrays - Stark, Markus; Eßer, Gerd; Lamott, A.; Geiger, Manfred (Photon Processing in Microelements and Phonotonics III, 2004)
LFT Import::2019-08-05 (1115)

Laser Beam Bending of Metallic Foils - Geiger, Manfred; Meyer-Pittroff, Frank (Production Engineering - Annals of the WGP, 2001)
LFT Import::2019-08-05 (910)

Laser Beam Brazing Using the Twin Spot Technology - Hanebuth, Henning; Hoffmann, Peter; Geiger, Manfred (Proceedings of the International Symposium on High Power Lasers and Laser Applications V, 1994)
LFT Import::2019-08-05 (612)

Laser Beam Cutting. - Gropp, Armin; Hutfless, Joachim; Schuberth, Stefan; Geiger, Manfred (Optical and Quantum Electronics, 1995)
LFT Import::2019-07-15 (559)

Laser Beam Cutting with Solid State Lasers and Industrial Robots - Geiger, Manfred; Gropp, A (Proc. of the 4th European Conf.on Laser Treatment of Materials (ECLAT) (1992), Göttingen, Oberursel : DGM Informationsgesellschaft, 1992)
LFT Import::2019-08-05 (372)

Laser Beam Joining of Magnesium Alloys - Klausecker, Roland; Geiger, Manfred; Otto, Andreas; Haberling, C. (LANE 2001, Proceedings of Laser Assisted Net Shape Engineering, 2001)
LFT Import::2019-08-05 (869)

Laser Beam Micro Welding as a new Interconnection Technique - Geiger, Manfred; Glasmacher, Matthias; Hutfless, Joachim; Pucher, Hans-Jörg (Proceedings of 10th European Microelectronics Conference 1995, 1995)
LFT Import::2019-08-05 (540)

Laser beam processing of aluminium foam sandwich - Klausecker, Roland; Otto, Andreas; Geiger, Manfred (Cellular Metals: Manufacture, Properties, Applications, 2003)
LFT Import::2019-07-15 (1000)

Laser Beam Soldering of Fine Pitch Technology Packages with Solid Solder Deposits. - Pucher, Hans-Jörg; Glasmacher, Matthias; Geiger, Manfred (Proceedings of the OE/LASER Optoelectronics and Lasers, 1996)
Micro electronics is a key technology attracting the attention of information, communication, automation and data processing technologies. Ongoing miniaturization combined with an increasing number of I/Os has inevitably lead to ever finer lead geometries. Therefore the demands put upon the surface mount technology are increasing continuously. Processing of high lead count fine pitch packages, for example those which are applied in high-capacity computers, has not increased the demands put upon the assembly process only, but also on the connecting techniques. By reflow soldering with laser beam radiation the benefits from the tool 'laser beam' are used extensively, for example contact and force free processing, strictly localized heating and the good controllability thereof, formation of fine crystalline and homogeneous structures, etc. Within the scope of this paper the fundamentals of laser beam soldering are discussed for fine pitch lead frames (pitch 300 micrometers ) for plastic packages, made by a modified CuFe2P alloy with a 5 micrometers Sn90Pb plating, on solid solder depths (Sn63Pb) performed by the so called High-Pad process. These investigations are unique in the field of laser beam soldering and are carried out by means of a Nd:YAG-laser. A pyrometer is used for detection of the emission of the temperature radiation of the joining area for process control. The additional use of a high-speed camera gives a detailed description of the melting and wetting process. The influence of laser beam parameters and the volume of the solid solder deposits on the joining result are presented. ©2005 Copyright SPIE - The International Society for Optical Engineering.
LFT Import::2019-08-05 (668)
Keywords: Electronics production; Fine pitch technology packages; Laser beam soldering; Reflow soldering and wetting process; Solid solder deposits

Laser Beam Welding of Magnesium Matrix Composites - Geiger, Manfred; Klausecker, Roland; Otto, Andreas (Annals of the German Academic Society for Production Engineering, 2001)
LFT Import::2019-08-05 (866)

Laser cutting of RRIM-Polyurethan components in comparison with other cutting techniques - Nuss, Rudolf; Müller, Roland; Geiger, Manfred (Lasers in Manufacturing, Proc. of the 5th Int. Conf., Berlin, 1988)
LFT Import::2019-08-05 (425)

Laser cutting of steel sheets - Geiger, Manfred; Bergmann, H.W.; Nuss, Rudolf (Laser assisted Processing - Int. Congress on Optical Science and Engineering, 1988)
LFT Import::2019-08-05 (278)

Laser Direct-Writing of AlN Substrates - Illyefalvi-Vitez, Z.; Geiger, Manfred (Proc. of the 10th ISHM, 1995)
LFT Import::2019-08-05 (568)

Laser Droplet Weld - an innovative joining technology - Geiger, Manfred; Jahrsdörfer, Bernd; Schmidt, Michael (Production Engineering - Annals of the WGP, 2003)
LFT Import::2019-08-05 (974)

Laser Droplet Weld: An Innovative Joining Technology opens new applications possibilities - Jahrsdörfer, Bernd; Eßer, Gerd; Geiger, Manfred; Govekar, E. (Proceedings of SPIE: Photon Processing in Microelectronics II, 2003)
"Laser Droplet Welding" is an innovative joining technology. The welding is realised by a laser generated liquid metal droplet which is deposited onto the parts to be joined. The raw material is a metal wire. In conventional laser welding a gap between the parts worsens the quality of the laser welded joint substantially. Contrarily a droplet offers sufficient material to bridge gaps. Even different gap sizes can be bridged by a suitable selection of the droplet size. A further advantage is the controllable heat transfer, only given by the heat content of a single drop that is sufficient to produce a high-temperature weld. The droplet heating provides the opportunity to weld small devices, thin coatings and even heat sensitive components without negative influence on their mechanical and electrical function. It is also possible to interconnect different materials by the addition of material supplied in form of drops. With the Laser Droplet Weld it is furthermore possible to join high reflective materials. This article describes the process and the system technology as well as achieved results. It will mainly focus on the droplet detachment which influences the complete process, e. g. the heat quantity or weld splashes.
LFT Import::2019-08-05 (979)
Keywords: Drops; Joining technology; Laser droplet weld; Laser welding; Welding technology

Laser Droplet Welding and its potential for joining dissimilar materials - Jahrsdörfer, Bernd; Schmidt, Michael; Geiger, Manfred (Proceedings of the LANE 2004, 2004)
LFT Import::2019-08-05 (1089)

Laser: Ein flexibles Schneidwerkzeug für die Blechbearbeitung, Teile 1 und 2 - Nuss, Rudolf; Geiger, Manfred (Blech, Rohre, Profile, 1986)
LFT Import::2019-07-12 (184)

Laser: Ein Werkzeug für die Fertigungstechnik - Geiger, Manfred; Nuss, Rudolf (Schweizer Maschinenmarkt, 1986)
LFT Import::2019-07-12 (183)

Laserformgebung von Blechen - Geiger, Manfred; Arnet, Horst; Vollertsen, Frank (SFU-Tagungsband zur Sächsischen Fachtagung Umformtechnik, 1994)
LFT Import::2019-08-05 (460)

Laser Forming - An Introduction for Manufacturing Engineering - Geiger, Manfred; Hennige, Thomas (Proceedings of the 8th International Conference on Sheet Metal, SheMet, 2000)
LFT Import::2019-08-05 (765)

Laser Forming - Geiger, Manfred; Arnet, Horst; Vollertsen, Frank (Manufacturing Systems, 1995)
LFT Import::2019-07-15 (519)

Laser Forming of Aluminium and Aluminium Alloys - Microstructural Investigation - Merklein, Marion; Hennige, Thomas; Geiger, Manfred (Proc. 7th Int. Conf. on Sheet Metal, SheMet 1999, 1999)

Laser forming of aluminium and aluminium alloys - microstructural investigations - Merklein, Marion; Hennige, Thomas; Geiger, Manfred (Journal of Materials Processing Technology, 2001)
This paper shows the microstructural development and changes in mechanical properties aluminium and aluminium alloys undergo during the process of laser forming. The resulting structures, grain structure and microstructure were analysed both quantitatively and qualitatively by optical and electron microscopy in order to examine the kind of existing structure zones and their extent. Zones with different substructures can be seen depending on the selected test parameters. The degree of substructural development seems to be a function of all influences and cannot entirely be explained by laser parameters and material characteristics. Obviously, during laser forming several different inhomogeneous particle and dislocation structures develop which are responsible for the strength of the whole composite on the one hand, and for the strength of individual small components of the whole on the other hand. Thus, hardness tests of laser-formed specimens prove the existence of different zones depending on the material and heat treatment. © 2001 Elsevier Science B.V. All rights reserved.
LFT Import::2019-07-15 (871)
Keywords: Aluminium and aluminium alloys; Hardness test; Laser forming; Microstructure; Rapid prototyping

Laser Fusion Cutting of Stainless Steel with a Pulsed Nd:YAG-Laser - Geiger, Manfred; Gropp, Armin (Welding in the World, 1993)
Recent improvements in the beam quality and output power of Nd:YAG lasers have made them more competitive as industrial tools. Two major advantages over CO2 lasers are the increase in absorbtivity of the shorter wavelength Nd:YAG light, especially when working on metals, and the possibility of using optical fibers. This report is concerned with the influence of the main process parameters on cut quality and the optimization of cut quality when cutting thin section stainless steel with an inert gas using a pulsed Nd:YAG laser.
LFT Import::2019-07-15 (398)

Lasergestützte Fertigungsverfahren - Innovationen für die Mikrotechnik von morgen - Fleckenstein, Marc; Schmidt, Michael; Geiger, Manfred (Proceedings of the 5th International Laser Marketplace 2001, 21. Juni, 2001)
LFT Import::2019-08-05 (859)

Lasergestützte Mikrofabrikationstechniken - Geiger, Manfred; Hennige, Thomas (VDI-Berichte, 2000)
LFT Import::2019-07-15 (766)

Laser Material Processing in Synergy to Metal Forming - Geiger, Manfred; Hoffmann, Peter; Hutfless, Joachim (Production Engineering (Annals of the German Academic Society for Production Engineering), 1992)
LFT Import::2019-08-05 (490)

Laser Micro Technology - A New Approach for Joining in electronics Production - Fröhlich, Thomas; Hierl, Stefan; Schmidt, Michael; Lenfert, Kai; Geiger, Manfred (MICRO.tec2000 Proceedings, 2000)
LFT Import::2019-08-05 (762)

Laseromvormen - Geiger, Manfred; Arnet, Horst; Vollertsen, Frank; Coremans, Arjan (MB Produktietechniek, 1995)
LFT Import::2019-07-15 (520)

Laser Power Stabilizing Control System For High Power CO2 Laser Welding - Deinzer, Günter; Hoffmann, Peter; Bär, W.; Geiger, Manfred (Proceedings of SPIE, 1993)
LFT Import::2019-07-15 (385)

Lasers in electronics and optics manufacturing - Research at the Bavarian Laser Center - Schmidt, Michael; Geiger, Manfred (Proceedings of the 5th International Conference Beam Technologies and Laser Applications, St. Petersburg, Russland, 2006)
LFT Import::2019-08-05 (1355)

Laserstrahlbiegen von Eisen- und NE-Legierungen - Vollertsen, Frank; Geiger, Manfred (Blech, Rohre, Profile, 1993)
LFT Import::2019-07-15 (448)

Laserstrahlhartlöten in der Automobilindustrie - Hanebuth, Henning; Hoffmann, Peter; Geiger, Manfred (Blech, Rohre, Profile, 1994)
LFT Import::2019-07-15 (613)

Laserstrahl-Mikroschweißen als alternatives Fügeverfahren zur Leadkontaktierung - Geiger, Manfred; Glasmacher, Matthias; Pucher, Hans-Jörg (Tagungsband SMT/ASIC/Hybrid 94, 1994)
LFT Import::2019-08-05 (470)

Laserstrahlschneiden faserverstärkter Kunststoffe - Müller, Roland; Biermann, Stefan; Geiger, Manfred (Laser/Optoelektronik in der Technik, 1990)
LFT Import::2019-08-05 (738)

Laserstrahlschneiden faserverstärkter Kunststoffe - Müller, Roland; Nuss, Rudolf; Biermann, Stefan; Geiger, Manfred (Laser/Optoelektronik in der Technik, 1989)
LFT Import::2019-07-15 (436)

Laserstrahlschneiden in der industriellen Praxis - Gropp, Armin; Geiger, Manfred (Blech, Rohre, Profile, 1993)
LFT Import::2019-07-15 (419)

Laserstrahlschneiden mit dem System Industrieroboter - Festkörperlaser - Geiger, Manfred; Gropp, Armin (Laser und Optoelektronik, 1993)
LFT Import::2019-07-15 (399)

Laserstrahlschneiden und -schweißen in der flexibel automatisierten Blechteilefertigung - Nuss, Rudolf; Hoffmann, Peter; Hoffmann, Martin; Geiger, Manfred (Automatisierungstechnische Praxis, 1988)
LFT Import::2019-07-15 (423)

Laserstrahlschneiden und -schweißen von Blechformteilen - Geiger, Manfred; Hoffmann, Peter (Neue Entwicklungen in der Blechumformung, 1990)
LFT Import::2019-08-05 (730)

Laserstrahlschneiden von Feinblechen, Teil 1 - Nuss, Rudolf; Geiger, Manfred (Werkstattstechnik, 1988)
LFT Import::2019-07-15 (284)

Laserstrahlschneiden von Stahlblechen - Geiger, Manfred; Gropp, Armin (METAV 90: Sonderschau Laser, 1990)
LFT Import::2019-08-05 (725)

Laserstrahlschneiden von Stahlblechen: In der Industrie bestens eingeführt. Tl. I-III. - Geiger, Manfred; Heckel, Werner (Schweizer Maschinenmarkt, 1990)
LFT Import::2019-07-15 (727)

Laserstrahlumformen räumlicher Bauteile - Geiger, Manfred; Kraus, Jürgen; Vollertsen, Frank (Bänder, Bleche, Rohre, 1994)
LFT Import::2019-07-15 (596)

Laserstrahlumformen von Aluminiumwerkstoffen - Merklein, Marion; Geiger, Manfred (Strahltechnik, 2002)
LFT Import::2019-07-16 (1719)

Laserstrahlumformen von Aluminiumwerkstoffen unter Berücksichtigung der mechanischen Eigenschaften und der Mikrostruktur - Geiger, Manfred; Merklein, Marion (Zeitschrift für Metallkunde, 2001)
LFT Import::2019-07-15 (823)

Laserstrahlumformen von räumlichen Bauteilen - Geiger, Manfred; Kraus, Jürgen; Vollertsen, Frank (Tagungsband zur VDI-Tagung Rapid Prototyping, 1994)
LFT Import::2019-08-05 (597)

Laser-supported rapid tooling - Tools for the manufacture of functional Components with Net Shape Properties. - Geiger, Manfred; Coremans, Arjan (Proceedings of the International Conference on Industrial Tools. Maribor, Slowenien, 21. - 22.04.1997, 1997)
LFT Import::2019-08-05 (716)

Lasertechniek in synergie met omvormtechnik - Coremans, Arjan; Geiger, Manfred (MB Produktietechniek, 1995)
LFT Import::2019-07-15 (513)

Lasertechnik am Lehrstuhl für Fertigungstechnologie, Universität Erlangen-Nürnberg - Geiger, Manfred; Nuss, Rudolf (Laser in der Fertigungstechnik, 1987)
LFT Import::2019-07-15 (188)

Lasertechnik in Synergie zur Umformtechnik - Geiger, Manfred; Hoffmann, Peter; Hutfless, Joachim (Blech, Rohre, Profile, 1993)
LFT Import::2019-07-15 (406)

Laserumformung von Blechen - Geiger, Manfred; Vollertsen, Frank; Arnet, Horst (SFU-Tagungsband Innovationspotential Umformtechnik, 1994)
LFT Import::2019-08-05 (607)

La técnica de conformación en la 41a Asamblea General del CIRP - Geiger, Manfred; Cser, L (Alambre, 1992)
LFT Import::2019-07-15 (363)

Leichtbau erfordert neue Prozesstechnik - Geiger, Manfred; Hennige, Thomas (Leichtbau durch Umformtechnik, 2000)
LFT Import::2019-07-15 (767)

Les techniques de formage lors de la 41ème-assemblée générale du CIRP - Geiger, Manfred; Cser, L (Le tréfilé, 1992)
LFT Import::2019-07-15 (364)

Lightweight construction by means of innovative process strategies in hydroforming technology - Geiger, Manfred; Merklein, Marion; Blankl, Andreas; Cojutti, Massimo (Steel Grips, 2007)
LFT Import::2019-07-16 (1442)

Local Energy Approach - an Advanced Model for FEM-Simulation of Multiaxial Fatigue - Hänsel, Matthias; Meßner, Arthur; Engel, Ulf; Geiger, Manfred (Localized Damage II, Vol.2: Computational Methods in Fracture Mechanics, 1992)
LFT Import::2019-07-15 (481)

Locally Optimized Tool Surfaces by Laser Treatment in Cold Forging - Wagner, Kay; Völkl, Ralf; Engel, Ulf; Geiger, Manfred; Meyer-Pittroff, Frank (Proceedings of the LANE 2007, 2007)
LFT Import::2019-08-05 (1438)

Logistics from IMS towards virtual factory - Cser, L.; Geiger, Manfred (Journal of Materials Processing Technology, 2000)
This paper shows some aspects of the design and control in logistic systems of typical processes in traditional integrated systems, IMS and virtual factories in the sheet metal industry. Main components of the virtual factory are logistics and the information technology background. By globalisation of production, factory inside logistics is replaced by a global logistic concept. In this paper those logistic concepts are summarised, which can be used in designing of material flow, optimising the parameters as well as in performance evaluation for closed loop production of sheet metal processing. The information flow, connected with the material flow, is also represented in the survey. Shared data structures and telecommunication are essential parts of the control strategy in logistic systems.
LFT Import::2019-07-15 (750)

Low Cost Lasersystem for Material Processing - Kugler, Peter; Hoffmann, Peter; Geiger, Manfred (Proceedings of the ICALEO Europe 98, 1998)
LFT Import::2019-08-05 (1608)

Macro and Micro Off-Line Programming - Geiger, Manfred; Pursche, Lars; Backes, Frank (IX. Internationales Produktionstechnisches Kolloquium Tagungsband PTK 98, 1998)
LFT Import::2019-08-05 (1629)

Magnetinduktive Prüfung der Halbzeugqualität in der Blechverarbeitung. - Geiger, Manfred; Engel, Ulf; Schwind, M. (Blech, Rohre, Profile, 1992)
LFT Import::2019-07-16 (1964)

Magnetinduktive Prüfung der Halbzeugqualität in der Blechverarbeitung - Geiger, Manfred; Engel, U; Schwind, M (Blech, Rohre, Profile, 1992)
LFT Import::2019-07-15 (369)

Manufacturing complex Sheet Metal Components by Hydroforming of Deep-Drawn Preforms - Lamprecht, Klaus; Merklein, Marion; Geiger, Manfred (Proceedings of the 24th IDDRG Congress, 20.-26.06., Besancon, France, 2005)
LFT Import::2019-08-05 (1145)

Manufacturing engineering in Erlangen University chair for manufacturing technology and university chair for automation in manufacturing and production systematology - Feldmann, Klaus; Geiger, Manfred; Kreis, Oliver; Schüßler, Florian (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2007)

Manufacturing Science Ensures Competence and Future - Geiger, Manfred; Nock, Marco (COMA 2004, Proceedings of the International Conference on Competetive Manufacturing, Stellenbisch, South Africa, 2004)
LFT Import::2019-08-05 (1045)

Marking of Silicate Glasses with Excimer Lasers Radiation - Influence of Glass Properties and Laser Parameters - Buerhop, C; Lutz, N; Weißmann, R; Geiger, Manfred (Proc. of the 4th European Conf. on Laser Treatment of Materials (ECLAT), Oberursel : DGM Informationsgesellschaft, 1992)
LFT Import::2019-08-05 (359)

Materialbearbeitung mit Hochleistungslasern - Geiger, Manfred; Christiansen, J.; Brand, H.; Bergmann, H.W. (FLE-Symposium, 1988)
LFT Import::2019-08-05 (255)

Material suited part and process design in sheet forming - Merklein, Marion; Geiger, Manfred; Vogt, Uwe (Neuere Entwicklungen in der Blechumformung: Tagungsband, Stuttgart: Werkstoff-Informationsgesellschaft, 2006)
LFT Import::2019-08-05 (1275)

Mathematical Modelling of the Flow Behaviour of Hot Stamping Steels for a FE-based Process Design - Merklein, Marion; Lechler, Jürgen; Geiger, Manfred (Tagungsband COMA'07, Südafrika, 2007)
LFT Import::2019-08-05 (1456)

Maximale bezogene Stempelkraft beim Hohl-Vorwärts-Fließpressen von Stahlwerkstoffen bei Raumtemperatur - Widmann, M.; Geiger, Manfred (Industrieanzeiger, 1978)
LFT Import::2019-07-15 (347)

Measurement of material properties of aluminium sheet alloys at elevated temperatures - Novotny, Stefan; Celeghini, Martino; Geiger, Manfred (Proceedings of the 8th International Conference on Sheet Metal, SheMet, 2000)
LFT Import::2019-08-05 (796)

Mechanical Properties and bending behaviour of metal foils - Diehl, Alexander; Engel, Ulf; Geiger, Manfred (Proceedings of the Institution of Mechanical Engineers, Part B: Journal of Engineering Manufacture, 2008)
LFT Import::2019-07-29 (1529)

Mechanical Propteries and bending behaviour of metal foils - Diehl, Alexander; Engel, Ulf; Geiger, Manfred (4M 2006, 2nd International Conference on Multi-Material Micro Manufacture, 20.-22.09.2006, Grenoble, France, 2006)
LFT Import::2019-08-05 (1323)

Medición in situ por ultrasonidos del área real contacto en el procedimiento de conformación del macizo - Geiger, Manfred; Engel, Ulf; Vollertsen, Frank (Alambre, 1993)
LFT Import::2019-07-15 (393)

Mehrlagenbeschichtungen für den beanspruchungsgerechten Einsatz bei Kaltmassivumformwerkzeugen - Schrader, Tobias; Engel, Ulf; Geiger, Manfred; Merklein, Marion (Moderne Beschichtungen zum Verschleißschutz von Werkzeugen, 2012)
LFT Import::2019-08-05 (1845)

Mesoscopic Model - Advanced Simulation of Microforming Processes - Geiger, Manfred; Geißdörfer, Stefan (AIP Conference Proceedings, 2007)
Continued miniaturization in many fields of forming technology implies the need for a better understanding of the effects occurring while scaling down from conventional macroscopic scale to microscale. At microscale, the material can no longer be regarded as a homogeneous continuum because of the presence of only a few grains in the deformation zone. This leads to a change in the material behaviour resulting among others in a large scatter of forming results. A correlation between the integral flow stress of the workpiece and the scatter of the process factors on the one hand and the mean grain size and its standard deviation on the other hand has been observed in experiments. The conventional FE-simulation of scaled down processes is not able to consider the size-effects observed such as the actual reduction of the flow stress, the increasing scatter of the process factors and a local material flow being different to that obtained in the case of macroparts. For that reason, a new simulation model has been developed taking into account all the size-effects. The present paper deals with the theoretical background of the new mesoscopic model, its characteristics like synthetic grain structure generation and the calculation of micro material properties - based on conventional material properties. The verification of the simulation model is done by carrying out various experiments with different mean grain sizes and grain structures but the same geometrical dimensions of the workpiece. © 2007 American Institute of Physics.
LFT Import::2019-07-16 (1418)
Keywords: Microforming; Simulation; Simulation of process scatter; Synthetic grain structure

Mesosopic Model - Simulative Approach to the Scatter of Process Factors in Microforming - Geißdörfer, Stefan; Engel, Ulf; Geiger, Manfred (Proceedings of the 1st Colloquium of DFG Priority Program Process Scaling, 2003)
LFT Import::2019-08-05 (991)

Meßtechnische Erfassung der Wirkflächenvorgänge in der Umformtechnik. - Geiger, Manfred; Engel, Ulf; Niederkorn, Sorin; Pfestorf, Markus (Tribologie und Schmierungstechnik, 1996)
LFT Import::2019-07-15 (641)

Mesure in situ, par les ultrasons, de la surface de contact réelle dans les procédés der formage massif - Geiger, Manfred; Engel, Ulf; Vollertsen, Frank (Le tréfilé, 1993)
LFT Import::2019-07-15 (394)

Metal Forming at the 41st CIRP General Assembly - Geiger, Manfred; Cser, L (Wire, 1992)
LFT Import::2019-07-15 (365)

Metal Forming at the 45th CIRP General Assembly. - Geiger, Manfred; Coremans, Arjan (Wire, 1996)
LFT Import::2019-07-15 (638)

Metal forming ensures innovation and future in Europe - Geiger, Manfred; Merklein, Marion; Tolazzi, Massimo (Proceedings of the 8th International Conference on TEchnology of Plasticity (ICTP), 2005)
The role of the European Union in the field of research funding is becoming more and more important for the strategic choices of the single countries of the Old Continent. The new framework programs receive increased investments and at the same time give precise the-matic areas for the possible application of research proposal. However it can be surprisingly observed that topics concerning metal forming technology have strongly lost consideration in the 6th Framework Program. Metal forming remains in fact a key technology, being es-sential for almost all the manufacturing processes and fundament of the most important aspects of our society: mobility, health, communication. The extraordinary developments of the Industrial Society in the 20th Century showed the importance and potential of a scien-tifically driven technology development, in which an idea can become an invention, be ap-plied and completely change the world in few decades. If we want to ensure our future we cannot give up innovation and research, especially in metal forming; on the contrary we should properly fund them at a public level. There are in fact many promising innovations in metal forming, which are emerging in these years and will be presented in this paper, which may become key technologies for the manufacturing of tomorrow.
LFT Import::2019-08-05 (1219)
Keywords: Funding; Innovation; Metal forming; Research

Metal Forming of Microparts for Electronics - Geiger, Manfred; Engel, Ulf; Vollertsen, Frank; Kals, Roland; Meßner, A. (Production Engineering, 1994)
LFT Import::2019-07-15 (468)

Metal forming progress since 2000 - Jeswiet, J.; Geiger, Manfred; Engel, Ulf; Kleiner, M.; Schikorra, M.; Duflou, J.; Neugebauer, R.; Bariani, P.; Bruschi, S. (CIRP Journal of Manufacturing Science and Technology, 2008)
Considerable changes have occurred in metal forming in the last decade. A record of these changes can be found in keynote papers presented by the members of the Scientific Technical Committee-Forming, at the CIRP Annual General Meeting each year. The keynote papers are excellent references on important developments in metal forming and are used as a reference, globally. Not only is this paper a compendium of most of the keynotes presented, but from 2001 onward, it has updates on new information on five keynote subject areas. The authors of each keynote have written an update with new information that has developed since the writing of the keynote. The authors of each section are shown in order of presentation. © 2008.
LFT Import::2019-07-29 (1534)
Keywords: Metal forming

Metal Forming Technology at the 44th CIRP General Assembly - Geiger, Manfred; Coremans, Arjan (Wire, 1995)
LFT Import::2019-07-15 (525)

Metallumformung mit dem Laserstrahl - eine Innovation mit Zukunft - Geiger, Manfred (Marktchance Individualisierung, 2003)
LFT Import::2019-07-16 (1008)

Metallurgical Short-Term Effects in Laser Forming of Alluminium Alloys - Merklein, Marion; Geiger, Manfred (Proceedings of the 3rd ESAFORM Conference on Material Forming, 2000)
LFT Import::2019-08-05 (790)

Micro-adjustment by thermally induced strains using laser technology - Huber, Alexander; Geiger, Manfred (Proceedings of the MICRO.tec 2000, VDE World Microtechnologies Congress, 2000)
LFT Import::2019-08-05 (780)

Microforming and investigation of parameter interactions - Eichenhüller, Bernd; Engel, Ulf; Geiger, Manfred (Production Engineering, 2010)
Microforming processes are significantly influenced by several process parameters. The research work covered in this paper investigates the interactions of some of these parameters and their impacts on the forming process. The impairment of formability and cavity filling are some typical results caused by miniaturizing the geometrical dimensions of the extruded form feature. The impact of an interaction on the forming result will be shown exemplarily with the temperature-pin diameter-interaction in more detail for a backward extrusion process. Additionally, the hardness distribution within the forming area will be investigated. © 2010 German Academic Society for Production Engineering (WGP).
LFT Import::2019-07-29 (313)
Keywords: Microforming; Production process; Size effect

Microforming - Geiger, Manfred; Kleiner, M.; Eckstein, Ralf; Tiesler, Nicolas; Engel, Ulf (Keynote Paper. Annals of the CIRP, 2001)
Microforming is a well suited technology to manufacture very small metallic parts, in particular for mass production, as they are required in many industrial products resulting from microtechnology. Compared to other manufacturing technologies microforming features specific economical and ecological advantages. Nevertheless, there are only some singular applications known until today. This paper tries to final out the reason why, analyzing systematically the problems emerging in transferring the know-how on forming from the macro- to the microworld. Reviewing the state of the art in basic and applied research reveals that scaling effects do appear not only within the process but must be taken into account in all the other areas of the whole forming system as well, demanding finally new solutions especially for tool manufacturing and machine concepts. Recent progress, innovative ideas and new developments on these sectors represent a promising basis to exploit the inherent potential of microforming in the future. © 2001 Elsevier Science Ltd. All rights reserved.
LFT Import::2019-08-05 (855)
Keywords: Equipment; Material; Micro Metal Forming

Micromachining of Ceramics with Excimer Laser Radiation - Goller, M.; Lutz, Norbert; Geiger, Manfred (Journal of the European Ceramic Society, 1993)
A XeCl excimer laser (λ = 308 nm) was used for investigating the possibilities of micromachining ceramic materials. The influence of the optical setup and laser parameters on the processing quality has been determined, as well as the behaviour of various ceramic materials during the machining process. The machining results and the structure quality are discussed concerning the shape of the holes, break-outs in the structure and the homogeneity of the hole depth and size. Optical microscopy and SEM investigations served as the main tools for the characterization. Strategies for large area micromachining were investigated to achieve a very large number of high quality microstructures. © 1993.
LFT Import::2019-07-15 (416)

Micro Production - Chances and Challenges - Geiger, Manfred; Eßer, Gerd (Proceedings of the 3rd ISPF-Seminar, 2004)
LFT Import::2019-08-05 (1104)

Microstructural Investigations of Aluminium Tailored Heat Treated Blanks - Geiger, Manfred; Merklein, Marion; Kerausch, Michael (Production Engineering. Annals of the German Academic Society for Production Engineering WGP, 2004)
LFT Import::2019-08-05 (1094)

Micro Texturing of Ceramic Tool Surfaces and its Influence on Friction in Sheet Metal Forming Processes - Geiger, Manfred; Neudecker, Thomas; Engel, Ulf (Production Engineering, 2000)
LFT Import::2019-07-15 (808)

Micro Texturing of Tool Surfaces and its Influence on Friction in Deep Drawing Processes - Neudecker, Thomas; Popp, Uwe; Engel, Ulf; Geiger, Manfred (Proceedings of the 8th International Conference on Sheet Metal, 2000)
LFT Import::2019-08-07 (794)

Micro Texturing of Tool Surfaces and its Influence on Friction in Forming Processes - Neudecker, Thomas; Popp, Uwe; Engel, Ulf; Geiger, Manfred (X. International Colloquium on Surfaces, 2000)
LFT Import::2019-08-05 (793)

Mikrobiegen und Präzisionsrichten mit gepulster UV-Laserstrahlung. - Geiger, Manfred; Becker, Wolfgang; Vollertsen, Frank (Laser und Optoelektronik, 1997)
LFT Import::2019-07-15 (714)

Mikrooptiken für die effiziente Materialbearbeitung mit Excimerlasern. - Hutfless, Joachim; Rebhan, Thomas; Lutz, Norbert; Geiger, Manfred; Frank, M.; Streibl, N.; Schwinder, J. (Laser und Optoelektronik, 1994)
LFT Import::2019-07-15 (619)

Mikroproduktion? Chancen und Herausforderung - Geiger, Manfred; Geißdörfer, Stefan (22. ASK, Aachener Stahlkolloquium, 2007)
LFT Import::2019-08-05 (1419)

Mikroproduktionstechnik: Chance und Herausforderung für die Lasertechnik - Geiger, Manfred; Eßer, Gerd (Tagungsband Stuttgarter Lasertage 2003, 2003)
LFT Import::2019-08-05 (987)

Mikroproduktionstechnik: Minibauteile mit Größe - Geiger, Manfred; Eßer, Gerd (Zukunft im Brennpunkt, 2003)
LFT Import::2019-07-15 (982)

Modeling of Process-Tool-Machine Interactions in Cold Forging - Kroiß, Thomas; Völkl, Ralf; Engel, Ulf; Geiger, Manfred (Proc. 1st Int. Conf. on Process Machine Interactions (PMI), 2008)
LFT Import::2019-08-05 (496)

Modellierung und Simulation der Warmblechumformung: Aktueller Stand und zukünftiger Forschungsbedarf - Brosius, A.; Karbasian, H.; Tekkaya, A.E.; Lechler, Jürgen; Merklein, Marion; Geiger, Manfred; Springer, R.; Schaper, M.; Bach, F.W.; Hoffmann, H. (Tagungsband 2. Erlanger Workshop Warmblechumformung, 2007)
LFT Import::2019-08-05 (1499)

Modellierung von Aktoren für das Laserstrahljustieren in der Mikrotechnik - Geiger, Manfred; Wurm, Thomas; Hagenah, Hinnerk (Fortschritte in der Simulationstechnik, Tagungsband des 17. Symposiums Simulationstechnik ASIM 2003, 2003)
LFT Import::2019-08-05 (943)

Modelling of a Flexbile Tube Bending Technology Using an Elastomere Tool - Nock, Marco; Geiger, Manfred (COMA 2004, Proceedings of the International Conference on Competetive Manufacturing, Stellenbisch, South Africa, 2004)
LFT Import::2019-08-05 (1046)

Modelling of Laser BEam Forming of Large Sheet Metal Parts - Pitz, Indra; Otto, Andreas; Geiger, Manfred (Proceedings of the LANE 2007, 2007)
LFT Import::2019-08-05 (1436)

Modelling of Laser Beam Welding at 3D Workpiece Contours. - Otto, Andreas; Backes, Frank; Geiger, Manfred (Proceedings of the 6th European Conference on Laser Treatment of Materials, ECLAT 96, 1996)
LFT Import::2019-08-05 (664)

Modell zur Vorhersage des Werkstoffversagens durch Bruch und Verschleiß - Geiger, Manfred; Engel, U; Sobis, T; Hänsel, M (PSU: Bericht zum Workshop des Gemeinschaftsprojekts Prozeßsimulation in der Umformtechnik PSU, 1991)
LFT Import::2019-08-05 (237)

Moderne Alternativen in der Blechbearbeitung - Geiger, Manfred; Wissmeier, H. J (Werkstattstechnik, 1982)
LFT Import::2019-07-12 (173)

Moderne Blechumformung - Offen für neue fachübergreifende Denkansätze - Geiger, Manfred; Coremans, Arjan (Blech, Rohre, Profile, 1995)
LFT Import::2019-07-15 (526)

Modification of Ceramic Surfaces by Excimer Laser Processing - Becker, Wolfgang; Hutfless, Joachim; Geiger, Manfred (Cleo/Europe 94 Conference Proceedings, 1994)
Excimer laser radiation was found to be applicable in modifying ceramic surfaces. This technique proves to be novel, flexible and effective alternative to traditional modes of surface finishing of ceramics with costly diamond equipment. In this study, a XeCl excimer laser was applied to smooth alumina and silicon carbide ceramics. Basic testings were carried out to obtain data with regard to interaction mechanisms and to determine the optical processing parameters. Meanwhile, strength and wear experiments are designated to characterize the mechanical and tribological features of the processed surfaces.
LFT Import::2019-08-05 (631)

MoS2-Alloyed Steel for Wear-Loaded Parts - Vollertsen, Frank; Geiger, Manfred (Proc. of PM´94 World Congress, Editions de Physique I, Paris, 1994)
LFT Import::2019-07-15 (626)

Multi-Objective Optimization of Actuator System Design for Laser Micro Adjustment - Geiger, Manfred; Plettke, Raoul; Hagenah, Hinnerk (Production Engineering, 2009)
Complex design processes require a high level of expertise and are time consuming. By assisting the engineer with a computer aided design system the design process can be accelerated and be made more reliable. Actuator system design for laser micro adjustment is complex and its challenges may be a hindrance for the application of laser micro adjustment. To overcome this obstacle a computer aided design system was developed which utilizes a multi-objective optimization algorithm to automatically improve actuator design. In this paper, the system and its components are presented. A special focus will be upon the assessment functions which allow the efficient assessment of an actuator design. An application example will be given to demonstrate the functionality of the design system. © German Academic Society for Production Engineering (WGP) 2008.
LFT Import::2019-07-29 (147)
Keywords: Computer aided design; Laser micro adjustment; Multi-objective optimization

Näherungsrechnung zur Ermittlung des Spannungs- und Bewegungszustands beim Fließen eines starrplastischen Werkstoffes - Geiger, Manfred; Steck, E (Industrieanzeiger, 1967)
LFT Import::2019-07-12 (168)

Nanotopography characterisation in microforming - Weidel, Stephan; Engel, Ulf; Geiger, Manfred (Proceedings of the 7th International Conference of the European Society for Precision Engineering and Nanotechnology Euspen, Bremen, 2007)
In microforming applications the contact state between the tool and a lubricated workpiece differs significantly from that of a forming process in conventional length scale. The drastic reduction of the lateral dimensions of the workpiece surfaces in microforming, while there is no change in surface roughness, causes a significant reduction of the number of asperities contacting the tool. Therefore, the influence of single asperities on the tribological behaviour of the surface increases. Thus, the assumption that a complete flattening of the regions on top of the asperities contacting the tool takes place during forming can not be maintained. Instead, the socalled nanotopography on top of the flattened asperities has to be investigated. The relationship between these contact regions, the lubricant and the impact on the tribological behaviour has not been analysed yet. In this paper the flattening behaviour of single idealised asperities is analysed. A test rig for surface flattening is introduced, which enables the in-situ observation of the developing contact area with a translucent tool, a telecentric objective and a CCDcamera. Upsetting tests are performed with and without lubricant. The nanotopography and its behaviour during flattening is characterised by confocal microscopy and scanning probe microscopy.
LFT Import::2019-08-05 (1404)

Near-Field 3D Position Sensing using Optical Fibers - Geiger, Manfred; Hohenstein, Ralph (Production Engineering Research and Development - Annals of the German Academic Society for Production Engineering, 2008)
LFT Import::2019-08-05 (1525)

Neue Entwicklungen bei IHU von Blechen und deren Einsatzpotenziale für Leichtbauteile - Geiger, Manfred; Merklein, Marion; Celeghini, Martino; Novotny, Stefan; Vahl, Meik (Innenhochdruck-Umformen für Karosseriekomponenten, 2002)
LFT Import::2019-07-16 (1706)

Neue Entwicklungen in der Umformtechnik - Fachdokumentation des Fortschritts - Lange, K; Geiger, Manfred (Industrieanzeiger, 1968)
LFT Import::2019-07-12 (167)

Neue Erkenntnisse zum Laserstrahlschneiden: Durch Experimente zu höherer Flexibilität - Geiger, Manfred; Heckel, Werner; Biermann, Stefan (Schweizer Maschinenmarkt, 1990)
LFT Import::2019-07-15 (728)

Neue Ideen zum Innenhochdruckumformen. - Geiger, Manfred; Hein, Philipp (Blech, Rohre, Profile, 1996)
LFT Import::2019-07-15 (643)

Neue Konzepte zur überwachung und Regelung von Laserstrahlschweißprozessen - Otto, Andreas; Geiger, Manfred; Hohenstein, Ralph (4. Laseranwenderforum 2002, 2002)
LFT Import::2019-08-05 (1699)

Neuere Entwicklungen im Bereich der Massivumformung - Geiger, R.; Geiger, Manfred (Draht, 1977)
LFT Import::2019-07-15 (340)

Neuere Möglichkeiten zur Auslegung vorgespannter Fließpreßmatrizen - Geiger, Manfred; Lange, K. (Draht, 1978)
LFT Import::2019-07-15 (345)

Neue Technologien in der Blechbearbeitung - Geiger, Manfred; Hoffmann, M (Tisza, M: Kardos, K: Proc. 5th Int. Conf. on Metal Forming (ICMF 91), 1991)
LFT Import::2019-08-05 (242)

Neue Wege der Innenhochdruckumformung. Innenhochdruckumformen, eine Alternative in der Fertigungstechnik. - Geiger, Manfred; Vollertsen, Frank; Hein, Philipp (EFB Kolloquium Stuttgart, 1996)
LFT Import::2019-08-05 (657)

Neural Networks in Metal Forming. - Geiger, Manfred; Cser, L.; Lenard, J.; Farkas, K.; Backes, Frank; Hwu, Y. (Preprints of the Second International Work- shop on Learning in Intelligent Manufacturing Systems LIMS, 1995)
LFT Import::2019-08-05 (530)

Neural Networks Matching Contours in CAD Models - Wilke, Peter; Greska, Wolfgang; Geiger, Manfred; Berentz, Jörg (1994)

Neuronale Netze in der Blechumformung - Backes, F.; Geiger, Manfred; Lenard, J.; Cser, L. (Blech, Rohre, Profile, 1995)
LFT Import::2019-07-15 (512)

Neuronale Netze zur Konturanalyse in CAD-Modellen - Greska, Wolfgang; Wilke, Peter; Geiger, Manfred; Berentz, Jörg (Zeitschrift für Wirtschaftliche Fertigung und Automatisierung, 1994)

New developments and perspectives of forming technology at the LFT - Geiger, Manfred; Merklein, Marion; Celeghini, Martino; Eckstein, Ralf; Novotny, Stefan (Proceedings of the 10th International Conference on Sheet Metal, SheMet 2003, 14.-16.04., Jordanstown, 2003)
LFT Import::2019-08-05 (957)

New Developments for the Qualification of Technical Surfaces in Forming Processes - Geiger, Manfred; Engel, Ulf; Pfestorf, Markus (CIRP Annals - Manufacturing Technology, 1997)
In modern sheet metal forming, blank topographies are characterized by various quite different and rather sophisticated structures. This is due to the various deterministic or semi-deterministic methods of surface texturing produced by skinpass rolling. The conventional surface parameters determined from profile data are not capable of characterizing such surfaces, in particular with respect to their functional behavior. Thus, there is a strong demand for the development of new parameters which can only be determined via the measurement of area. With special respect to the application of deterministically textured topographies in metal forming, appropriate 3d surface parameters can be derived from the mechanical rheological model recently developed at the Institute of Manufacturing Technology. These are the maximum ratio of closed void area and the closed void volume, both of which result from a special evaluation of the bearing ratio curves. Industrial applications show that these parameters can be related to the functionality of the surface and hence may be regarded as very suitable for the characterization and qualification of complex surface structures.
LFT Import::2019-07-16 (1989)
Keywords: Forming; Rolling; Topography

New Technologies in sheet metal forming for light-weight construction. - Geiger, Manfred; Müller, Burkhard (Proc. of the 4th Int. Conf. on Sheet Metal, Twente : University of Twente, 1996)
LFT Import::2019-08-05 (651)

New Tribological Aspects of Dry Film Lubricated Aluminium Sheet Metal - Pfestorf, Markus; Meiler, M.; Merklein, Marion; Geiger, Manfred (Proceedings of the 4th International Conference THE coatings in Manufacturing Engineering, 2004)
LFT Import::2019-08-05 (1096)

Nonlinear and Stochastic Analysis and Modelling of Laser Beam Melt Ablation as an Approach to Online Process Diagnostics and Control Strategy - Cser, Adrienn Orsolya; Otto, Andreas; Geiger, Manfred (Proceedings of the 4th LANE 2004, 2004)
LFT Import::2019-08-05 (1078)

Nonlinear Dynamics Durin Laser Beam Welding. - Otto, Andreas; Geisel, Mark; Geiger, Manfred (Proc. of the 15th Int. Congress on Application of Laser and Electro-Optics, ICALEO 96, 1996)
LFT Import::2019-08-05 (666)

Novel adaptive control for air bending of sheet metals. - Geiger, Manfred; Breitenbach, F.; Schmidt, Michael (Production engineering, 1997)

Novel concept of experimental setup for characterisation of plastic yielding of sheet metal at elevated temperatures - Geiger, Manfred; van der Heyd, Gerhard; Merklein, Marion; Hußnätter, Wolfgang (Advanced Materials Research, 2005)
In times of highest significance of process modelling and numerical simulation characterisation of material properties is of special importance for tools' and components' dimensioning. But in general material properties depend on many different influencing variables, e.g. temperature, humidity and many others. Especially in fields of sheet metal forming the mechanical behaviour of components highly differs according to real stress condition. In particular yield loci combine the information of beginning of yielding with a biaxial stress condition, but nevertheless for many materials they have not been determined yet. For all others the existing values are available only at room temperature. In this paper a novel concept of the experimental setup is shown, with which plastic yielding of sheet metal can be examined also at elevated temperatures. In usual biaxial tension tests cruciform specimen are drawn in plane. The new machine-concept, which is presented in this paper, is based on a punch-load moving perpendicular to the sheet. By clamping the specimen restoring forces are induced, which cause in dependence of special developed tool and work piece geometries defined stress conditions. Using an optical measurement system for determination of strains with CCDcameras of very high frame rate allows exact identification of starting plastification by offline analysis. Experiments at elevated temperatures are realised by local heating with a diode laser and a special optical system to reach a homogenous distribution of temperatures in the forming zone. On the one hand these investigations are necessary for many materials to achieve further information on characteristic properties in warm forming, because their data are only known at room temperature. On the other hand some materials, e.g. magnesium wrought alloys, are mostly formed at elevated temperatures (here in the range of 200°C to 250°C), because of its significant higher formability. Thus, material behaviour must be characterised at these temperatures.
LFT Import::2019-07-16 (1135)
Keywords: Material characterisation; Sheet metal forming; System technology

Novel technique for high-quality microstructuring with excimer lasers - Roth, Stephan; Geiger, Manfred (Proceedings of SPIE, 2000)
Laser micromachining has become increasingly established in many microsystems applications during the past years. These new fields occasion higher demands on the quality of micromachined devices combined with high resolution and working velocity. Due to the disadvantages of conventional excimer laser processing, a novel technique is required to meet these demands. The main problems of conventional excimer laser machining are the redeposition of ablated material on the irradiated work piece and the formation of a strong melting phase especially for metals. These difficulties greatly reduce the applicability of excimer laser material processing for manufacturing microsystems technology components. By applying a thin water film to the substrate surface, the redeposition of ablated material can be completely avoided, which results in a better quality of the microstructures. Usage of a water film, however, has proved to lead to a marked reduction of the ablation rate for the examined materials - ceramics and stainless steel. Therefore, one of the objectives of future research will be to raise the ablation rate in order to render excimer laser processing more interesting economically. Adding alcoholic additives, among others, has improved the wetting of the liquid films on the surface. The effect of the modified chemical composition of the liquid on ablation rate and structure quality for various materials is presented here.
LFT Import::2019-07-15 (799)

Numerical simulation to improve robustness in sheet metal forming process chains - Hagenah, Hinnerk; Geiger, Manfred; Merklein, Marion (AIP Conference Proceedings, 2013)
The paper will present developments towards the improvement of the robustness of sheet metal forming process chains. The possibilities and challenges will be demonstrated using two examples. Firstly, the effect of heat treatment to precipitation hardened aluminum sheet metals in order to enlarge the process window for deep drawing operations will be discussed. Numerical simulation can be used to predict the effects of the heat treatment. Using more sophisticated approaches the heat treatment layout and its effects on the forming process can be computed and predicted. Thus the process window can be enlarged and in consequence the process chain will receive an increased robustness. Secondly the integrated tube and sheet hydroforming process that also includes joining operation will be used as an example of the positive impact numerical simulation can have on complex process chains. This highly integrated process chains needs carefully designed tools that ensure robust production. Furthermore, several effects occurring during the forming operations are difficult to understand since the process cannot be stopped at arbitrary moments or easily investigated in situ. The needed understanding and therefor the mandatory input for successful and robust process design has to be derived from advanced numerical models and the according simulation runs. © 2013 AIP Publishing LLC.
LFT Import::2019-07-29 (1899)
Keywords: Robust process chains; sheet hydroforming; tailored heat treatment

Numerische Simulation der Verschleißvorgänge in der Umformtechnik - Sobis, Tomasz; Engel, Ulf; Geiger, Manfred (Berichtsband der DGM zum Symposium -Reibung und Verschleiß- Bad Neuheim, 29.-30.Okt.1992 (1993), Oberursel : DGM-Informationsgesellschaft, 1992)
LFT Import::2019-08-05 (488)

Oberflächenausbildung keramischer Bauteile nach einer Endbearbeitung mit Excimerlaserstrahlung. - Geiger, Manfred; Becker, Wolfgang (Tagungsband der Werkstoffwoche 96, Symposium 5, Werkstoffe für die Fertigungstechnik, 1996)
LFT Import::2019-08-05 (635)

On-Line Diagnostic System for the Quality of High Power CO2 Laser Optics - Geiger, Manfred; Hutfless, Joachim (Proc. of GCL 92, 9th Int. Symp. on Gas Flow and Chemical Lasers, Heraklion, Kreta, 1992)
LFT Import::2019-08-05 (476)

On the Way to Real-time Simulation of Incremental Laser Beam Bending - Komlodi, Attila; Otto, Andreas; Geiger, Manfred (Laser Assisted Net shape Engineering 4 - Proceedings of the LANE 2004, 21.-25. September 2004, Erlangen, Germany, 2004)
LFT Import::2019-08-05 (1091)

Optical properties of plastics and their role for the modelling of the laser transmission welding process - Geiger, Manfred; Frick, T.; Schmidt, Michael (Production Engineering, 2009)
Laser transmission welding of plastics is a joining technique which permits the welding of plastic parts with low process inherent thermal and mechanical stresses. In order to compute the temperature fields during the welding process a simulation model of the process is established. Especially the optical and thermal properties of the welded materials are necessary as input parameters in order to model the process properly. While the thermal properties of polymers are well-investigated, there is little knowledge about the optical properties of plastics. The optical properties of different amorphous and semi-crystalline thermoplastics are therefore investigated in dependence on material temperature and additive concentration. Based on these data it is possible to analytically describe the absorption of laser energy in plastics. The computation of temperature fields during welding is carried out for polypropylene and the results are then compared with experimentally accomplished welding tests. The calculated results show good accordance with the experimentally determined melt pool geometries of welded specimens and prove the compatibility of the computation model with the experimental analysis. © German Academic Society for Production Engineering (WGP) 2008.
Created from Fastlane, Scopus look-up
Keywords: Laser transmission welding; Process modelling; Production process

Optimierte Produktqualität und Werkzeuglebensdauer durch stochastische Simulation - Geiger, Manfred; Engel, Ulf; Völkl, Ralf (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2003)
LFT Import::2019-07-15 (964)

Optimierungsstrategien zur Verbesserung der Lebensdauer von Umformwerkzeugen - Geiger, Manfred; Hänsel, Matthias; Sobis, Tomasz; Engel, Ulf (Prozeßsimulation in der Umformtechnik, 1993)
LFT Import::2019-07-15 (400)

Optimisation of Specimen's Geometry for Characerisation of Plastic Yielding - Geiger, Manfred; Merklein, Marion; Hußnätter, Wolfgang (Proceedings of the 8th ESAFORM Conference on material forming, 2005)
LFT Import::2019-08-05 (1170)

Optimizing Laser Forming by FEM-Simulation - Geiger, Manfred; Holzer, Stefan; Vollertsen, Frank (Annals of the German Academic Society for Production Engineering, 1995)
LFT Import::2019-08-05 (545)

Optimizing Systems for Laser Beam Welding. - Deinzer, Günter; Otto, Andreas; Hoffmann, Peter; Geiger, Manfred (Proceedings of the CIRP, 1995)
LFT Import::2019-08-05 (515)

Path Planning for a Kinematic Section Bending Process. - Geiger, Manfred; Arnet, Horst; Vollertsen, Frank (Production Engineering, 1997)
LFT Import::2019-07-15 (712)

Patterning of Circuitry on Tree-Dimensional Molded Interconnected Devices Using Focused Laser Radiation - Geiger, Manfred; Roth, Stephan; Eßer, Gerd (Production Engineering, 1998)
LFT Import::2019-07-16 (1595)

Physical and Numerical Modelling of the Buckling Mechanism. - Holzer, Stefan; Arnet, Horst; Geiger, Manfred (Manufacturing Systems, 1995)
LFT Import::2019-07-15 (566)

Physical modeling of surface asperities - the impact of liquid lubricant on the real contact area - Weidel, Stephan; Engel, Ulf; Geiger, Manfred (Proceedings of the 9th International Conference on Technology of Plasticity ICTP, 2008)
LFT Import::2019-08-05 (1539)

Planning and Control of Laser Forming Applications - Hagenah, Hinnerk; Plettke, Raoul; Geiger, Manfred (Proceedings of the 39th CIRP International Seminar on Manufacturing Systems, 2006)
LFT Import::2019-08-05 (138)

Planning of Handling Operations for Complex Bending Parts - Geiger, Manfred; Vormann, Bodo (Production Engineering, 1995)
LFT Import::2019-07-15 (558)

Planungssystem für das Handhaben komplexer Blechbiegeteile - Geiger, Manfred; Vormann, Bodo (Bänder, Bleche, Rohre, 1994)
LFT Import::2019-07-15 (608)

Post-Treatment of Direct Metal Laser Sintered Parts by Infiltration Process - Dueck, J.; Niebling, Frank; Neeße, T.; Geiger, Manfred (Space Challenge in the 21st Century, 2003)
LFT Import::2019-07-15 (967)

Potential der Laserstrahlbearbeitung zur - Geiger, Manfred; Becker, Wolfgang; Pohl, M.; Schaus, M. (Tagungsband der Werkstoffwoche 96, Symposium 5, Werkstoffe für die Fertigungstechnik (1997), 1996)
LFT Import::2019-08-05 (669)

Präzisionslaserstrahlfertigungstechnik für den Maschinenbau - Geiger, Manfred; Hoffmann, Peter (Berichtsband zum FORLAS-Berichtskolloquium am 28.6.1995 in Erlangen, 1995)
LFT Import::2019-08-05 (511)

Präzisionslaserstrahlfertigungstechnik für den Maschinenbau. - Geiger, Manfred; Reinhart, G.; Hoffmann, Peter; Schultz, Markus (Abschlußbericht zum Bayerischen Forschungsverbund Lasertechnik FORLAS., 1997)
LFT Import::2019-08-05 (680)

Precise Cutting of critical Contour Elements - Geiger, Manfred; Biermann, Stefan; Nuss, Rudolf; Hoffmann, Peter (Conf. on Lasers and Electro-Optics (CLEO 89), 1989)
LFT Import::2019-08-05 (429)

Precise cutting of Sheet Metal with CO2- Laser - Nuss, Rudolf; Biermann, S; Geiger, Manfred (Sheet metal tubes section, 1987)
LFT Import::2019-07-15 (191)

Precision Machining of Ceramics with XeCl Excimer Laser Radiation - Geiger, Manfred; Lutz, Norbert (Production Engineering - Annals of the WGP, 1994)
LFT Import::2019-08-05 (599)

Precision of P/M-Parts a System Property - Vollertsen, Frank; Geiger, Manfred (Powder Metallurgy Int. 22, 1990)
It is necessary for determination of the precision of P/M parts to consider the whole system consisting of powder, the compaction press, and sintering furnace. All system parameters such as composition variations, scatter in compaction force and deviations from sintering time and temperature contribute to the final scatter in length, i.e., to dimensional accuracy. It is shown that the green density and the amount of liquid phase are the main factors determining dimensional accuracy after liquid phase sintering. The shape accuracy is primarily determined by friction forces during compaction and sintering and by the slumping effect. It is easier to control dimensional behaviour than the shape of a sintered part. A method is presented to calculate the dimensional accuracy from experimental data in order to find the critical parameters of a given system.
LFT Import::2019-08-05 (740)

Prediction of Service Life and Failure Probability o Cold Forging Tools - Geiger, Manfred; Falk, Bernd (CIRP Annals - Manufacturing Technology, 2001)
LFT Import::2019-07-15 (863)

Prediction of Tool Failure from a Probabilistic Point of View. In: Journal of Materials Processing Technology - Engel, U; Geiger, Manfred (Proc. of the Int. Conf. on Cold and Warm Forging Technology, Okt. 1992, Columbus, Ohio, USA, 1992)
LFT Import::2019-08-05 (361)

Proceedings of ceramics with excimer lasers - Lutz, Norbert; Geiger, Manfred (Proceedings of the 3rd European Conference on Laser Treatment of Materials (ECLAT), Erlangen, 1990)
LFT Import::2019-08-05 (737)

Process Chain towards Laminated Object Manufacturing with Metal Foil - Prechtl, Martin; Otto, Andreas; Geiger, Manfred; Graf, D. (LANE 2004, Proceedings of the 4th International Conference on Laser Assisted Net Shape Engineering, 2004)
LFT Import::2019-08-05 (1053)

Process Control in Laser Beam Cutting and Welding of Car Body Sheets Using a Five-Axes - Geiger, Manfred; Deinzer, Günter; Hoffmann, Peter; Biermann, Stefan (Proceedings of the 32nd International Symposium on Automotive Technology and Automation : ISATA´99 : Automotive Mechatronics Design & Engineering, Croydon, England, 1990)
LFT Import::2019-08-05 (505)

Process Design for Hydroforming of Lightweight Metal Sheets at Elevated Temperatures - Novotny, Stefan; Geiger, Manfred (Journal of Materials Processing Technology, 2003)
Lightweight materials like aluminium and magnesium alloys offer a high potential for weight reduction in automotive and other transportation vehicle construction. The high alloy percentages in aluminium alloys and the hexagonal structure of magnesium, however, lead to a relatively low formability of the sheet materials which can be enhanced by conducting the forming processes at elevated temperatures up to the recrystallisation temperature. This strategy is commonly used in rolling and forging, but still rises problems in sheet forming. In a research project at the chair of manufacturing technology the process of hydroforming of aluminium and magnesium sheet material shall be enhanced to be conducted at elevated temperatures. Based on material tests to determine the behaviour of different aluminium and magnesium alloys at elevated temperatures, appropriate hydroforming strategies for these materials have to be developed. Laboratory systems for the uniaxial tension test, the free hydraulic bulging of sheet material and for strip drawing, all at elevated temperatures, were built up and used as models for the design of a production system for hydroforming with a warm pressure fluid. The tests were also simulated with an FEM-system to show the restrictions and the potentials of simulation tools for this production strategy, aiming at the subsequent simulation of the complete hydroforming process. © 2003 Elsevier Science B.V. All rights reserved.
LFT Import::2019-07-15 (926)
Keywords: Aluminium; Elevated temperature; FEM simulation; Hydroforming; Lightweight construction; Magnesium

Process design for hydroforming of sheet metal pairs using a closed loop controlled finite element simulation - Kohlbauer, Rainer; Hagenah, Hinnerk; Geiger, Manfred (Proceedings of the 10th International Conference on Sheet Metal, SheMet 2003, 2003)
LFT Import::2019-08-05 (928)

Processing of Aluminium Foam for Lightweight Construction - Geiger, Manfred; Hahn, Markus (Production Engineering, 2003)
LFT Import::2019-07-15 (962)

Processing of Aluminium Foam Sandwich Tailored Blanks - Dörfler, Stephan Manuel; Otto, Andreas; Merklein, Marion; Geiger, Manfred (Proceedings of the Advanced Metallic Materials, 2003)
LFT Import::2019-08-05 (966)

Processing of Aluminium Foam Tailored Blanks - Dörfler, Stephan Manuel; Otto, Andreas; Geiger, Manfred (Cellular Metals - Manufacture, Properties, Applications, 2003)
LFT Import::2019-07-15 (959)

Processing of Compounds and Silica-Layers with an Excimer-Laser-Processing Centre - Geiger, Manfred; Rebhan, Thomas; Lutz, Norbert; Hutfless, Joachim (Proceedings of the EUREKA 205 International Workshop Excimer Laser Applications, 1993)
LFT Import::2019-08-05 (413)

Process Integration by Hydroforming, Cutting and Laser Beam Welding in One Single Tool - Geiger, Manfred; Kreis, Oliver (Production Engineering, 2003)
LFT Import::2019-07-15 (954)

Process-machine interactions in cold forging – calculation of press / tooling stiffness and its integration into FE process simulation - Kroiß, T.; Völkl, Ralf; Engel, Ulf; Geiger, Manfred (Proc. of the 9th International Conference on Technology of Plasticity (ICTP), 2008)
In this paper a new approach for the calculation of the axial stiffness for the complete system consisting of stroke-controlled press and tooling system in combination with an axially symmetric cold forging process is presented. Two stroke-controlled presses, one with a C-frame, the other in a stiff 4-columns design, were examined both showing a nearly linear behavior. The analyzed example process is full forward extrusion. The stiffness is determined indirectly using the evolution of the workpiece length depending on the actual punch stroke that changes due to the forming load and the resulting deflection. For the stiffness calculation experiments and a FE simulation of the example process are applied. The calculated stiffness was integrated into FE process simulation using a spring element. The comparison between experimental and simulation results shows a very good agreement.
LFT Import::2019-08-05 (497)

Process Modelling of Laser Ablation Ferrous Materials - Schubart, Doris; Vollertsen, Frank; Kauf, Michael; Geiger, Manfred (Proc. of the EuroLaser Academy, 1995)
LFT Import::2019-08-05 (575)

Process Optimizing Adaptive Optics for the Beam Delivery of High Power CO2 Lasers - Hoffmann, Peter; Schuberth, Stefan; Geiger, Manfred (Proc. of the Conf. OE/Technology 92, Nr. 1834, 1992)
LFT Import::2019-08-05 (484)

Process Optimizing CO2-Laser Beam Welding Using Adaptive Optics - Geiger, Manfred; Schuberth, Stefan; Hoffmann, Peter; Hutfless, Joachim (CO2-Laser Beam Welding Using Adaptive Optics, 1994)
LFT Import::2019-07-15 (603)

Process-Oriented Adaptation of Laser Beam Brazing to Production Techniques - Geiger, Manfred; Hanebuth, Henning; Hoffmann, Peter (Production Engineering, 1995)
LFT Import::2019-07-15 (543)

Process parameters optimisation in sheet hydroforming - Tolazzi, Massimo; Geiger, Manfred (Innovation in Metal Forming, 2004)
LFT Import::2019-07-16 (1077)

Process Strategies for Sheet Metal Hydroforming of Lightweight Components - Geiger, Manfred; Vahl, Meik; Novotny, Stefan; Bobbert, S. (Proceedings of the Institution of Mechanical Engineers, Part B: Journal of Engineering Manufacture, 2001)
LFT Import::2019-07-15 (832)
Keywords: Aluminium; Elevated temperature; Finite element simulation; Hydroforming; Magnesium; Process control; Sheet metal forming

Production of Microparts by Cold and Warm Forming - Engel, Ulf; Egerer, Emil; Geiger, Manfred (Proceedings of the CIRP Seminar on Micro and Nano Technology, 2003)
LFT Import::2019-08-05 (941)

Production of microparts - size effects in bulk metal Forming, similarity theory. - Geiger, Manfred; Meßner, Arthur; Engel, Ulf (Production Engineering, 1996)
LFT Import::2019-07-15 (650)

Profilbiegen mit Polyurethanmatrize - Prozeßführung und Formgebungsmöglichkeiten. - Geiger, Manfred; Arnet, Horst; Vollertsen, Frank (Blech, Rohre, Profile, 1996)
LFT Import::2019-07-15 (634)

Prozessangepasste Lösungen für den Einsatz von Leichtbauwerkstoffen in der Blechumformung - Celeghini, Martino; Kerausch, Michael; Kreis, Oliver; Merklein, Marion; Geiger, Manfred (Robuste, verkürzte Prozessketten für flächige Leichtbauteile. Tagungsband zum Industriekolloquium 2003 des SFB 396, Erlangen, 15.-16.10, 2003)
LFT Import::2019-08-05 (960)

Prozessgeregelte Mikrobearbeitung mit Laserstrahlung in der Elektronikproduktion - Geiger, Manfred; Otto, Andreas; Fleckenstein, Marc; Mys, I.; Schmidt, Michael (Produktionssysteme in der Elektronik - Sonderforschungsbereich 356 - Bericht des Forschungsverbundes 1999 - 2001, 2001)
LFT Import::2019-08-05 (867)

Prozessgrundlagen für die Halbwarmumformung - Neugebauer, R.; Geiger, Manfred; Hartwig, H.; Bitter, Stefan (Tagungsband der Konferenz Neue Entwicklung in der Massivumformung, 2003)
LFT Import::2019-08-05 (953)

Prozeßinnovationen durch den Einsatz prozeßoptimierender Optiken - Geiger, Manfred; Hoffmann, Peter; Schuberth, Stefan (Bericht zum Laser 93 -Fachseminar Prozeßoptimierende adaptive Optiken, 1993)
LFT Import::2019-08-05 (407)

Prozesskettenverkürzung in der Blechumformung - Merklein, Marion; Geiger, Manfred; Blankl, Andreas; Cojutti, Massimo; Vogt, Uwe (Robuste, verkürzte Prozessketten für flächige Leichtbauteile. Tagungsband zum Industriekolloquium des SFB 396, 2006)
LFT Import::2019-08-05 (1283)

Pulvermetallurgische Herstellung und Eigenschaften verschleißfester Bauteile - Vollertsen, Frank; Engel, Ulf; Leithner, K.; Geiger, Manfred; Geiger, R. (Metall, 1989)
LFT Import::2019-07-15 (441)

Qualität des Laserschnitts - Biermann, Stefan; Nuss, Rudolf; Geiger, Manfred (Maschinenmarkt, 1988)
LFT Import::2019-07-15 (268)

Qualitätssicherung in der Blechberarbeitung - magnetinduktive Überwachung der mechanischen Blechkennwerte - Schwind, Michael; Engel, Ulf; Geiger, Manfred (Blech, Rohre, Profile, 1993)
LFT Import::2019-07-15 (446)

Qualitätssicherung in der Laserstrahlschweißtechnik - Hoffmann, Peter; Deinzer, Günter; Geiger, Manfred (Blech, Rohre, Profile, 1992)
LFT Import::2019-07-15 (483)

Quality Assurance for Laser Beam Microbonding in Electronic Production - Geiger, Manfred; Glasmacher, Matthias; Pucher, Hans-Jörg (Production Engineering, 1994)
LFT Import::2019-07-15 (471)

Quality Control during Excimer Laser Material Processing - Geiger, Manfred; Lutz, Norbert; Rebhan, Thomas; Hutfless, Joachim (Proceedings of Gas Flow and Chemical Lasers, 1993)
LFT Import::2019-07-15 (411)

Randerscheinungen rücken ins Zentrum - Diehl, Alexander; Engel, Ulf; Geiger, Manfred (Mikroproduktion, 2005)
LFT Import::2019-07-16 (1238)

Rapid Prototyping für Aluminium-Bleche - Geiger, Manfred; Vollertsen, Frank (VDI-Berichte, 1994)
LFT Import::2019-07-15 (605)

Rapid Prototyping in Profile Forming by Means of Laser-Inducted Thermal Stresses - Geiger, Manfred; Kraus, Jürgen; Hoffmann, Peter; Vollertsen, Frank (Rapid Prototyping in the Automative Industries, Proc. Of the 28th ISATA, 1995)
LFT Import::2019-08-05 (557)

Rapid Prototyping von keramischen Bauteilen: Der SLC-Prozess - Niebling, Frank; Sindelar, R.; Otto, Andreas; Prechtl, Martin; Travitzky, N.; Geiger, Manfred; Greil, Peter (Keramik im Fahrzeugbau, 2003)
LFT Import::2019-07-15 (938)

Rapid tooling beim IHU - Prier, M.; Engel, B.; Geiger, Manfred; Celeghini, Martino (7. Forum Innenhochdruckumformen. Darmstadt, 2001)
LFT Import::2019-08-05 (915)

Rapid Tooling by Laminated Object Manufacturing of Metal Foil - Prechtl, Martin; Otto, Andreas; Geiger, Manfred (Advanced Materials Research, 2005)
The technology of Laminated Object Manufacturing (LOM) is not very new. For hundreds of years wooden parts are built by stacking layers together. Nowadays also paper, plastic, ceramic composite and metal sheets are treated in layers. For the manufacture of prototypes and especially technical tools, e. g. moulds for gravity casting, die casting or injection molding, out of metallic foil however the low self stiffness of this material is a great challenge. In this case it is useful to produce the parts in a two step process. The first subprocess is the stacking of the layers, which can be realised by laser beam spot welding to determine the position of the layer in combination with generating the defined contour by a laser beam cutting process. This procedure is done in a fully automated machine where the CAD-file of the desired part and the building parameters like the laser parameters and the cutting velocity are needed as input. However the stability of the produced green part is insufficient for most kind of application. Hence, a second sub-process to enhance the mechanical properties of the part is necessary. This can for example be realised by high temperature soldering or by diffusion welding in a furnace with inert gas or vacuum. During these kinds of joining processes the green part is homogeneously pressed with the help of a powder bed and at the same time it is tempered for a defined term. In this paper the principle of sheet metal LOM is described as well as the process chain of Laminated Object Manufacturing of metal foil. For each sub-process of metal foil LOM the results of the experimental work for qualifying and optimizing the sub-process are shown. Finally some examples of possible applications especially in the field of Rapid Tooling and Rapid Manufacturing are discussed.
LFT Import::2019-07-16 (1245)
Keywords: Diffusion welding; Laser cutting; Laser welding

Rapid tooling - Current Status and Future Trend - Eßer, Gerd; Niebling, Frank; Geiger, Manfred (Proceedings of the 3rd International Conference on Industrial Tools (ICIT 2001), 23.-26. April Slatina, Celje, Slowenien, 2001)
LFT Import::2019-08-05 (858)

Recent Developments in Laser System Technology for Welding Applications - Hoffmann, Peter; Geiger, Manfred (CIRP Annals - Manufacturing Technology, 1995)
Further spreading of laser welding technology essentially needs an improvement of the reliability of the welding systems and an enlargement of applicability even at complicated workpiece structures. With this paper measures are proposed in order to meet these goals: - stabilization of the laser source by a closed loop control of the laser power - optimization of the laser beam guiding and forming by use of Adaptive Optics. © 1995 CIRP.
LFT Import::2019-07-15 (565)
Keywords: laser; quality assurance; welding

Rechnergestützte Fertigungsvorbereitung für komplexe Blechbiegeteile - Geiger, Manfred; Geißler, Uwe; Hoffmann, Martin (CIM-Management, 1990)
LFT Import::2019-07-15 (724)

Rechnergestützter Entwurf von Aktorsystemen für die lasergebundene Mikrojustage - Plettke, Raoul; Hagenah, Hinnerk; Geiger, Manfred (Simulation und Visualisierung 2007. Proceedings of the 18th Conference on Simulation and Visualization (SimVis), 2007)
LFT Import::2019-08-05 (139)

Rechnergestützte Werkzeugplanung für Blechbiegeteile - Geiger, Manfred; Franke, Volker (Blech, Rohre, Profile, 1995)
LFT Import::2019-07-15 (538)

Rechnerunterstützte Auslegung von Pressengestellen - Ergebnisse einer Modelluntersuchung - Geiger, Manfred (Industrieanzeiger, 1974)
LFT Import::2019-07-12 (164)

Reduzierung der Durchflußmengenstreuung laserstrahlerzeugter Bohrungen - Geiger, Manfred; Hoffmann, Peter; Bartl, Norbert; Schmidt-Hebbel, Robert (Abtragen und Bohren mit Festkörperlasern, 1993)
LFT Import::2019-07-15 (405)

Reibrührschweißen - Innovativ in der festen Phase verbinden - Geiger, Manfred; Merklein, Marion; Giera, Artur (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2005)
LFT Import::2019-07-16 (1241)

Representing Process Knowledge Using a Hybrid Fuzzy Rule Approach - Geiger, Manfred; Menzel, Thomas; Novotny, Stefan (Production Engineering. Annals of the German Academic Society for Production Engineering, 2000)
LFT Import::2019-08-05 (771)

Requirements towards future laser systems for flexible manufacturing - Eßer, Gerd; Otto, Andreas; Geiger, Manfred (LANE 2004, Proceedings of the 4th International Conference on Laser Assisted Net Shape Engineering, 2004)
LFT Import::2019-08-05 (1106)

Residual Stresses and Distortion due to Laser Beam Welding - Geiger, Manfred; Deinzer, Günter (LSEN, F.O.; Proc. 4th NOLAMP Conf. on Laser Material Processing, 1993)
LFT Import::2019-08-05 (391)

Residual Stresses and Distortion during Laser Beam Welding - Measurement and Strategies to Minimize - Geiger, Manfred; Deinzer, G (Proceedings of the 3rd European Conference on Residual Stresses, 1992)
LFT Import::2019-07-15 (368)

Resonant Simulation of Laser Welding Processes - Geiger, Manfred; Geisel, Mark; Otto, Andreas (Production Engineering, 1998)
LFT Import::2019-07-16 (1589)

Richten von Blechformteilen mittels laserinduzierten thermischen Spannungen - Hoffmann, Peter; Kraus, Jürgen; Geiger, Manfred (Laser in der Technik. Vorträge des 11. Internationalen Kongresses (LASER 93), 1993)
LFT Import::2019-08-05 (424)

Robust and shortened process sequences for sheet light weight parts - Geiger, Manfred; Otto, Andreas (Proceedings of the Int. Workshop on Environmentally Conscious Manufacturing - Ecology and Economy in Metal Forming and Cutting (ICEM-98), 1998)
LFT Import::2019-08-05 (1593)

Robuste, verkürzte Prozessketten für flächige Leichtbauteile - Herausforderung für Forschung und Entwicklung - Kerausch, Michael; Geiger, Manfred (Robuste, verkürzte Prozessketten für flächige Leichtbauteile. Tagungsband zum Industriekolloquium 2003 des SFB 396, 2003)
LFT Import::2019-08-05 (998)

Robust, shortened process sequences for sheet light weight parts - Geiger, Manfred; Merklein, Marion; Kerausch, Michael; Celeghini, Martino (Proceedings of the 5th International Conference on Industrial Tools, 2005, Velenje, Slowenien, 2005)
LFT Import::2019-08-05 (1177)

Scaling effects in sheet metal forming. - Kals, Roland; Vollertsen, Frank; Geiger, Manfred (Proc. of the 4th Int. Conf. on Sheet Metal, 1996)
LFT Import::2019-08-05 (661)

Schlüsseltechnologie Laser: Innovationen für den Fahrzeugleichtbau - Geiger, Manfred; Hoffmann, Peter; Schultz, Markus (ECLAT 1996, Laser treatment of materials, 1996)
LFT Import::2019-07-15 (647)

Schneiden und Schweißen von Karosserieteilen mit CO2-Hochleistungslasern - Hoffmann, Peter; Geiger, Manfred (Industrieanzeiger, 1990)
LFT Import::2019-07-15 (735)

Schneiden von Al- und Ti-Werkstoffen mit CO2-Lasern - Juckenath, B.; Bergmann, H.W.; Geiger, Manfred (Laser/Optoelektronik in der Technik, 1989)
LFT Import::2019-07-15 (435)

Section bending between a rigid roller and an elastic pad. - Arnet, Horst; Geiger, Manfred; Vollertsen, Frank (Sheet Metal 1997, Univ. of Ulster, Nordirland, 08.04.-10.04.1997, 1997)
LFT Import::2019-08-05 (686)

Selective Laser Curing of Preceramic Polymers - Sindelar, R.; Niebling, Frank; Buhler, P.; Greil, Peter; Geiger, Manfred (Laser Assisted Net shape Engineering, 2001)
LFT Import::2019-07-15 (874)

Sheet Hydroforming: Analytical Modeling and Experimental Verification of Complex Structures - Geiger, Manfred; Merklein, Marion; Tolazzi, Massimo (Production Engineering - Annals of the WGP, 2005)
LFT Import::2019-08-05 (1233)

Sheet Metal 1996: proceedings of the 4th International conference - Kals, H.J.J.; Shirvani, Bez; Singh, U.P.; Geiger, Manfred (University of Twente, 1996)

Sheet Metal 1997, Proceedings of the International Conference (SheMet'97) - Singh, U.P.; Geiger, Manfred; Kals, H.J.J.; Shirvani, Bez; et al. (University of Ulster at Jordanstown, 1997)

Sheet metal 1998, Proceedings of the International Conference - Kals, H.J.J.; Geiger, Manfred; Shirvani, Bez; Singh, U.P.; et al. (University of Twente, 1998)

Sheet Metal 1999, Proceedings of the 7 th International Conference on Sheet Metal - SheMet'99 - Geiger, Manfred; Kals, H.J.J.; Shirvani, Bez; Singh, U.P. (Meisenbach, 1999)

Sheet metal 2000: proceedings of the 8th international conference - Shirvani, Bez; Geiger, Manfred; Kals, H.J.J.; Singh, U.P. (University of Central England, 2000)

Sheet Metal 2001, Proceedings of the International Conference - Duflou, J. R.; Geiger, Manfred; Kals, H.J.J.; Shirvani, Bez; Singh, U.P. (Katholieke Universiteit Leuven, 2001)

Sheet Metal 2003: proceedings of the 10th international conference - Singh, U.P.; Geiger, Manfred; Kals, H.J.J.; Shirvani, Bez (University of Ulster at Jordanstown, 2003)

Sheet Metal 2005 - Geiger, Manfred; Duflou, Joost R.; Kals, H.J.J.; Shirvani, Bez; Singh, U.P. (Trans Tech Publications Ltd, 2005)
Proceedings of the 11th International Conference on Sheet Metal 2005, held at the Friedrich-Alexander University Erlangen-Nürnberg, Germany, 08-08 April 2005. <br
Keywords: Aluminum (Al); Finite Element Model (FEM); Forming; Laser; Sheet Metal; Simulation; Welding

Sheet Metal 2007 - Micari, Fabrizio; Geiger, Manfred; Duflou, Joost R.; Shirvani, Bez; Fratini, Livan; et al. (Trans Tech Publications, 2007)
Volume is indexed by Thomson Reuters CPCI-S (WoS). Collections of peer-reviewed papers always make excellent sources of knowledge and new ideas for researchers coming from both universities and industry. The present collection in particular provides interdisciplinary and international resources, thus encouraging the close cooperation of material scientists, manufacturing and computer engineers and promoting the diffusion of research results, and technology transfer, in all areas of Sheet Metal Processing and Characterizatio

Sheet metal forming - a new kind of forge for the future - Geiger, Manfred; Merklein, Marion (Key Engineering Materials, 2007)
Within the last years in sheet metal forming a trend towards forming at elevated temperatures as well as temperature assisted forming technologies can be observed. This development is caused by the increasing need on light and high strength materials in order to fulfill the demands of light weight structures. The decision which kind of temperature assistance is the most useful in order to improve the formability of the material depends on a hugh number of process influencing parameters, like e.g. the material itself, the geometry of the component, the number of forming operations etc.. In this paper the general possibility to separate different temperature assisted forming processes with regard to the used materials will be introduced. The different forming procedures will be explained and discussed. Examples with an industrial relevance are shown.
LFT Import::2019-07-16 (1467)
Keywords: Elevated temperature; Hot stamping; Sheet metal forming

Sheet Metal Forming at Elevated Temperatures - Neugebauer, Stephan; Altan, T.; Geiger, Manfred; Kleiner, M.; Sterzing, A. (CIRP Annals - Manufacturing Technology, 2006)
Due to the need to significantly reduce the part weights in automotive manufacturing, the use of lightweight materials becomes ever more important. Unfortunately, these materials are often associated with a limited cold formability. Due to this fact, production of large, complex sheet metal components using forming technology frequently entails increased expenditures. Moreover, processing high-strength materials requires correspondingly high processing forces and pressures. In order to find a solution to counter the disadvantages mentioned above, the use of elevated temperatures as a process parameter in forming operations represents a potential solution approach. The following paper will give an overview about research activities in the field of forming operations at elevated temperatures.
LFT Import::2019-07-16 (1329)
Keywords: Forming; Metal; Temperature

Sheet Metal Hydroforming of Complex Components with a Ring-Shaped Geometry - Tolazzi, Massimo; Geiger, Manfred (Sheet Metal 2003, Proceedings of the 9th International Conference on Sheet Metal, 2003)
LFT Import::2019-08-05 (949)

Short Term Effects of Laser Forming in Aluminium Alloys - Geiger, Manfred; Merklein, Marion (Production Engineering, 2000)
LFT Import::2019-07-15 (772)

Simulation based optimisation of the accuracy of sheet metal bending parts caused by the manufacturing plan - Geiger, Manfred; Hagenah, Hinnerk; Menzel, Thomas (Proceedings of the 2nd CIRP International Seminar of Intelligent Computation in Manufacturing Engineering ICME 2000, 2000)
LFT Import::2019-08-05 (764)

Simulation der Versagensformen Verschleiß und Bruch bei Werkzeugen der Kaltmassivumformung - Engel, U; Hänsel, M; Sobis, T; Geiger, Manfred (Werkstatt und Betrieb, 1992)
LFT Import::2019-07-15 (362)

Simulation der Versagensformen Verschleiß und Bruch. - Engel, Ulf; Hänsel, Matthias; Sobis, Tomasz; Geiger, Manfred (Werkstatt und Betrieb, 1992)
LFT Import::2019-07-16 (1963)

Simulation des Laserstrahlschneidens von Kunststoffen - Geiger, Manfred; Müller, R; Foerster, A (Werkstattstechnik, 1991)
LFT Import::2019-07-15 (249)

Simulation des Laserstrahlschneidens von Werkstoffen mit geringer Wärmeleitfähigkeit - Geiger, Manfred; Müller, R (Laser/Optoelektronik in der Technik, 1991)
LFT Import::2019-07-15 (248)

Simulation of Microforming Processes - An Advanced Approach Apllying a Mesoscopic Model - Geißdörfer, Stefan; Engel, Ulf; Geiger, Manfred (Proceedings of the 8th International Conference on Technology of Plasticity (ICTP), 2005)
LFT Import::2019-08-05 (1250)

Simulation of Microforming Processes by Applying a Mesoscopic Model - Geißdörfer, Stefan; Engel, Ulf; Geiger, Manfred (Proceedings of the 4th International Conference on Multi-Material Micro Manufacture, 2008)
LFT Import::2019-08-05 (1532)

Simulation of Tool Life Cycle - Cser, L.; Geiger, Manfred (Proceedings of the 26th Plenary Meeting of the ICFG, 1993)
LFT Import::2019-08-05 (380)

Simulation of Warm Forming Processes - Bitter, Stefan; Falk, Bernd; Geiger, Manfred (Proceedings of the AMPT '01 Advances in Materials and Processing Technologies, 2001)
LFT Import::2019-08-05 (856)

Simulationsgestütze Analyse komplexer Strukturen beim IHU von Blechen - Geiger, Manfred; Vahl, Meik (Tagungsunterlagen zum Seminar Virtual Materials Processing des Kompetenzzentrums Neue Materialien Nordbayern GmbH, 2002)
LFT Import::2019-08-05 (1707)

Simulationsgestütze Bewertung des Einflusses von Technologieinnovationen auf die Produktion - Geiger, Manfred; Menzel, Thomas (Modellierung der Produktion. Abschlusskolloquium zum DFG - Schwerpunktprogramm. Hannover, 7. und 8. März, 2000)
LFT Import::2019-08-05 (770)

Simultanious Laser Beam Soldering of SMT-Components on MIDs with Fibre-coupled Laser Diodes. - Fröhlich, Thomas; Geiger, Manfred; Glasmacher, Matthias; Pucher, Hans-Jörg (Proceedings 2nd Int. Congress Molded Interconnected Devives - MID 96. Erlangen, 1996)
LFT Import::2019-08-05 (632)

Specific characteristics of micro sheet metal working - Eckstein, Ralf; Geiger, Manfred; Engel, Ulf (SHEET METAL 1999, Proc. Of the Int. Conf. SheMet‘99, 27-28 Sep 1999, Erlangen, Germany, 1999)
None
LFT Import::2019-08-05 (1999)

Specific surface treatment by laser irradiation under liquid films - Roth, Stephan; Geiger, Manfred (ICALEO 2000, Proceedings of the 19th International Congress on Applications of Lasers & Electro-Optics, 2000)
LFT Import::2019-08-05 (800)

Specimen for a Novel Concept of Biaxial Tension Test? Design and Optimisation - Hußnätter, Wolfgang; Merklein, Marion; Geiger, Manfred (Advanced Methods in Material Forming, 2007)
Although in times of highest significance of process modelling and numerical simulation yield loci get more and more important, these characteristic values do only exist for a few materials primarily at room temperature. In this paper a novel concept of an experimental setup is introduced, with which plastic yielding of sheet metal can be examined also at elevated temperatures. The design of specimen is of great importance for the quality of experimental results, because stress conditions and with it forming behaviour are constituted. Thus, it must be optimized in consideration of stress singularities at corners and for achieving stress states, which are comparable to those of previous yield locus examinations. Most information and details can be obtained from finite element simulation. © 2007 Springer-Verlag Berlin Heidelberg.
LFT Import::2019-07-16 (1389)
Keywords: FE-simulation; sheet metal forming; yield locus

Specimen for a novel concept of the biaxial tension test - Geiger, Manfred; Hußnätter, Wolfgang; Merklein, Marion (Journal of Materials Processing Technology, 2005)
LFT Import::2019-07-16 (1191)
Keywords: Biaxial testing; FE-simulation; Sheet metal

Spring-back behaviour of thing metal foils in free bending processes - Diehl, Alexander; Engel, Ulf; Geiger, Manfred (4M 2005, Proceedings of the 1st International Conference on Multi-Material Micro Manufacture, 2005)
LFT Import::2019-08-05 (1181)

Stahlbleche Laserstrahl-Schneiden - Nuss, Rudolf; Gropp, Armin; Biermann, Stefan; Geiger, Manfred (Werkstatt und Betrieb, 1989)
LFT Import::2019-07-15 (439)

Stahl heiß in Form gebracht - Geiger, Manfred; Merklein, Marion; Lechler, Jürgen (Automobiltechnik in Bayern, 2007)
LFT Import::2019-07-16 (1461)

Stand und Entwicklungstendenzen bei der Laseranwendung in der Blechbearbeitung - Geiger, Manfred; Coremans, Arjan (Blechbearbeitung, VDI Berichte, 1994)
LFT Import::2019-08-05 (463)

Starker Anstieg an Bewerberzahlen an der Uni Erlangen-Nürnberg - Geiger, Manfred; Kreis, Oliver (t&m - Technologie & Management, 2002)
LFT Import::2019-07-16 (1666)

State of the Art in Laser Material Processing - Geiger, Manfred; Schultz, Markus; Hoffmann, Peter (ISEM 1992, State of the Art in Laser Material Processing. In: Proc. of the 10th International Symposium on Electromachining, 1992)
LFT Import::2019-08-05 (479)

Statistical Investigations on Friction Stir Welded - Giera, Artur; Merklein, Marion; Geiger, Manfred (Sheet Metal 2005, Proceedings of the 11th International Conference on Sheet Metal, 2005)
LFT Import::2019-08-05 (1163)

Strahlformungskomponenten für das simultane Laserstrahllöten - Fröhlich, Thomas; Brickert, M.; Geiger, Manfred (Laser in der Elektronikproduktion & Feinwerktechnik, 2001)
LFT Import::2019-08-05 (860)

Strömungsbeeinflusstes Innenhochdruckumformen - Geiger, Manfred; Dal Bò, Paolo (Abschlusskolloquium des DFG Schwerpunktprogramms 1074, 2.-3. Mai 2005, Aachen, 2005)
LFT Import::2019-08-05 (1195)

Study of Micro Sheet Metal Working Processes - Geiger, Manfred; Eckstein, Ralf; Engel, Ulf (Production Engineering, 2001)
LFT Import::2019-07-15 (846)

Surface characterization with regard to the tribological behaviour of sheet metal in forming processes - Popp, Uwe; Engel, Ulf; Geiger, Manfred (SHEET METAL 1999, Proc. Of the Int. Conf. SheMet‘99, 27-28 Sep 1999, Erlangen, Germany, 1999)
None
LFT Import::2019-08-05 (2000)

Synergies of laser material processing and metal forming - Geiger, Manfred; Otto, Andreas (Characterization of Manufacturing, Proceeding of the Workshop, Ljubljana 25-26. Mai, Processes: Synergetics and Data Processing Methods, 2000)
LFT Import::2019-08-05 (773)

Synergy of Laser Material Processing and Metal Forming - Geiger, Manfred (CIRP Annals - Manufacturing Technology, 1994)
It will be shown, on the basis of selected examples in the field of metal forming, how metal forming and laser beam processing can be combined in a synergetic way. A characteristic of metal forming is its ability for large scale manufacturing with high quality. Laser material processing is characterized by a high process, product, and quantity flexibility. Synergetic combinations of both processes enable completely new solutions for products and technologies. Although most of these developments are still in their initial phase, the first industrial applications have already proved their potential economical viability. © 1994 CIRP.
LFT Import::2019-07-15 (459)
Keywords: Forming; Laser Material Processing; Sheetmetal

Systemanalyse des dynamischen Prozessverhaltens beim Laserstrahlschweißen - Hohenstein, Ralph; Otto, Andreas; Geiger, Manfred (Strahl-Stoff-Wechselwirkung bei der Laserstrahlbearbeitung 2, Strahltechnik, 1998)
LFT Import::2019-07-16 (1607)

Task Specific Registration Algorithmy within the Closed Loop Control of Laser Forming Processes - Geiger, Manfred; Hagenah, Hinnerk; Hutterer, Angelika (Production Engineering, 2005)
LFT Import::2019-07-16 (1186)

Technik – die prägende geistige Errungenschaft unserer Zeit. Festvortrag zum dies academicus aus Anlass des 261. Jahrestages der Gründung der Friedrich-Alexander-Universität Erlangen-Nürnberg am 4. November 2004 - Geiger, Manfred; Kreis, Oliver; Gaus, Ingrid (FAU, 2005)

Techniken in der Klein- und Mittelserienfertigung von Blechteilen - Geiger, Manfred; Geißler, U (Technische Rundschau, 1991)
LFT Import::2019-07-15 (239)

Technische Keramik in der Kaltmassivumformung? Verbesserung der Oberflächenqualität und Maßhaltigkeit - Arbak, Murat; Putz, Alexander; Engel, Ulf; Geiger, Manfred (Maschinenbau in Bayern, 2006)
LFT Import::2019-07-16 (1281)

Technological Comparison of CO2- and Nd:YAG-Laser Manufacturing Systems - Geiger, Manfred; Gropp, A; Hoffmann, P (Proc. of Laser Applications in the Automotive Industries (25th ISATA), 1992)
LFT Import::2019-08-05 (373)

Technology oriented Off-line programming for 3D Laser Processing. - Backes, Frank; Geiger, Manfred; Franke, Volker (Technical Papers of the North American Manufacturing Research Institution, 1996)
This paper describes the concept and basic algorithms of a flexible off-line programming system which has been specially developed for 3D laser processing tasks such as cutting or welding. The most important feature of the system is a technology oriented path planning, which simultaneously considers the part geometry, the particular process parameters and the properties of the machine tool.
LFT Import::2019-08-05 (585)
Keywords: 3D Laser Processing; Off-Line Programming

Technology Oriented Off-line Programming of 3D-Laser Machines - Geiger, Manfred; Backes, Frank; Menzel, Thomas (Production Engineering, 1998)
LFT Import::2019-07-16 (1588)

Tecnica della formatura alla 41a Assemblea Generale del CIRP - Geiger, Manfred; Cser, L (Il filo metallico, 1992)
LFT Import::2019-07-15 (366)

Temperature and stress development in the DMLS process - Niebling, Frank; Otto, Andreas; Geiger, Manfred (LANE 2004, Proceedings of the 4th International Conference on Laser Assisted Net Shape Engineering, 2004)
LFT Import::2019-08-05 (1105)

Temperaturfest kontaktieren - Geiger, Manfred; Schmidt, Michael (Laser-Praxis, 1998)
LFT Import::2019-07-16 (1596)

The Coatings in Manufacturing Engineering - Merklein, Marion; Bach, Friedrich-Wilhelm; Bouzakis, Konstantinos D.; Denkena, Berend; Geiger, Manfred; Toenshoff, H. - K. (Trans Tech Publications, 2010)
Coating technology has made great strides during recent years. The properties of surface layers determine the function and quality of entire components. Thus, it is essential to obtain information concerning the development and functionality of the topmost layers. The beneficial effect of coating technology can be observed in many manufacturing fields, where it solves problems such as wear, corrosion, erosion, electrical contact, etc. Even decoration falls under this headin
Keywords: Aluminium Oxide; Bionic Layer; Coating; Cohesive Damage; Contact Angle (CA); Diamond-Like Carbon (DLC); Finite Element Analysis (FEA); Friction; Hot Stamping; Mechanical Property; Optically Non-Cooperative Surface; Plasma Nitriding; Precision Glass Molding; PtIr; PVD Film; Simulation; Thermal Spraying; Tribology; Ultra-Precision Machining; Wear

The Mechanisms of Laser Forming - Geiger, Manfred; Vollertsen, Frank (CIRP Annals - Manufacturing Technology, 1993)
Laser forming is a complex dynamic forming process. Its basic feature is the forming by thermal stresses, induced by irradiation of a laser beam. A two-layer model for laser bending is proposed, which is capable to describe the process in spite of many restrictions which have to be made. It is shown that the coefficient of thermal expansion is one of the most significant parameters for the process. The model shows the right dependence on the sheet thickness and the right order of magnitude for the bend angle which can be obtained in one step of the laser bending process. Possible extentions of the model are discussed, using experimental results which had shown that the neutral line lies at a relative thickness z/s0 = 0.65. © 1993 CIRP.
LFT Import::2019-07-15 (414)
Keywords: forming; laser beam application; simulation

Thermoelement- Sensorik- ein Lagesensor für CO2- Hochleistungslaser - Geiger, Manfred; Hutfless, J; Hoffmann, P (Strahltechnik (3. Int. Konferenz Strahltechnik, Karlsruhe), DVS- Bericht, 1991)
LFT Import::2019-08-05 (245)

The use of dry film lubricants in aluminium sheet metal forming - Meiler, M.; Pfestorf, Markus; Geiger, Manfred; Merklein, Marion (Wear, 2003)
LFT Import::2019-07-16 (1005)
Keywords: Aluminum; Friction; Textures; Tribology

The use of kinematic chains and construction catalogues for an advanced design of complex actuator geometries in micro adjustment - Wurm, Thomas; Menzel, Thomas; Müller, Burkhard; Hagenah, Hinnerk; Geiger, Manfred (Proceedings: International CIRP Design Seminar: Design in the New Economy; Design Theory, Methodology and its Intergration with the Computational Tools to support Teams of Competence, 2001)
LFT Import::2019-08-05 (824)

Three Dimensional Characterization of Surfaces for Sheet Metal Forming - Pfestorf, Markus; Engel, Ulf; Geiger, Manfred (Wear, 1998)
In metal-forming processes, the load at the interface between workpiece and die is transmitted by three different kinds of bearing ratios. These are the real contact area, which is represented by the solid contact, and the static and dynamic lubricant pockets. As the real contact area is already well known from other researchers, the static and dynamic lubricant pockets are newly defined bearing ratios that characterize the contact mechanisms in mixed lubrication. To determine them with respect to the topography, three-dimensional surface parameters have to be defined. These are the material area ratio, as well as the open and closed void area ratio. As it is shown in the paper, the maximum of the closed void area ratio and the closed void volume seem to be distinctive features for characterizing the tribological properties of the surface, even if there are only slight variations in the surface topography. In order to determine these characteristic parameters, the surface is mapped three-dimensionally by an optical measuring device. Based on the measured surface data, the area ratios can be calculated by the program SAM (surface analysis module) which will also be presented in the paper. © 1998 Elsevier Science S.A. All rights reserved.
LFT Import::2019-07-16 (1616)
Keywords: 3D surface parameters; Sheet metal forming; Tribology

Three Dimensional CO2-Laser Material Processing with Gantry Machine Systems - Hoffmann, Peter; Biermann, Stefan; Geiger, Manfred; Nuss, Rudolf (Tagungsband Int. Congress on Optical Science & Engineering, 1990)
LFT Import::2019-08-05 (733)

Three kinds of case-based learning in sheet metal manufacturing - Cser, L; Geiger, Manfred; Greska, Wolfgang (Computers in Industry, 1991)
The paper outlines three applications of case-based learning in sheet metal manufacturing by utilization of artificial intelligence, each based on different concepts. One topic is the synthesis with feature processing for the process outline on a CNC bending machine. Statistics on fail and success influence weights of rules in an expert system. Another example is the classification of sheet metal parts. Real objects and their components are represented by a frame like data structure, which is embedded in a semantic network. Grouping of work pieces is done by a decision method of Bayes. This method is also used for part diagnosis to avoid possible defects of tools and machines. © 1991.
LFT Import::2019-07-15 (232)
Keywords: Classification; Computer aided planning; Failure; Features; Forming; Knowledge based systems

Time dependent determination of forming limit diagrams - Merklein, Marion; Kuppert, Andreas; Geiger, Manfred (CIRP Annals - Manufacturing Technology, 2010)
LFT Import::2019-07-29 (297)
Keywords: Failure criterion; Forming; Sheet metal

Time efficient Micro-Adjustment Based on a New Type of Laser-Operated Actuators - Dirscherl, Manfred; Eßer, Gerd; Geiger, Manfred (Proceedings Sensor 2003, Vol I, 2003)
LFT Import::2019-08-05 (981)

Tool Life Improvement by Surface Laser Texturing - Geiger, Manfred; Popp, Uwe; Engel, Ulf (THE Coatings, Proceedings of the 4th International Conference, 2004)
LFT Import::2019-08-05 (1042)

Tool Life & Tool Quality in Bulk Metal Forming - Lange, K.; Kals, J.A.G.; Geiger, Manfred; Cser, Laszlo (Annals of the CIRP, 1992)
LFT Import::2019-08-07 (485)

Tool Life und Tool Quality in Bulk Metal Forming - Cser, L.; Lange, K.; Geiger, Manfred; Kals, J.A.G. (Wire, 1993)
LFT Import::2019-07-15 (390)

Tool Path Optimization for 2D Laser Cutting - Geiger, Manfred; Kollera, Harald (Production Engineering - Annals of the WGP, 1994)
LFT Import::2019-08-05 (593)

Tool Planning for Complex Bending Parts - Geiger, Manfred; Franke, Volker (Production Engineering, 1995)
LFT Import::2019-07-15 (539)

Tool Quality in Bulk Metal Forming - Cser, L.; Geiger, Manfred; Lange, K.; Kals, J.A.G. (Proceedings of the Institution of Mechanical Engineers, Part B: Journal of Engineering Manufacture, 1993)
LFT Import::2019-07-15 (384)

Towards a better understanding of laser beam melt ablation using methods of statical analysis - Cser, Adrienn Orsolya; Donner, R.; Schwarz, U.; Otto, Andreas; Geiger, Manfred; Feudel, U. (Proceedings of the 3rd CIRP International Seminar on Intelligent Computation in Manufacturing Engineering (ICME 2002), 2002)
LFT Import::2019-08-05 (1672)

Towards Clean Forming Techniques (Keynote Paper) - Geiger, Manfred (Annals of the CIRP, 1995)
LFT Import::2019-08-05 (517)

Towards Hot Crack Free Welding of Aluminium alloys Using FEM Simulations - Geiger, Manfred; Komlodi, Attila; Otto, Andreas (Production Engineering - Annals of the WGP (2004), 2004)
LFT Import::2019-08-05 (1092)

Towards optimized lubrication by micro texturing of tool surfaces - Neudecker, Thomas; Popp, Uwe; Engel, Ulf; Geiger, Manfred (Advanced Technology of Plasticity 1999, Proc. of the 6th Int. Conf. on Technology of Plasticity, Vol. 1, 1999)
None
LFT Import::2019-08-05 (1998)

Transfer of Contact Conditions for Failure Analysis of Metal Forming Tools - Sobis, Tomasz; Engel, Ulf; Geiger, Manfred (Numerical Methods in Industrial Forming Processes - NUMIFORM 92, Rotterdam : Balkema, 1992)
LFT Import::2019-08-05 (489)

Transiente Prozesse beim Laserstrahlschneiden - Otto, Andreas; Geiger, Manfred (Strahl-Stoff-Wechselwirkung bei der Laserstrahlbearbeitung 2, Strahltechnik, 1998)
LFT Import::2019-07-16 (1614)

Tribiological Properties of Dry Film Lubricants in Aluminium Sheet Metal Forming. - Meiler, M.; Pfestorf, Markus; Merklein, Marion; Geiger, Manfred (Processing of the 2nd International conference on Tribology in Manufacturing Processes, Nyborg, Denmark, June 15-18 2004, 2004)
LFT Import::2019-08-05 (1057)

Tribological Properties of Ceramics after Machining with XeCl Excimer Laser Radiation. - Geiger, Manfred; Becker, Wolfgang (Production Engineering, 1996)
LFT Import::2019-07-15 (636)

Tribologische Eigenschaften von Keramikoberflächen nach einer Endbearbeitung mit Excimerlaserstrahlung - Geiger, Manfred; Hutfless, Joachim; Becker, Wolfgang; Tönshoff, H.-K.; Von Alvensleben, F.; Kappel., H. (Tagungsband zum Werkstoffkolloquium: Laserinduzierte Hochtemperatur-Werkstoffprüfung und -optimierung, 1995)
LFT Import::2019-08-05 (547)

Tribology and influence of tool coatings on frictional conditions within forming of advanced high strength steels - Merklein, Marion; Geiger, Manfred; Kaupper, Markus (Conference Proceedings, 7th International Conference THE Coatings, 2008)
LFT Import::2019-08-05 (205)

Ultraschallschneiden von kurzglasverstärkten PUR-Formteilen - Geiger, Manfred; van der Heyd, Gerhard; Müller, Roland (Kunststoffe, 1989)
LFT Import::2019-07-15 (434)

Ultrasonic Inspection of Cold Forging Tools - Geiger, Manfred; Putz, Alexander; Engel, Ulf (Production Engineering - Annals of the WGP, 2006)
LFT Import::2019-08-05 (1265)

Ultrasonic Inspection of Stress State of Prestressed Extrusion Dies - Geiger, Manfred; Engel, Ulf; Pfestorf, Markus (Production Engineering, 1994)
LFT Import::2019-07-15 (467)

Ultrasonic Investigation of Friction Mechanism in Metal Forming - Niederkorn, Sorin; Engel, Ulf; Geiger, Manfred (Journal of Materials Processing Technology, 1994)
A newly developed friction and lubrication test is used to examine the quantitative relation between real contact area (r.c.a.) and coefficient of friction in metal forming processes. The first part of the paper will give a description of the experimental set-up. It enables the in-situ ultrasound measuring of the r.c.a. simultaneously to the measuring of the friction coefficient in the second part the relation between r.c.a. and the coefficient of friction is analysed, using a ring and a closed-die upsetting test to determine the coefficient of friction, each combined with the ultrasound method for measuring the r.c.a. © 1994.
LFT Import::2019-07-15 (625)

Ultrasonic Measurement of the Real Contact Area between Die and Ring in Prestressed Cold Forging Tools - Putz, Alexander; Engel, Ulf; Geiger, Manfred (ISPF 2004, Proceedings of the 3rd JSTP International Seminar on Precision Forging, 2004)
LFT Import::2019-08-05 (1025)

Umformen in der Fertigungstechnik - Entwicklungstendenzen bei Verfahren und Maschinen - Lange, K.; Geiger, Manfred; et al. (Industrieanzeiger, 1971)
LFT Import::2019-07-11 (154)

Umformtechnik auf der 41. CIRP- Generalversammlung - Geiger, Manfred; Cser, L (Umformtechnik 25/4, 1991)
LFT Import::2019-08-05 (236)

Umformtechnik auf der 42. CIRP-Generalversammlung - Geiger, Manfred; Cser, L. (Umformtechnik, 1993)
LFT Import::2019-07-15 (388)

Umformtechnik auf der 43. CIRP-Generalversammlung - Geiger, Manfred; Coremans, Adrianus (Blech, Rohre, Profile, 1994)
LFT Import::2019-07-15 (388)

Umformtechnik auf der 44. CIRP-Generalversammlung. - Geiger, Manfred; Coremans, Arjan (Blech, Rohre, Profile, 1995)
LFT Import::2019-07-15 (527)

Umformtechnik auf der 45. CIRP-Generalversammlung. - Geiger, Manfred; Coremans, Arjan (Blech, Rohre, Profile, 1995)
LFT Import::2019-07-15 (528)

Umformtechnische Herstellung kleiner Bauteile - Siegert, K.; Frank, H.; Geiger, Manfred; Eckstein, Ralf; Neugebauer, R.; Schubert, A.; Böhm, J. (FTK 2000 - Fertigungstechnisches Kolloquium. Schriftliche Fassung der Vorträge zum Fertigungstechnischen Kolloquium am 26./27. September 2000 in Stuttgart, 2000)
LFT Import::2019-08-05 (803)

Umformtechnische Herstellung metallischer Kleinstteile - Geiger, Manfred; Engel, Ulf; Eckstein, Ralf; Tiesler, Nicolas (Sonderforschungsbereich 356 Produktionssysteme in der Elektronik, 2001)
LFT Import::2019-08-05 (847)

Umformtechnische Herstellung metallischer Kleinstteile - Werkstoffverhalten und Wirkflächenreibung - Geiger, Manfred; Meßner, Arthur; Engel, Ulf (Tagungsband zur 2. Sächsischen Fachtagung Umformtechnik, 1995)
LFT Import::2019-08-05 (549)

Umformtechnische Herstellung metallischer Kleinstteile - Werkstoffverhalten und Wirkflächenreibung - Geiger, Manfred; Meßner, Arthur; Engel, Ulf (Tagungsband 2. Sächsische Fachtagung Umformtechnik, 1995)
LFT Import::2019-08-05 (1984)

Umformung von Tailored Heat Treated Blanks aus Aluminium - Merklein, Marion; Geiger, Manfred (Metall, 2006)
LFT Import::2019-07-16 (1300)

Untersuchung der thermo-mechanischen Fließeigenschaften presshärtbarer Stähle - Merklein, Marion; Lechler, Jürgen; Geiger, Manfred; Kleiner, M.; Karbasian, H.; Homberg, W. (Proceedings of the 2nd International Conference on Accuracy in Forming Technology ICAFT 2006, in Verbindung mit 13. sächsische Fachtagung Umformtechnik SFU 2006, 2006)
LFT Import::2019-08-05 (1341)

Untersuchungen an einem Gestellmodell - Roll, K.; Felgner, W.; Geiger, Manfred (Industrieanzeiger, 1975)
LFT Import::2019-07-15 (331)

Untersuchungen zum Blechbiegen mit elastischem Werkzeug - Geiger, Manfred; vom Ende, Arnold; Engel, Ulf (Blech, Rohre, Profile, 1992)
LFT Import::2019-07-15 (480)

Untersuchung und Berechnungen der Spannungen und Verformungen von mechanisch weggebundenen Pressen. Beitrag zur rechnerunterstützten Auslegung von Pressgestellen - Geiger, Manfred (VDW-Bericht, 1975)
LFT Import::2019-07-12 (169)

Use of design experiments in the modeling of a hydro-forming tool - Celeghini, Martino; Geiger, Manfred (9th International Conference on Sheet Metal (SheMet 2001), Leuven (Belgien) 02.-04.04.2001, 2001)
LFT Import::2019-08-05 (857)

Use of Optical 3-D Sensing for In-Process Measurement of Workpiece Contours. - Heckel, Werner; Geiger, Manfred (Manufacturing Systems, 1995)
LFT Import::2019-07-15 (563)

Use of pre-pulse in laser spot welding of materials with high optical reflection - Mys, R.; Geiger, Manfred (Laser Precision Microfabrication LPM 203, Proceedings of SPIE, 2003)
Laser micro welding has become a standard manufacturing technique, particularly in industry sectors, such as automotive and aerospace electronics or medical devices, where the requirements for strength, miniaturization and temperature resistance are constantly rising. So far the use of laser micro welding is limited due to the fluctuation of the quality of the welded joints, because the welding results for material with high optical reflection and thermal conductivity, such as copper and copper alloys, depend very strongly on the condition of the material surface. This paper presents investigations on the use of a laser pre-pulse in spot welding of electronic materials with Nd:YAG laser. In order to achieve reproducible joining results two strategies are followed-up. The first one utilizes a reflection-based process control for measuring the reflection during the short pre-pulse. The intensity of the reflected light is used to calculate an appropriated welding pulse power, which corresponds to the measured relative absorption. Adjustment of laser parameters according to the condition of the surface is done in real time before laser main pulse. A second possibility for the stabilization of copper welding is the employment of a short and powerful laser pre-pulse before laser main pulse. This pre-pulse affects the workpiece surface and creates more reproducible absorption conditions for the main pulse, independent from the initial situation on material surface.
LFT Import::2019-08-05 (1009)
Keywords: Laser micro welding; Pre-pulse; Process control; Sensors

Verallgemeinerte Ansätze der elementaren Plastizitätstheorie zur Kraftberechnung bei Umformvorgängen - Geiger, Manfred; Geiger, R. (Industrieanzeiger, 1973)
LFT Import::2019-07-12 (159)

Verbesserter Materialfluss beim Tiefziehen von Aluminiumblechen durch lokale Laserwärmebehandlung - Kerausch, Michael; Merklein, Marion; Geiger, Manfred (Tagungsband zum XXII. Verformungskundlichen Kolloquium, 2003)
LFT Import::2019-08-05 (951)

Verbesserung der Arbeitsgenauigkeit bei der Herstellung von Blechteilen mit U-förmigen Querschnitt durch Biegen mit elastischer Matrize - vom Ende, Arnold; Engel, Ulf; Geiger, Manfred (Blech, Rohre, Profile, 1989)
LFT Import::2019-07-15 (442)

Verfahrensentwicklung zum kombinierten Laserstrahlschneiden und -schweißen - Rief, A; Geiger, Manfred; Pollmann, W (Strahltechnik, 1991)
LFT Import::2019-07-15 (352)

Verfahrensfolge Laserstrahlschneiden und -schweißen - Geiger, Manfred; Hoffmann, Peter; Deinzer, Günter (3D-Bearbeiten mit CO2-Hochleistungslasern, 1992)
LFT Import::2019-07-15 (475)

Verfahrensgrundlagen zum Laserstrahlschneiden - Nuss, Rudolf; Geiger, Manfred (Laser und Optoelektronik, 1988)
LFT Import::2019-07-15 (285)

Verfahrensgrundlagen zur Laserstrahlbearbeitung mit prozessoptimierten Optiken - Neubauer, Norbert; Otto, Andreas; Geiger, Manfred (Strahl-Stoff-Wechselwirkung bei der Laserstrahlbearbeitung 2, Strahltechnik, 1998)
LFT Import::2019-07-16 (1611)

Verfahren und Simulation zur umformtechnischen Charakterisierung von Tailored Hybrid Blanks - Geiger, Manfred; Merklein, Marion; Staud, Detlev; Giera, Artur (Berichtskolloquium der DFG-Forschergruppe 505, 2005)
LFT Import::2019-08-05 (1243)

Vergleichende Untersuchungen zur Laserstrahlüberwachung an einem CO2-Hochleistungslaser - Biermann, Stefan; Hutfless, Joachim; Lutz, Norbert; Nuss, Rudolf; Geiger, Manfred (Laser/Optoelektronik in der Technik, 1989)
LFT Import::2019-07-15 (430)

Verkürzte Prozessketten in der Blechumformung - Geiger, Manfred; Otto, Andreas; Hofmann, Achim; Kreis, O.; Celeghini, Martino (Robuste, verkürzte Prozessketten für flächige Leichtbauteile, Tagungsband zum 1. Kolloquiumsband des SFB 396, 24-25.05.2000, Nürnberg, 2000)
LFT Import::2019-08-05 (774)

Verkürzte Prozessketten in der Blechumformung - Kreis, Oliver; Geiger, Manfred; Otto, Andreas; Celeghini, Martino (Tagungsband zum 1. Berichtskolloquium des SFB 396 Robuste, verkürzte Prozessketten für flächige Leichtbauteile., 2000)

warm hydroforming of magnesium sheets? results and microstructural changes - Geiger, Manfred; Merklein, Marion; Hecht, Joachim (Proceedings of the 8th International Conference on Technology of Plasticity (ICTP), 09.-13.10., Verona, Italy, 2005)
LFT Import::2019-08-05 (1217)

Welding of Aluminium Alloys with a CO2-Laser of High Beam Quality. - Geiger, Manfred; Schultz, Markus; Hoffmann, Peter; Hutfless, Joachim (12. International Colloquium Advanced Manufacturing and Repair Technologies in Vehicle Industry, 1995)
LFT Import::2019-08-05 (554)

Werkstattnahe Programmierung von Laserstrahlschneidemaschinen - Geiger, Manfred; Kollera, Harald (Blech, Rohre, Profile, 1994)
LFT Import::2019-07-15 (594)

Werkstattnahe Programmierung von Laserstrahlschneidmaschinen - Geiger, Manfred; Kollera, Harald (Proc. of the MicroCAD-SYSTEM 93. Section I: Manufacturing Systems, Informatics, 1993)
LFT Import::2019-08-05 (409)

Werkstoffeigenschaften von Profilen nach dem Laserstrahlbiegen - Geiger, Manfred; Kraus, Jürgen; Vollertsen, Frank (Bänder, Bleche, Rohre, 1994)
LFT Import::2019-07-15 (598)

Werkstoffentwicklungen für Massenbauteile - Geiger, Manfred; Vollertsen, Frank (Symposium Neue Werkstoffe in Bayern, 1994)
LFT Import::2019-07-15 (606)

Werkstoffgerechte Bauteil- und Prozessauslegung in der Blechumformung - Merklein, Marion; Geiger, Manfred; Vogt, Uwe (Neuere Entwicklungen in der Blechumformung: Tagungsband, Stuttgart: Werkstoff-Informationsgesellschaft, 2006)
LFT Import::2019-08-05 (1301)

Werkstückgeometrie beim Aufweittiefziehen - Geiger, Manfred; Raghuathi, P.S. (Industrieanzeiger, 1977)
LFT Import::2019-07-15 (339)

Werkzeuglebensdauer und Werkzeugqualität in der Massivumformung - Cser, L.; Geiger, Manfred; Hänsel, Matthias (Tagungsband der internatinoalen Werkzeugkonferenz, 1993)
LFT Import::2019-08-05 (381)

Werkzeuglebensdauer und Werkzeugqualität in der Massivumformung - Cser, L.; Geiger, Manfred; Lange, K.; Kals, J.A.G.; Hänsel, Matthias (Umformtechnik, 1993)
LFT Import::2019-07-15 (382)

Werkzeug- und Halbzeugbeschichtungen für das direkte Presshärten - Wieland, Michael; Merklein, Marion; Geiger, Manfred (Moderne Beschichtungen zum Verschleißschutz von Werkzeugen, 2012)
LFT Import::2019-08-05 (1874)

Werkzeugversagen durch Bruch und Verschleiß - Geiger, Manfred; Engel, Ulf; Sobis, Tomasz; Hänsel, Matthias (Berichtsband des Berichtskolloquiums Gemeinschaftsprojekt Prozeßsimulation in der Umformtechnik, 1990)
LFT Import::2019-08-05 (506)

Wirkmedienbasierte Umformng von Tailor Welded Blanks - Tolazzi, Massimo; Merklein, Marion; Geiger, Manfred (Wirkmedienbasierte Fertigungstechniken zur Blechumformung, Abschlussbereicht zum DFG-Schwerpunktprogramm SPP 1098, 28.-29.09., Dortmund, 2006)
LFT Import::2019-08-05 (1311)

Wirkmedienbasierte Umformung tiefgezogener Tailored und Patchwork Blanks - Lamprecht, Klaus; Geiger, Manfred (Tagungsband zum 3. Kolloquium Wirkmedien-Blechumformung im Rahmen des DFG- Schwerpunktprogramms 1098 - Wirkmedienbasierte Fertigungstechniken zur Blechumformung, 2004)
LFT Import::2019-08-05 (1030)

Wirkmedienbasierte Umformung tiefgezogener Vorformen ausgehend von Platinen mit lokal unterschiedlichen Fließeigenschaften - Geiger, Manfred; Lamprecht, Klaus (Wirkmedienbasierte Fertigungstechniken zur Blechumformung, Abschlussbereicht zum DFG-Schwerpunktprogramm SPP 1098, 28.-29.09., Dortmund, 2006)
LFT Import::2019-08-05 (1297)

Wirkmedienbasierte Umformung von Rohren und Blechen bei erhöhten Temperaturen - Geiger, Manfred; Merklein, Marion; Celeghini, Martino; Haldenwanger, H.G.; Prier, M. (Hydroforming von Rohren, Strangpressprofilen und Blechen, 2003)
LFT Import::2019-07-15 (992)

Wirkmedienumformung inhomogener Platinen auf Basis von tiefgezogenen Vorformen - Lamprecht, Klaus; Geiger, Manfred (Tagungsband zum 2. Kolloquium Wirkmedien-Blechumformung im Rahmen des DFG-Schwerpunktprogramms 1098 - Wirkmedienbasierte Fertigungstechniken zur Blechumformung, 2003)
LFT Import::2019-08-05 (932)

Wirtschaftsingenieurwesen - Interdisziplinärer Studiengang an der Technischen Fakultät der Universität Erlangen-Nürnberg eingeführt - Geiger, Manfred; Mertens, P.; Kreis, Oliver; Barbian, D. (Technik in Bayern, 2001)
LFT Import::2019-07-15 (849)

Wissensbasierte Biegestadienplanung von komplexen Blechbiegeteilen - Geiger, Manfred; Hoffmann, M (Neuere Entwicklungen in der Blechbearbeitung (1992), Fellbach : Informationsgesellschaft Verlag, 1992)
LFT Import::2019-08-05 (376)

Wissensbasierte Klassifizierung von Blechformteilen - Geiger, Manfred; Greska, Wolfgang (Zeitschrift für Wirtschaftliche Fertigung und Automatisierung, 1992)
LFT Import::2019-07-15 (371)

Wissensbasiertes System zur Biegestadienplanung - Geiger, Manfred; Backes, Frank (Flexible Umformtechnik - Abschlußkolloquium zum DFG-Schwerpunktprogramm, 1995)
LFT Import::2019-08-05 (521)

Working Accuracy in Laser Bending. - Hennige, Thomas; Holzer, Stefan; Vollertsen, Frank; Geiger, Manfred (Proceedings of the Euro Laser Academy Seminar, 1995)
LFT Import::2019-08-05 (564)

Working Stresses in Prestressed Dies - Geiger, Manfred; Krämer, G. (Proc. 5th International Congress Cold Forging, Brighton/Großbritannien, 1975)
LFT Import::2019-08-05 (330)

Workshop Oriented Technology Planning for Laser Cutting Machines - Kollera, Harald; Geiger, Manfred (Manufacturing Systems, 1994)
LFT Import::2019-07-15 (620)

Zerstörungsfreie Überwachung umformtechnisch relevanter Blechkennwerte - Engel, Ulf; Schwind, Michael; Geiger, Manfred (EFB-Tagungsband T13: EFB Kolloqium: Möglichkeiten der Leistungssteigerung in der Blechverarbeitung, 1994)
LFT Import::2019-08-05 (456)

Zerstörungsfreie Überwachung von Blechkennwerten - Engel, Ulf; Schwind, Michael; Geiger, Manfred (Stahl, 1994)
LFT Import::2019-07-15 (457)